Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimatın e-memnuniyet, e-sadakat ve ödeme isteği üzerine etkisi: Tüketicilere yönelik karma yöntem uygulaması - Teki̇n, Makber (Akdeniz Üniversitesi, 2025)
Dijitalleşmenin hız kazandığı ve tüketici davranışlarının dönüşüme uğradığı günümüz e-ticaret ortamında, özellikle Covid-19 pandemisi sonrası çevrimiçi alışverişin yaygınlaşması sürdürülebilir lojistik uygulamalarının önemini artırmıştır. Artan sipariş hacmi, çevresel etkiler, karbon salımı ve teslimat sürelerine ilişkin beklentiler; daha verimli, esnek ve çevre dostu teslimat çözümlerine olan ihtiyacı gündeme getirmiştir. Bu bağlamda ev dışında teslimat gibi alternatif lojistik hizmetler ile sosyal, çevresel ve ekonomik sürdürülebilirlik yaklaşımları, tüketici davranışlarını etkileme potansiyeli taşıyan önemli değişkenler olarak öne çıkmaktadır. Bu doğrultuda tezin amacı, sürdürülebilir tedarik zinciri uygulamaları ile ev dışında teslimat modellerinin, e-memnuniyet, e-sadakat ve ödeme isteği üzerindeki etkilerini tüketiciler üzerinden incelemektir. Araştırma, açıklayıcı sıralı karma yöntem stratejisi ile yürütülmüştür. İlk aşamada 300'ü aşkın tüketiciden anket yoluyla nicel veriler toplanmış, ardından ikinci aşamada 27 katılımcı ile yapılan yarı yapılandırılmış görüşmeler aracılığıyla nitel veriler elde edilmiştir. Nicel veriler yapısal eşitlik modellemesiyle, nitel veriler ise tematik analiz yöntemiyle değerlendirilmiştir. Bulgular, özellikle sosyal ve çevresel sürdürülebilirlik boyutlarının e-memnuniyet üzerinde ve ekonomik ve çevresel sürdürülebilirlik boyutlarının ise e-sadakat üzerinde anlamlı etkiler yarattığı yönündedir. Sürdürülebilirliğin üç boyutu da ödeme istekliliği üzerinde anlamlı ve pozitif bir etki yaratmamıştır. Ekonomik sürdürülebilirlik boyutu ise tüketiciler tarafından doğrudan algılanamadığı için memnuniyet üzerinde anlamlı bir etki göstermemiştir. Ev dışında teslimat uygulamalarının esneklik, zaman tasarrufu ve erişilebilirlik gibi avantajlar sunarak e-memnuniyeti ve ödeme isteğini artırdığını göstermektedir. Son olarak e-memnuniyetin, e-sadakati ve e-sadakatin, ödeme isteğini pozitif yönde anlamlı etkilediği sonucuna ulaşılmıştır. Bu tez, sürdürülebilir tedarik zinciri yönetimi, ev dışında teslimat ve e-ticarette tüketici memnuniyeti, tüketici sadakati ve ödeme isteğini bütüncül biçimde ele alan özgün bir model sunmaktadır. Sürdürülebilir tedarik zinciri uygulamaları ve ev dışında teslimat hizmetlerinin tüketici davranışları üzerindeki etkilerini açıklamak amacıyla Sosyal Kimlik Teorisi (SIT), Yeşil Tüketici Davranışı Yaklaşımı ve destekleyici olarak Yeniliğin Yayılımı Teorisi (YYT) çerçevesinde şekillenen kuramsal yapı, sürdürülebilir uygulamaların tüketicilerdeki karşılığını açıklamaya yardımcı olmuştur. Ayrıca bu çalışma, Türkiye örneğinde sürdürülebilir teslimat hizmetlerine yönelik farkındalık düzeyini ve bu hizmetlerin e-memnuniyet, e-sadakat ve ödeme davranışları üzerindeki etkilerini analiz ederek hem akademik literatüre hem de pratik lojistik ve pazarlama stratejilerine katkı sunması beklenmektedir. In today's rapidly evolving e-commerce landscape, shaped by accelerated digitalization and shifting consumer behaviors, the widespread adoption of online shopping - particularly in the aftermath of the Covid-19 pandemic - has amplified the significance of sustainable logistics practices. Increasing order volumes, environmental impacts, carbon emissions, and heightened expectations regarding delivery times have underscored the need for more efficient, flexible, and eco-friendly delivery solutions. In this context, out-of-home delivery services and the dimensions of social, environmental, and economic sustainability have emerged as key variables with the potential to influence consumer behavior. Accordingly, the purpose of this dissertation is to examine the effects of sustainable supply chain practices and out-of-home delivery models on e-satisfaction, e-loyalty, and willingness to pay, through the lens of consumer perceptions. The research adopts an explanatory sequential mixed-methods design. In the first phase, quantitative data were collected via a survey administered to over 300 consumers; in the second phase, qualitative data were obtained through semi-structured interviews conducted with 27 participants. The quantitative data were analyzed using structural equation modeling, while the qualitative data were evaluated through thematic analysis. The findings indicate that the social and environmental dimensions of sustainability have a significant impact on e-satisfaction, while the economic and environmental dimensions significantly influence e-loyalty. None of the three dimensions of sustainability were found to have a significant and positive effect on willingness to pay. The economic dimension of sustainability did not show a significant effect on satisfaction, likely because it is not directly perceived by consumers. Out-of-home delivery practices were found to enhance e-satisfaction and willingness to pay by offering advantages such as flexibility, time savings, and accessibility. Finally, the results revealed that e-satisfaction has a positive and significant effect on e-loyalty, and e-loyalty, in turn, significantly and positively affects willingness to pay. This study aims to develop an original and integrative model that examines sustainable supply chain management, out-of-home delivery, and key consumer outcomes in e-commerce, namely e-satisfaction, e-loyalty, and willingness to pay. Grounded in the Social Identity Theory (SIT), the Green Consumer Behavior Approach, and supported by the Diffusion of Innovations Theory (DOI), the proposed theoretical framework explains how sustainable supply chain practices and out-of-home delivery services shape consumer behavior. Moreover, by investigating the level of awareness of sustainable delivery services in the Turkish context and analyzing their effects on e-satisfaction, e-loyalty, and payment behavior, this research is expected to provide significant contributions to both academic literature and practical implications for logistics and marketing strategies.
Keywords: E-commerce; E-ticaret; Ev Dışı Teslimat; Green Consumer Behavior; Karma Yöntem; Mixed Methods; Out-of-Home Delivery; Sustainable Supply Chain Practices; Sürdürülebilir Tedarik Zinciri Uygulamaları; Yeşil Tüketici Davranışı

Sermaye piyasası hukuku bakımından Mortgage - Aktaş, Mehmet Murat (Ankara Üniversitesi, 2024)
Türk mortgage sistemi veya mortgage menkul kıymetleştirmesi ve İpoteğe Dayalı Menkul Kıymetler-İDMK ihracı, sistemsel bütün olarak ilk kez uygulamada "Mortgage Kanunu" olarak da anılan 5582 sayılı "Konut Finansmanı Sistemine İlişkin Çeşitli Kanunlarda Değişiklik Yapılması Hakkındaki Kanun" (Konut Finansmanı Kanunu) ile 2007 yılında düzenlenmiştir. Meri'i düzenlemeler bakımından İDMK ihracı 6362 sayılı Sermaye Piyasası Kanunu (SerPK) madde 58 ve III-58.1 sayılı Varlığa ve İpoteğe Dayalı Menkul Kıymetler Tebliği (VİDMK Tebliği) ile düzenlenmiştir. Çalışmamızın amacı ve kapsamı, bünyesinde tek bir çalışmada ele alınması olanaksız sayıda hukuki düzenleme, kavram, kurum ve ilişki barındıran mortgage sistemini sermaye piyasası bakış açısıyla mevzuat tekrarlarından arındırılmış özlü tespit ve değerlendirmeleri esas alacak şekilde ele almaktır. Çalışmamızda mortgage sistemi kavramsal olarak gerçek anlamı ile ortaya konulacak ve ayrıca sistemin varlık nedeni ve özünü oluşturan sermaye piyasası unsuru olarak İDMK'ya ilişkin tespit, değerlendirme ve öneriler yer almaktadır. Mortgage ifadesi dar anlamda, Anglo-Sakson hukukunda kullanılan mortgage rehni ve mortgage teminatlı finansman alacaklarını ifade etmektedir. Mortgage terimi, sermaye ve finans piyasaları bakımından ise mortgage teminatlı alacakların İpoteğe Dayalı Menkul Kıymetler (İDMK/mortgage-backed securities-MBS) ihraç edilerek menkul kıymetleştirildiği (securitization) sistemi anlatmaktadır. Mortgage sistemi veya menkul kıymetleştirmesi ve İDMK ihracı ilk olarak Amerika Birleşik Devletleri (ABD) hukukunda uygulanmıştır. Mortgage sisteminin varlık nedeni, sermaye piyasalarından İDMK ihracı yoluyla en az maliyetle ve güvenilir bir şekilde finansman sağlanmasıdır. İDMK ihracı, mortgage (ipotek) teminatlı finansman alacaklarının, mortgage sistemi içerisinde gerçek satışa (true sale) dayalı olarak bilânço dışına çıkarılması ve menkul kıymetleştirilmesi ile gerçekleştirilmektedir. Bu nedenle İDMK, gerçek satışa dayalı bilânço dışı olarak gerçekleştirilen gerçek (geleneksel) menkul kıymetleştirme ürünü bir menkul kıymet niteliğindedir. Toplam beş bölümden oluşan Tez çalışmamızın ilk bölümünde, mortgage sistemi kavramı teknik anlamıyla değerlendirilecek, sistemin tarihi gelişim süreci ve ilişkili düzenlemeler ve niteliği olarak menkul kıymetleştirme ele alınacaktır. Çalışmamızın ikinci bölümünde, mortgage sisteminin işleyişi, sistemde kullanılan varlıklar ve safhaları, sistemin özgün terminolojisi berberinde değerlendirilecektir. Çalışmamızın üçüncü bölümünde ise mortgage sisteminde yer alan kuruluşlar gene sistemin kendine özgü kavram ve gereklilikleri dahilinde değerlendirilecektir. Çalışmamızın dördüncü bölümünde sistemin hedefi ve varlık sebebi olan İDMK tanımı türleri ve benzeri menkul kıymetler beraberinde ele alınacaktır. Çalışmamızın beşinci ve son bölümünde ise İDMK ihracı ile sağlanan sebepler ve ihracını güçleştiren sebeplere dair tespit ve önerilerimiz topluca yer alacaktır. Tezimizin sonuç kısmında ise gerçek anlamıyla uygulanması halinde ülkemizin hızlı ve sürdürülebilir bir biçimde kalkınmasını sağlayabilecek niteliği haiz bir sistem olan mortgage sistemi ve onun ürünü menkul kıymet olan İDMK'nın ihracı bakımından tespit ve çıkarımlarımız yer alacaktır. Tezimiz genel olarak Türkiye'nin finansal kurumlara, İDMK'yı, iç pazardaki ekonomik kalkınmayı hızlandırmak için sermaye piyasalarından fon sağlamak için kullanma önerisi de getirmektedir. Bu tez ile Türkiye'de finans kurumlarının MBS ihraçları için alternatif bir finansman kaynağı olarak dikkat çekilmesi de amaçlanmaktadır. Burada kamusal bir gelişme olarak ifade edilecek olursak, "Yeni Ekonomi Program", finansal derinliğin ve istikrarın sağlanması için Türkiye'deki menkul kıymetleştirmelerin (İDMK ihraçları dahildir) desteklenmesi tedbirini de içermektedir. The Turkish mortgage system, mortgage securitization, and the issuance of Mortgage-Backed Securities (MBS), collectively referred to as the "Mortgage Law," were initially regulated in 2007 by Law No. 5582, also known as the "Law on Various Amendments Regarding the Housing Finance System" (Housing Finance Law), commonly referred to as the "Mortgage Law" in practical application. In terms of secondary regulations, the issuance of MBS is governed by Article 58 of the Capital Markets Law No. 6362 (CML) and the Communiqué on Asset-Backed Securities and Mortgage-Backed Securities (ABS-MBS Communiqué). The aim and scope of this study involve a comprehensive examination of the mortgage system, which encompasses numerous legal regulations, concepts, institutions, and relationships. The focus is on providing concise assessments and evaluations, free from legal redundancies, based on the perspective of capital markets. The study conceptually presents the mortgage system in its true sense, addressing the essence and purpose of the system, particularly focusing on Mortgage-Backed Securities (MBS) as a capital market element, along with relevant findings, evaluations, and recommendations. In a narrow sense, the term "mortgage" refers to the mortgage lien and financing receivables secured by mortgages in Anglo-Saxon law. In the context of capital and financial markets, the mortgage system refers to the securitization of mortgage-backed receivables by issuing Mortgage-Backed Securities (MBS). The mortgage system, its securitization, and MBS issuance were initially implemented in the United States (US) legal framework. The raison d'être of the mortgage system lies in obtaining financing from capital markets through the issuance of MBS at minimal cost and in a reliable manner. MBS issuance involves transferring mortgage-backed financing receivables out of the balance sheet through a true sale mechanism within the mortgage system, facilitating their securitization. Therefore, MBS represents a security of a true sale-based, off-balance-sheet, and traditional nature. The thesis comprises five sections. The first section evaluates the concept of the mortgage system in technical terms, discussing its historical development, related regulations, and its nature as securitization. The second section delves into the operation of the mortgage system, the assets used, stages involved, and the system's unique terminology. The third section examines the institutions within the mortgage system, considering their specific concepts and requirements. The fourth section covers the objective of the system and the definition of MBS, its types, and similar securities. The fifth and final section consolidates our findings and recommendations regarding the reasons for MBS issuance and the challenges hindering it. In the conclusion, we highlight the potential of the mortgage system and its product, MBS, as a system capable of fostering rapid and sustainable development in Turkey when implemented in its true sense. The thesis suggests that financial institutions in Turkey consider MBS issuances as an alternative source of funding, aiming to accelerate economic development in the domestic market. Additionally, the study aligns with the "New Economic Program," which includes measures to support securitizations in Turkey, including MBS issuances, to ensure financial depth and stability.
Keywords: Capital market; Hypothèque; Menkul kıymetleştirme; Mortgage; Mortgage Backed Securities; Securtization; Sermaye Piyasası Hukuku; Sûretés; İpoteğe Dayalı Menkul Kıymetler

Milletlerarası özel hukukta iflâs - Dorken, Oğuz (Galatasaray Üniversitesi, 2024)
This study aims to provide a detailed and comprehensive legal analysis of international bankruptcy and related issues by drawing on comparative law and private international law. In this context, this thesis aims to determine the legal qualifications of the transactions that fall within the framework of international insolvency and to address the problems related to these issues in detail. This study consists of five chapters. The first chapter examines the specific aspects of insolvency in the fields of debt enforcement, procedural law, and substantive law. The main argument in this chapter is that bankruptcy law has its own normative scope. In this framework, bankruptcy law and enforcement law regulate areas that can be analytically distinguished from each other. The law of debt enforcement regulates all actions and procedures based on the state's sovereignty and power to use force. On the other hand, bankruptcy law can be characterized as a multi-layered and unique branch of substantive law that has features related to the law of obligations or commercial law, depending on the context. The first chapter begins with an etymology of the concept of insolvency across various languages. The Turkish word "iflâs" is highlighted, which comes from the Arabic word "fls" (fels), indicating a state of destitution and insolvency. In English, the term "bankruptcy" has historical origins that trace back to medieval Italy, where merchants who couldn't pay their debts had their trading benches physically broken, a practice referred to as "banca rotta." The main goal of this analysis is to emphasize that historically, insolvency has been perceived as a condition of incapacity and deficiency resulting in disgrace, even in the mildest scenarios. In terms of the severity of Roman law, penalties such as enslavement or death for bankrupt individuals illustrate how grave the offense of bankruptcy was considered. Furthermore, during the Middle Ages, those in financial distress were scorned by society. Meanwhile, with the modernization of legal systems, efforts have been made to alleviate the negative social perception of individuals who become insolvent. These efforts have led to changes in the law and the emergence of new terminologies. Over time, legal terminology across different countries has evolved. For example, in the US, the terms "debtor" and "insolvency" are now more commonly used in place of "bankrupt" and "bankruptcy" respectively, in the context of insolvency law. In line with these changes in terminology, reform efforts at both the comparative and international law levels aim to diminish the stigma attached to insolvent individuals and companies, striving to provide them with the opportunity for a fresh start within the economic order. Moving on, the first section distinguishes between the narrow and broad meanings of the concept of insolvency in comparative law and international instruments. Throughout this study, bankruptcy in its narrow sense refers specifically to procedures that involve the liquidation and distribution of a debtor's assets and/or the dissolution of their legal personality to satisfy creditors in accordance with applicable laws. In contrast, the broad sense of insolvency encompasses the debtor's objective inability to pay, the formal declaration of this predicament by a competent authority, body, or the debtor themselves, as well as all subsequent actions taken to settle claims and manage the debtor's assets. Within this expansive interpretation of insolvency, the study underscores the principle of collectivity, which is critical in administering bankruptcy procedures. Additionally, it conceptualizes bankruptcy as a wide-ranging framework, starting from liquidation in the narrowest scope and extending to include debt restructuring and non-judicial workout solutions. Furthermore, this study primarily considers insolvency law as substantive law. It supports the notion that while insolvency contains procedural elements, these are not its defining features. The focus here is on the processes associated with the initiation, execution, management, and conclusion of bankruptcy proceedings. The second chapter of the study is dedicated to the conceptual framework and theoretical perspectives of international insolvency. The term "international insolvency" refers to various situations in which a debtor may have a cross-border element—such as operating in more than one country, being domestic with creditors located abroad, being a foreign entity with domestic creditors, or having assets dispersed over multiple countries. In this section, the chapter elaborates on various theoretical approaches to the legal framework governing international insolvency. These approaches include territorialism, which is based on the principle of territoriality or locality; universalism, which advocates for consistent practices and standards in cross-border insolvencies; and the hybrid approach. Due to the practical difficulties encountered with universalism, mixed approaches have been developed, offering alternatives such as cooperative territoriality, multilateralism, contract theory, universal proceduralism, and modified universalism. The examination of these approaches, each presenting distinctive advantages and challenges, provides significant insights into the ongoing and potential resolutions for issues in international insolvency. Chapter Three outlines a general framework that defines the relationship between international insolvency and the law. In this chapter, the legal nature of international insolvency law is first explained, and a reminder is provided of the modern insolvency law approach introduced in the first chapter. Within this framework, the aim of insolvency law is to develop a collective procedural structure founded on the principles of justice that considers the interests of all parties involved. It seeks to maximize the value of the debtor's assets, minimize waste, ensure the rescue of viable businesses, and develop appropriate techniques for these purposes. The transnational aspect of bankruptcy introduces an additional layer of complexity to the existing definition and framework. Consequently, international insolvency law is evolving into a distinct system within private international law, specifically catering to transnational insolvency cases. This system often described as "sui generis" strives to fulfill the objectives of insolvency in scenarios that transcend national borders. The growing field of transnational insolvency anticipates the effective centralization of proceedings that are acknowledged and aided by foreign authorities. The goal is to maximize asset values and ensure business recovery while carefully considering the interests of all affected parties, regardless of their location. In international insolvency cases, it's important to balance the interests of creditors and debtors. Factors like nationality or foreign status, as well as the role of the state as an entity under international law, should be considered in this balance. In order to establish this balance, it is of great importance to explore harmonious and effective solutions by evaluating these interests in a holistic framework. Practices in international insolvency and comparative law have tended towards a perspective that aims to harmonize and coordinate different interests. In fact, this is the main concern of the modified universalism approach. From this perspective, the final section of the third chapter examines various legal frameworks or regimes for international insolvency. This includes a study of the ecosystem of Model Laws related to insolvency, with particular emphasis on the 1997 UNCITRAL Model Law, as well as the regulations in force within the European Union, the United States, and Latin American countries. The fourth chapter delves into international insolvency by addressing traditional concepts of international procedural law. It evaluates the criteria for international jurisdiction in insolvency proceedings, the recognition of foreign insolvency judgments, and the determination of applicable law. These topics are scrutinized using a comparative legal framework, drawing from the UNCITRAL Model Law, regulations in the U.S. and the EU, and various national laws, which the third chapter discusses. Techniques from comparative and private international law are employed to analyze these issues, which can be summarized as follows: Firstly, in the realm of international insolvency and private international law, a common challenge involves identifying the competent court for the proceedings. This issue is often resolved using the principle of the Center of Main Interests (COMI). COMI refers to the primary location of a company's or legal entity's operational activities in the context of insolvency or debt restructuring. It is typically associated with the site of the debtor's main administrative office, the place where significant operations are conducted, or the location where crucial commercial decisions are made. Additionally, the issue of forum shopping often arises in discussions of international jurisdiction and represents the second significant concern. In the context of international insolvency, 'forum shopping' is the practice where an internationally active company selects a jurisdiction that is perceived to offer the most favorable legal environment for its restructuring or insolvency processes. The company then takes steps to establish its case in the chosen jurisdiction in hopes of benefiting from its laws in the event of insolvency. The modified universalism approach argues for a legal framework where the primary insolvency proceedings are initiated in the debtor's Center of Main Interests (COMI), while ancillary proceedings may occur in other jurisdictions. Such a framework aims to curb the practice of forum shopping. Both the UNCITRAL Model Law and the EU Insolvency Regulation embrace this approach, thus promoting a more orderly and predictable system for handling cross-border insolvencies. The second issue addressed in Chapter Four is the recognition of the effect of foreign insolvency procedures. This section scrutinizes how foreign insolvency procedures interrelate with existing cross-border insolvency frameworks and evaluates the limitations imposed by such frameworks on the ability of these procedures to be recognized and enforced. Initially, the discussion focuses on how international frameworks handle the concept of a foreign procedure, beginning with standards set by the Model Law and then proceeding to the foreign insolvency procedures outlined in the EU Insolvency Regulation. The characteristics of the procedures in these two contexts are compared, and the techniques foreign courts apply to recognize, enforce, or reject them are examined. The third issue explored in the fourth chapter is the rules concerning the applicable law, with a focus on the principle of Lex fori concursus. This concept is rooted in the broader lex fori principle, a cornerstone of private international law. Under the Lex fori principle, a court typically applies its own domestic law—the law of the forum—to decide both procedural matters and, in the context of insolvency, the substantive rules governing the proceedings. This application of domestic law aligns with the state's sovereignty, as procedural law is deemed an extension of a nation's public law framework. According to the principle of Lex fori concursus, the law of the country where the insolvency proceedings are initiated typically governs the insolvency process and any related legal actions. This principle is formalized as a general rule in Article 7 of the EU Insolvency Regulation. Nevertheless, the regulation also delineates specific exceptions to this principle in subsequent provisions. These exceptions, as articulated in the EU Insolvency Regulation, include the following: (1) Third parties' rights in rem; (2) set-off; (3) reservation of title; (4) contracts relating to immoveable property; (5) payment systems and financial markets; (6) contracts of employment; (7) rights subject to registration; (8) detrimental acts of the debtor; (9) effects of insolvency proceedings on pending lawsuits or arbitral proceedings and 10) Protection of third-party purchasers. Furthermore, public policy is also recognized as an exception. It is a general principle that when foreign court proceedings are concerned, the Lex fori concursus - the law of the place where the insolvency proceedings are occurring -should be applied by the local court. The public policy exception, however, might place restrictions on this principle. This safeguard, which bars the application of foreign laws that are in conflict with the fundamental principles of the local law, enables the local court to give preference to its own laws over those of another country under specific, limited circumstances in bankruptcy cases. Nevertheless, it is important to underline that the concept of public policy does not grant countries unfettered discretion. UNCITRAL emphasizes that for the exception to the lex fori concursus to be invoked on public policy grounds, the contravention must be "manifestly" evident, leaving no room for doubt. Chapter 5 explores the specific challenges associated with international insolvency, such as the identification of the debtor's assets, the imposition of insolvency seizures, the prioritization of claims, and the annulment of detrimental transactions intended to disadvantage creditors. Furthermore, the chapter examines the procedures governing insolvency and the complexities surrounding the insolvency of multinational corporations. Among these problems, under the section titled 'Determination of the Debtor's Assets and Insolvency Seizure,' the text mentions the difficult task of monitoring and recovering assets internationally in the digital age, where goods can rapidly move across borders. Variations in practices among different countries contribute to inconsistencies in this area and exacerbate challenges in insolvency cases. International commercial activities and cross-border bankruptcies further complicate the process of tracing and recouping assets and can result in conflicts between laws. The absence of a universal legal framework, applicable across all countries, poses a significant impediment to protecting assets and maximizing their recovery in the course of insolvency proceedings. In this context, there is a pressing need to cultivate global cooperation and establish mechanisms that address critical issues such as the identification of assets, the temporary seizure of assets, and the prevention of unauthorized transfers. For instance, the use of 'freezing orders'—the authority to impose temporary restrictions on the transfer, sale, or disposal of assets under foreign jurisdictions—has proven effective in safeguarding assets. Within the European Union, Articles 19(1) and 20(1) of the EU Insolvency Regulation mandate that an EU-wide suspension of transactions automatically takes effect upon the initiation of substantive insolvency proceedings in any Member State. Another issue discussed in the fifth chapter concerns the annulment of transactions made with the intent to harm creditors, an issue commonly referred to as 'avoidance.' This term describes any actions that undermine the debtor's ability to fulfill its obligations, thus impairing the rights of creditors by devaluing the debtor's assets or rendering them unreachable for creditor claims. The UNCITRAL Model Law on Cross-Border Insolvency and the EU Insolvency Regulation both seek to offer various solutions to this problem. Nevertheless, avoidance laws can differ significantly from one country to another, where legal systems have disparate criteria for assessing the validity of such transactions. A transaction that is deemed fraudulent in one jurisdiction could be considered valid in another. The chapter also addresses "conflicts of priorities" which present analogous challenges. The matter of creditor priority in international insolvency law underscores the absence of standardized regulations and systems, consequently impeding cooperation among courts and complicating the adjudication process. Considerable variations exist in the interpretation of equitable treatment for domestic and foreign creditors during insolvency proceedings, as well as in how such equity should be guaranteed. These complexities span from determining the sequence of repayment to more granular concerns regarding the handling of various types of creditors and their respective claims. These difficulties obstruct efforts to establish a consistent and harmonized framework for international insolvency law. In international insolvency cases, the varying legal traditions, economic levels of different countries, and cultural norms that shape business and economic practices necessitate a flexible framework capable of accommodating all alternatives—judicial and extrajudicial—to manage insolvency effectively. The prevailing trend in cross border insolvency law, as reflected in internationally recognized instruments, aligns with the general evolution of insolvency and restructuring law. This trend entails examining the compatibility of evolved insolvency procedures, which offer solutions for early-stage financial distress, with the mechanisms for recognition, cooperation, and legal assistance provided by international frameworks. Moreover, the impact of these procedures' implementation within the context of such frameworks is thoroughly considered. Chapter 5 concludes with a discussion on the insolvencies of multinational corporations, which have significantly grown in complexity due to the global economic downturns experienced over the past three decades. These insolvencies have carved out a distinct and intricate niche within international insolvency law, necessitating detailed scrutiny. The collapse of such large, cross-border enterprises highlights some of the most challenging facets of insolvency cases and has a profound influence on the global economic landscape. As this area intersects with the broader issues explored earlier in the study, it stands out as a fertile ground for legal innovation and swift progression, drawing upon advancements in legal theory, comparative law practices, and international regulations. The ongoing efforts and developments in this sector are proving essential in tackling these multifaceted challenges day by day. In conclusion, this study provides a thorough examination of the foundations, distinguishing traits, and practical applications of international insolvency law, framed within comparative and private international law. Its principal aim is to enrich the legal and theoretical discourse on cross-border insolvency by meticulously investigating the multifaceted procedures of insolvency in their global context. The historical development of insolvency and its integration into modern legal systems are explored, recognizing the profound influence of international insolvency's complexities on various legal frameworks. With a particular focus on two salient issues, the study confronts challenging topics such as the recognition and interrelationship of insolvency proceedings, their alignment with collaborative mechanisms and judicial support, the expansive definition and scope of insolvency across jurisdictions, and the intricate insolvencies faced by multinational corporations.
Keywords: Insolvency; International bankruptcy; International law

Genişletilmiş toplu lisanslama - Erçal, Hi̇lal (Ankara Yıldırım Beyazıt Üniversitesi, 2024)
Teknolojik ilerlemenin bir sonucu olarak internet, telif hakkına konu fikri ürünlerin dağıtımının yapıldığı ana mecra haline gelmiştir. Dijital teknolojinin birçok yerde ve çok yönlü birçok kişi ya da kurum tarafından kullanılması, özellikle telif haklarına konu fikri ürünleri etkilemiştir. Avrupa Birliği (AB) ise Dijital Tek Pazar oluşturma stratejisi kapsamında düzenlemelerine 2019/790 sayılı Dijital Tek Pazarda Telif Hakları ve Bağlantılı Haklar Yönergesini eklemiştir. Söz konusu direktifin 8 ve 12. maddelerinde ise genişletilmiş toplu lisanslama (GTL) düzenlenmiştir. GTL özellikle kitlesel olarak dijital mecrada kullanımın yoğun olduğu müzik, işitsel-görsel, sinema vb. eserlerin teliften arındırılmış şekilde kullanılmasına olanak sağlayan bir sistemdir. Özellikle televizyon yayınlarında olduğu gibi bazı kullanımların çok miktarda eser veya telif unsuru içermesi nedeniyle, tüm hak sahipleri ile görüşülerek kullanım izinlerinin alınması dijitalleşen dünyada hem çok maliyetli hem de oldukça zahmetli ve hatta çoğu zaman imkânsız bir hal almaktadır. Fikri ürünler üzerinde hak sahibi olanların, telif haklarını kullanma yetkisini herhangi bir meslek birliğine ya da toplu hak takibi yapan bir organizasyona vermemesi, başka bir deyişle oranın bir üyesi olmaması halinde söz konusu kullanımlar için izin alınması hem kullanıcılar açısından oldukça külfetli, hem de hak sahiplerinin menfaatlerini koruma noktasında daha da büyük bir sorun teşkil etmektedir. Bunun yanında kültürel mirasın korunmasıyla yükümlü olan kurumlar açısından en önemli zorluklardan biri, telif hakkı sahiplerinin kimliklerinin belirlenmesi ve telif hakkı içeren eserlerin kullanılması için yetki ya da lisans alınması gibi telif hakkı temizliğine ilişkin süreçlerdir. Özellikle sınır ötesi online kullanımlar açısından düşünüldüğünde bu çok daha karmaşıktır. GTL düzenlemesi ile dijital çağda herhangi bir toplu hak yönetimi organizasyonuna üye olmayan eser ve bağlantılı hak sahipleri açısından da meslek birlikleri ile kullanıcılar arasında yapılan lisans sözleşmelerinin geçerli olmasını sağlayacak bir sistem öngörülmüştür. As a conclusion of technological progress, the Internet has named as the main channel where the intellectual products subject to copyright are distributed. The use of digital technology by many people or institutions in many places and in many ways has especially affected the products that are subject to copyright. On the other hand The European Union (EU), within the scope of the Digital Single Market creation strategy, has added the Digital Signal Market Directive EC 2019/790 to its regulations. Extended Collective Licensing (ECL) is regulated in 8th and 12th articles of the mentioned directive. ECL is a system that enables the copyright permisson obtained use of works such as music, audio-visual, cinema, etc., which are massively used in digital media. As some uses especially like television broadcasts include a large amount of copyright items or works, in the digitalized world, it becomes costly as well as tough and even imposibble obtaining authorisations from right-holders by negotiating with all of them. If the rightholders of the intellectual products don't give authorisation of the exercise of their rights to a collecting society in another words, ıf they are not member of this organisation, obtaining permission for such uses would be very hard and transaction costs would be very high for the users and creates a greater issue as for the protection of benefits of the right-holders. Besides that the largest copyright challenge for Cultural Heritage Instutitions is the process of identification of right holders of copyright and clearence of rights, i.e obtaining authorization of licences for use of in-copyright works. When it's considered for cross-border online uses, it is more complex. In the digital age with the regulation of ECL, a system has been predicted to ensure that the licence agreements made between collecting societies and users are valid for authors and related-right holders who are not members of any collective rights management organisations.
Keywords: Copyright; Extended Collective Licensing; Extended Effect; Genişletilmiş Etki; Genişletilmiş Toplu Lisanslama; Intellectual property; Telif Hakkı

Girişim şirketlerinin finansmanının hukuki çerçevesi - Günay, Yavuz Selim (Ankara Hacı Bayram Veli Üniversitesi, 2024)
Girişimcilik hem ülkemiz hem de dünya ekonomisi için, ekonomik gelişme sağlaması, istihdamı artırması gibi bir çok sebeple, son derece önemlidir. Girişimcilik ekosisteminde uygulanan finansman yöntemleri, sözleşmeler, hukuk kuralları gibi unsurlar dinamik ve esnek yapısı dolayısıyla geleneksel yöntem ve kurallardan ayrışmaktadır. Girişimcilerin banka kredisi gibi geleneksel finansman yöntemlerine erişememesi dolayısıyla kitle fonlaması, gölge pay, aile ve arkadaşlar, girişim sermayesi ve melek yatırımcı gibi yenilikçi finansman yöntemleri ortaya çıkmıştır. Bu finansman yöntemlerinden en yaygın ve yapısal olarak kullanılanı girişim sermayesidir. Girişim sermayesi, çeşitli fonlar ve şirketlerden toplanan kaynakların, büyüme potansiyeli gösteren ve gelecek vadeden girişim şirketlerine, pay karşılığı yatırım yapılmasını ifade etmektedir. Girişim şirketleri bakımından finansman haricinde de bir çok faydası bulunan girişim sermayesi, Türk hukukunda SPK tarafından GSYO ve GSYF yapıları altında düzenlenmiştir. Girişim sermayesi uygulamasında en çok sorun teşkil eden hususlardan biri ise girişimci ile yatırımcı ilişkileridir. Girişimci ile yatırımcı arasında hem yatırım öncesinde hem de yatırım sonrasında bilgi asimetrisinin ve menfaat farklılaşmasının söz konusu olması, girişimci ile yatırımcı arasında yönetilmesi zorunlu hale gelen bir menfaat çatışması yaratmaktadır. Bu menfaat çatışmasının olumsuz etkilerinin en aza indirilememesi ve yönetilememesi sadece girişim şirketi için değil ülke ekonomisi için de olumsuz sonuçlar doğuracaktır. Girişimci ile yatırımcı arasındaki bu menfaat çatışmasının pay devir sözleşmesi, pay sahipleri sözleşmesi, paya dönüştürülebilir borçlanma araçları gibi çeşitli sözleşmesel düzenlemelerle yönetilmesi mümkündür. Ayrıca, girişimci ile yatırımcının kendi aralarında gerçekleştirecekleri sözleşmesel kurumsal yönetim düzenlemeleri de girişimci ile yatırımcı arasındaki menfaat çatışmasının yönetilmesinde etkili olacaktır. Entrepreneurship is important for both our country and the world economy for many reasons such as providing economic development and increasing employment. Elements such as financing methods, contracts and legal rules applied in the entrepreneurship ecosystem differ from traditional methods and rules due to their dynamic and flexible structure. Since entrepreneurs cannot access traditional financing methods such as bank loans, innovative financing methods such as crowdfunding, phantom share, venture capital and angel investors have emerged. The most widely and structurally used of these financing methods is venture capital. Venture capital refers to the investment of resources collected from various funds and companies in return for shares in promising venture companies with growth potential. Venture capital, which has many benefits other than financing for venture companies, is regulated by the CMB under the structures of GSYO and GSYF in Turkish law. One of the most problematic issues in venture capital implementation is the relationship between the entrepreneur and the investor. The fact that there is information asymmetry and interest differentiation between the entrepreneur and the investor both before and after the investment creates a conflict of interest between the entrepreneur and the investor that must be managed. Failure to minimize and manage the negative effects of this conflict of interest will have negative consequences not only for the venture firm but also for the national economy. It is possible to manage this conflict of interest between the entrepreneur and the investor through various contractual arrangements such as share transfer agreements, shareholders' agreements, convertible debt instruments. In addition, contractual corporate governance arrangements between the entrepreneur and the investor will also be effective in managing the conflict of interest between the entrepreneur and the investor.

Bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta taraflar - Güngör, Tuba (Kırıkkale Üniversitesi, 2024)
Türk hukukunda, özellikle iş uyuşmazlıkları bakımından arabuluculuğun dava şartı olarak kabul edildiği tarihten bu yana, arabuluculuk kurumundan beklenen faydanın elde edilip edilmediği bir yana bırakılırsa öğreti ve uygulamada halen tartışıla gelen birçok konu bulunmaktadır. Bunlardan biri, çalışma konumuzu oluşturan bireysel iş uyuşmazlıkları bakımından dava şartı arabuluculukta işçi ve işveren tarafların doğru ve tam olarak teşkilinin sağlanmasıdır. Alternatif çözüm yollarından biri olan arabuluculuğun dava şartı olarak düzenlenmesi, arabuluculuk faaliyetini yargılamanın ön şartı ve ayrılmaz bir parçası haline getirmiştir. Bu bakımdan arabuluculuk sürecinin doğru işçi veya işveren tarafla yürütülmemesi yargılamayı doğrudan etkileyecektir. İş uyuşmazlıkları bakımından işçi sıfatının belirlenmesi özellikle işçi olup olmadığı konusunda tereddüt yaşanan çalışanlar açısından önemlidir. İşveren tarafının doğru belirlenmesi ise, arabuluculuk faaliyetinin yanlış veya eksik işverenle yürütülmesinin ardından, yargılama sürecinde bu durumun tespit edilmesi halinde işveren tarafında değişiklik yapılamaması bakımından önem arz etmektedir. Arabuluculuk dava şartı olarak düzenlendiğinden, yargılama sırasında tamamlanabilmesi olanaklı değildir. Sürecin bu şekilde işlemesi ise mahkemeye erişim hakkının önünde engel teşkil edebileceği gibi, gerek iş güvencesi gerekse işçinin alacağına kavuşma noktasında hak kaybına ve mağduriyetine yol açabilecektir. In Turkish law, especially since the adoption of mediation as a condition for litigation in terms of labour disputes, there are still many issues that are still debated in the doctrine and practice, let alone whether the expected benefit of the mediation institution has been achieved. One of these issues is to ensure that the employee and employer parties are accurately and fully constituted in the mediation as a condition for litigation in terms of individual labour disputes, which is the subject of our study. The regulation of mediation as a condition of litigation, which is one of the alternative remedies, has made the mediation activity a prerequisite and an integral part of the proceedings. In this respect, failure to conduct the mediation process with the right employee or employer party will directly affect the proceedings. In terms of labour disputes, the determination of the employee party is especially important for employees who are in doubt as to whether they are employees or not. The correct determination of the employer party is important in terms of not being able to make changes on the employer side if this situation is detected during the proceedings after the mediation is carried out with the wrong or incomplete employer. Since mediation is regulated as a condition of litigation, it is not possible to complete it during the proceedings. This process may constitute an obstacle to the right of access to the court, and may lead to loss of rights and victimisation in terms of both job security and the employee's receivables.
Keywords: Dava şartı arabuluculuk; Employee; Employer; Iş uyuşmazlığı; Işveren; Labour dispute; Mediation; İşçi

Anonim şirketlerde yönetim kurulu iç yönergesi - İlgün Çamli, Zehra (Kırıkkale Üniversitesi, 2024)
Anonim şirket organları, özel hukuktaki sözleşme özgürlüğünün bir sonucu olarak kendi yetki alanlarına giren konuları iç yönerge ile düzenleyebilirler. Anonim şirket yönetim kurulu da yetki alanına giren konularda iç yönerge çıkarmak suretiyle düzenleme yapabilir. Türk Ticaret Kanunu'nda yönetim kurulunun yönetim yetkisini devrettiği ve sınırlı yetkili ticari vekil ve diğer tacir yardımcıları atadığı durumlarda bu işlemleri bir iç yönerge çıkararak gerçekleştirmesi zorunlu tutulmuştur. Bununla birlikte anonim şirket yönetim kurulu iç yönergesinde iç yönerge çıkarma zorunluluğu doğuran bu iki durum dışında yetki alanına giren diğer birçok konuyu düzenleyebilir. Bu kapsamda belirli durumlarda çıkarılması zorunlu olan bu iç yönergelerin zorunlu içeriğinin dışında, iç yönergede, yönetim kurulunun görevleri, çalışma usulü, yönetim kurulu üyelerinin ve yönetim yetkisinin devredildiği kişilerin hak ve yükümlülükleri gibi birçok husus yer alabilir. Bu düzenlemelerin sınırını da ilk başta Türk Ticaret Kanunu ve diğer kanunların emredici hükümleri oluşturur. Yönetim kurulunun Türk Ticaret Kanunu'nda çizilen yetki sınırları da bu çerçevede yönetim kurulu iç yönergesinin azami içeriğini belirler. Çalışmamızın ilk bölümünde anonim şirketlerde iç yönerge terimi açıklanmaya çalışılmış, ardından yönetim kurulu iç yönergesi terimi yetki devrinden ve sınırlı yetkili ticari vekil ve diğer tacir yardımcısı atanmasından bağımsız şekilde yönetim kurulunun çıkardığı düzenleyici bir metin olarak ele alınmıştır. Çalışmamızın ikinci bölümünde anonim şirket yönetim kurulu iç yönergesinin içerebileceği düzenlemeler ve bunların iç yönergede ne şekilde düzenlenebileceği incelenmiştir. Çalışmamızın son bölümünde ise yönetim kurulunun kendi çıkardığı iç yönergeyi ihlal etmesinin sonuçları gibi iç yönergeye ilişkin diğer meseleler ele alınmıştır. The organs of a joint stock company, as a result of the freedom of contract in private law, can regulate matters within their jurisdiction through internal directives. The board of directors of a joint stock company can also regulate matters within its jurisdiction by issuing internal directives. According to the Turkish Commercial Code, it is mandatory for the board of directors to execute transactions, such as delegating management authority and appointing limited authority commercial representatives and other merchant assistants, through the issuance of an internal directive. However, beyond these two instances where issuing an internal directive is mandatory, the board of directors can regulate many other matters within its jurisdiction through an internal directive. In this context, aside from the mandatory content in specific situations, an internal directive can include many issues such as the duties of the board of directors, working procedures, and the rights and obligations of board members and those to whom management authority has been delegated. The boundaries of these regulations are primarily determined by the mandatory provisions of the Turkish Commercial Code and other laws. The authority limits outlined in the Turkish Commercial Code also define the maximum content of the board's internal directive. In the first part of our study, the term "internal directive" in joint stock companies is explained. Subsequently, the term "internal directive of the board of directors" is examined as a regulatory document issued by the board, independent of authority delegation and the appointment of limited authority commercial representatives and other merchant assistants. In the second part of our study, the potential regulations that could be included in the internal directive of the board of directors of a joint stock company and how these can be arranged within the internal directive are analyzed. In the final part of our study, other issues related to internal directives, such as the consequences of the board of directors violating its own internal directive, are discussed.
Keywords: Authority of the Board of Directors; Board of directors; Delegation of Management; Droit des sociétés commerciales; Internal Directive; Limited Authority Commercial Representative; Sınırlı Yetkili Ticari Vekil; Working Procedures of the Board of Directors; Yönetim Kurulu; Yönetim Kurulunun Yetki Alanı; Yönetim Kurulunun Çalışma Usulü; Yönetimin Devri; İç Yönerge

Pazarlamacılık sözleşmesi - Kaya, Servecan (Üniversitesi Ankara, 2024)
Ticari hayatta duyulan ihtiyaç sonucu ortaya çıkmış sözleşmelerden birisi olan pazarlamacılık sözleşmesi, sıklıkla uygulanan sözleşmelerden olması ve hizmet sözleşmesinin özel bir türü olmasına karşın farklılaştığı hususların önemi sebebiyle kanun koyucu tarafından Türk Borçlar Kanunu içerisinde hizmet sözleşmesinden ayrı olarak düzenlenmiştir. Kanuni bir tanımının da bulunmasının etkisiyle tarafları ve unsurları rahatlıkla belirlenebilir mahiyettedir. Pazarlamacılık sözleşmesi unsurları; bağımlılık, süreklilik, iş yeri dışı faaliyet alanı ve ücret olan, rızai ve tam iki tarafa borç yükleyen bir isimli sözleşmedir. Pazarlamacılık sözleşmesinin taraflarından sözleşmeye de ismini vermiş olan pazarlamacı aynı zamanda bağımlı bir tacir yardımcısıdır. Bu bağlamda pazarlamacılık sözleşmesinin benzer olduğu birçok sözleşme bulunduğu gibi pazarlamacının da benzer olduğu birçok tacir yardımcısı bulunmaktadır, ancak her ikisinin de özüne inildiğinde benzer noktalardan ziyade diğerlerinden farklı karakteristik özellikleri bulunduğu rahatlıkla anlaşılacaktır. Tarafların hakları ve yükümlülükleri genel itibariyle pazarlamacılık sözleşmesinde birbirlerine karşılık gelmektedir, sözleşme böylece taraflar arasında kurulur, sürer ve sona erer. Pazarlamacılık sözleşmesinin sona ermesinde hizmet sözleşmesine ilişkin sona erme hallerinin söz konusu olduğu gibi kendine has sona erme halleri de söz konusudur. Her sözleşmede olduğu gibi sona erme halinde bunun da meydana getireceği sonuçlar taraflar özelinde kendisini gösterir. Ticaret hukuku ve borçlar hukuku özellikleri gösteren bir sözleşme olan pazarlamacılık sözleşmesi, özellikle belirli sektörlerde sıklıkla uygulanması, uyuşmazlıklara konu olması haricinde pazarlamacının sözleşmenin diğer tarafı olan işverene bağlı olarak faaliyet göstermesi sebebiyle de iş hukuku özelliği de gösteren bir sözleşmedir. Traveling salesman, which is one of the contracts that emerged as a result of a need in commercial life, has been arranged separately from the contract of service in the Turkish Code of Obligations, due to the importance of the matters that differentiate it, although it is one of the most frequently applied contracts and it is a special type of contract of service. With the effect of having a legal definition, its parties and facts can be easily identified. Traveling salesman is a consensual and bilateral contract with its elements which are dependency, continuity, non-operational field of business and fee. Traveling salesman as one of the parties of traveling salesman contract, who has given its name to the contract, is also a dependent tradesman assistant. In this context, as there are several contracts that traveling salesman is similar to, there are several tradesman assistants that traveling salesman is similar to, but when the essence of both is examined, it will be easily understood that they have various characteristics from the others. The rights and obligations of the parties generally correspond to each other in traveling salesman, so the contract is concluded, continued and terminated between the parties. In the termination of traveling salesman, there are specific termination cases as well as the termination cases related to contract of service. As with every contract, the consequences of termination in the event of termination will manifest themselves in particular to the parties. Traveling salesman is a contract that has the characteristics of commercial law and law of obligations, and also is a contract that has labor law characteristics, especially since it is frequently applied in certain sectors, is the subject of disputes, and because the traveling salesman operates under the employer, the other party of the contract.
Keywords: Code of Obligations; Commercial traveller; Contract; Traveling salesman

Hava Kargo Taşımacılığının Ülke Refahına Etkisi: OECD Ülke Analizi - Kelek, Bura Sabiha (İstanbul Ticaret Üniversitesi, 2024)
Bu çalışmanın amacı, ülkelerin rekabet güçleri açısından oldukça önemli olan lojistik performansları ile insani gelişmişlik düzeylerinin hava kargo ve küresel rekabet faktörlerinin nasıl ilişkili olduğunu ortaya koymaktır. Bunu ifade etmek için, 29 OECD (Ekonomik İş birliği ve Gelişme Teşkilatı) ülkesinin lojistik performanslarını hava taşımacılığının kargo göstergeleri ile ilişkilendirip ve sonuçları bahsi geçen ülkelerin insani gelişmişlik düzeyine etkisi açısından yorumlamaktır. Verilerin tüm ülkeler için eşit olmasına dikkat edilmiştir. Kullanılan puanlamaların zaman serisi 2010, 2012, 2014, 2016, 2018 yıllarını kapsamaktadır. Sonuçların analizi, kullanılan verilerin SPSS ile ortaya çıkarılarak oluşan yapısal eşitlik modellemesinin (YEM) üzerinden, çalışan ve çalışmayan regresyonların belirlenip ortaya hava taşımacılığı açısından etki eden verilerin bulgusuna erişmek ve yapılan analiz ile bu verilerin göstergesi ışığında hava lojistiği performansıyla ilişkili olup olmadığını göstermeye çalışılmaktadır. Çalışmada özellikle elde edilmek istenen bulgular bahsi geçen ülkelerin gayri safi milli hasıla ile kişi başına düşen milli gelirin hava taşımacılığının doğrudan veya dolaylı yoldan hem küresel rekabete olan etkisi hem de GSYİH’ye olan katkısıdır. Çalışma da lojistik kavramı ile birlikte ülkelerin ticaretleri ele alınarak dünya üzerindeki ticari üstünlüklerine değinilmiştir. Literatür araştırması, insani açıdan yetkin ülkelerin lojistik endüstrisine bakış açıları değerlendirilmiş ve lojistik alanındaki yükselişleri ile bağlantılı kalkınmasına işaret edilmiştir. Kullanılan veriler güvenilirlik açısından Dünya Bankası’ndan alınmış ve kullanılan endeksler çalışmanın kapsamında bulunan bütün parametreler ile analiz edilmiştir. Bunun sonucunda kurulan model de hava kargo taşımacılığının dolaylı olarak küresel rekabete etkisi ile Gayri Safi Yurtiçi Hasıla’ya ve aynı zamanda insani rekabet performanslarının lojistik performans endeksi ile anlamlı bir ilişki kurduğu ortaya çıkmıştır.
Keywords: Hava Kargo; Küresel Rekabet; Lojistik Performans; Lojistik Yönetimi; Milli Gelir

Vergi ceza hukukunda muhasebe hileleri ve hukuki sonuçları - Parlak, Mehmet Ali (İstanbul Üniversitesi, 2024)
Bu çalışma, Vergi Usul Kanunu'nun 359. maddesinin (a) fıkrasının birinci bendinde düzenlenen "hesap ve muhasebe hileleri yapmak" hükmünün, suç ve cezada kanunilik ilkesini karşılayıp karşılamadığı temelinde suçun kapsamı, özellikleri, unsurları ve sonuçlarının doktrin, içtihat ve mevzuat hükümleri ışığında incelenmesini konu edinmektedir. Muhasebe hilesi geniş anlamda, işletmelerde meydana gelen değer hareketlerinin belgelendirilmesinden faaliyet sonuçlarının raporlanmasına kadar olan süreçte, işlemlerin gerçeği yansıtmayacak şekilde değiştirilmesidir. Bu itibarla muhasebe hilesi muhasebe, denetim, ticaret hukuku gibi farklı disiplinlerin inceleme alanlarına giren genel bir kavramdır. Bunun yanında vergi kaçakçılık fiili olarak vergi hukuku doktrininde de önemli bir yer tutan tartışma konusudur. Vergi hukukundaki tartışmalar, hükümdeki muhasebe hilesi kavramının tanımsız, torba suç, kaçakçılık suçlarının en geneli ve işlevsiz bir suç olup olmadığına yöneliktir. Bu tartışmaların kaynağı kanun koyucunun maddede suçun kurucu unsurlarına yer vermemesi ve herhangi bir soyut tipe dair belirleme yapmamasıdır. Bu bakımdan çalışmada farklı disiplinler bakımından muhasebe hilesinin kapsamı, yöntemleri, sebep ve sonuçları karşılaştırmalı olarak ele alınmış; tümden gelim yöntemiyle vergi hukukundaki muhasebe hilesi suçunun içeriği tespit edilmeye çalışılmıştır. Çalışmada ulaşılan sonuç; "hesap ve muhasebe hileleri yapmak" hükmünün suçu tanımlamak bakımından "belirlilik" ilkesini karşılamadığıdır. Dolayısıyla adli ve idari mercilerin subjektif değerlendirmelerinin önüne geçilmesi, hukuki kesinlik ve eşitliğin temini, hukuki güvencenin sağlanabilmesi ve normun işlerlik kazanabilmesi için bir düzenlemeye ihtiyaç duyulmaktadır. This study examines the scope, characteristics, elements and consequences of the crime in the light of doctrine, jurisprudence and legislation on the basis of whether the provision of "committing accounting and accounting fraud" regulated in the first paragraph of paragraph (a) of Article 359 of the Tax Procedure Law meets the principle of legality in crime and punishment. It is about to be examined. Accounting fraud, in broad terms, is changing transactions in a way that does not reflect reality, from the documentation of value movements in businesses to the reporting of activity results. In this respect, accounting fraud is a general concept that falls into the fields of investigation of different disciplines such as accounting, auditing and commercial law. Discussions in tax law are about whether the concept of accounting fraud in the provision is undefined, an omnibus crime, the most general of smuggling crimes, and whether it is a dysfunctional crime. The source of these discussions is that the legislator does not include the constitutive elements of the crime in the article and does not specify any abstract type. In this regard, the scope, methods, causes and consequences of accounting fraud in terms of different disciplines were discussed comparatively in the study; The content of the crime of accounting fraud in tax law has been tried to be determined by deductive method. The result reached in the study; The provision of "committing account and accounting fraud" does not meet the principle of "specificity" in terms of defining the crime. Therefore, a regulation is needed to prevent subjective evaluations of judicial and administrative authorities, to ensure legal certainty and equality, to provide legal assurance and to make the norm functional.
Keywords: Accounting; Finance; Fraud; Fraude fiscale; Maliye; Tax fraud

Arabuluculuk faaliyetinin anlaşma ile sona ermesi - Terzi̇ Kahraman, Si̇bel (Kadir Has Üniversitesi, 2024)
Arabuluculuk kurumundan beklenen avantajların ortaya çıkabilmesi arabuluculuk faaliyeti sonunda anlaşmaya varılması ile mümkündür. Mevzuatta sürekli değişiklikler meydana gelmekte ve kurumun kapsamına aldığı uyuşmazlıklar hızla genişletmektedir. Uygulamanın yerleşmesi ve zaman zaman doktrinde görüş ayrılıkları yaşanması kaçınılmazdır. Mevzuatta daha detaylı ya da değiştirilerek düzenlenmesine ihtiyaç duyulan alanlar bulunmaktadır. Tez, mevzuatta yapılan son düzenlemeleri de kapsayarak anlaşmayı tüm yönleriyle ele almayı ve kurumun daha iyi anlaşılmasına hizmet etmeyi amaçlamaktadır. Yapılan bu çalışmanın ilk bölümde arabuluculuğun kurumsal çerçevesi ortaya konulmuştur. Bu bölümde amaç arabuluculuk kurumunu ve arabuluculuk faaliyetinin işleyişini anlatabilmektir. Bu amaçla arabuluculuğun kapsamı, türleri, arabuluculuğun karşılaştırmalı hukukta ve Türk hukukunda gelişimi, yargı ve tahkimden farkı, med-arb uygulaması anlatılmıştır. İkinci bölümde sona erme halleri tek tek ele alınmış, sona erme hallerinin mevzuatta dağınık halde düzenlendiği hususuna dikkat çekilmiş ve başkaca sona erme halleri de dikkate alınarak tek bir madde halinde düzenlenebilmesi hususu önerilmiştir. Arabulucunun, faaliyeti sona erdirme yönünde inisiyatif almasının sona erme hali olarak düzenlenmesi yönünde de öneri getirilmiştir. Üçüncü bölümde anlaşmanın terminoloji sorununa ve benzer kavramlardan farkına değinilmiştir. Arabuluculuk faaliyeti sonunda varılan anlaşmanın esaslı unsurları tespit edilmiştir. Bu kapsamda, sözleşme serbestisi, şarta bağlı edim düzenlenip düzenlenemeyeceği gibi önemli hususlara yer verilmiştir. Anlaşmanın nasıl düzenleneceğine ilişkin öneride bulunulmuştur. Anlaşmanın hukuki niteliği, anlaşılan hususlara karşı dava açılamayacağı, anlaşmanın hukuka uygun düzenlenmediği takdirde karşılaşılabilecek sonuçlar anlatılmış ve anlaşmanın arabuluculuğa elverişli olmamasına rağmen düzenlenmesi, dava şartı kapsamına girmeyen bir hususta faaliyetin yürütülmesi ve anlaşmaya varılması, yanlış dava türünden yapılan başvuru sonucu anlaşmaya varılması, arabulucunun uzmanlık alanına girmeyen bir konuyla ilgili anlaşma sürecini tamamlaması, hukuka uygun arabuluculuk faaliyeti yürütülmemesi sonucunda anlaşmaya varılması, arabulucunun arabuluculuktan çekilmesi gerekirken yine de anlaşma yapması gibi anlaşmadan kaynaklı sorunlara yer verilmiştir. Dördüncü bölümde anlaşmanın yerine getirilmemesi durumunda icra edilebilirlik şerhi alınması hususu, mahkemeye başvuru, yargılama usulü, mahkemenin incelemesi, şarta bağlı olarak yapılan anlaşmaya şerh verilmesi, icra edilebilirlik şerhi alınan anlaşmanın icrası, anlaşmayla ilamlı ve ilamsız takip yapılması gibi önemli hususlar ele alınmıştır. Son olarak, arabuluculuk sonucunda elde edilen uluslararası ticari anlaşmaların icra edilmesini kolaylaştırması amacıyla hukukumuzda da kabul edilen Singapur Konvansiyonu incelenmiştir. The expected advantages of the mediation institution can be realized through reaching an agreement at the end of the mediation process. There are continuous changes in the legislation, rapidly expanding the scope of disputes covered by the institution. The thesis aims to comprehensively examine the agreement reached at the end of the mediation process, including recent legislative amendments, to better understand the institution and its operations. The first part of this study outlines the institutional framework of mediation, explaining its scope, types, development in comparative law and Turkish law, differences from judiciary and arbitration, and the practice of med-arb. The second part discusses the various termination conditions, highlighting the scattered nature of these conditions in legislation and proposing their consolidation into a single provision. It also suggests granting mediators the initiative to terminate the process as a termination condition. In the third part, attention is given to the terminology issues and distinctions from similar concepts regarding the agreement reached through mediation. The essential elements of such agreements are identified, covering issues like contractual freedom and the regulation of conditional obligations. Recommendations are made on how agreements should be drafted. The legal nature of the agreement, restrictions on litigation concerning agreed-upon matters, consequences of improperly drafted agreements, and issues arising from inappropriate mediation activities are discussed. The fourth part addresses the issue of obtaining enforceability endorsements for agreements not fulfilled, court applications, trial procedures, court reviews, endorsement of conditional agreements, enforcement of endorsed agreements, and procedures for enforcement with and without judgments. Finally, the study explores the Singapore Convention, adopted in our legal system to facilitate the enforcement of international commercial agreements resulting from mediation.
Keywords: ADR; Agreement termination; Alternative dispute resolution; Anlaşmazlık; Arabuluculuk; Executability Annotation; Kanunlar 6325 sayılı; Laws 6325 numbered; Mandatory mediation; Mediation; Mediator; Médiation; Singapore Convention; Zorunlu arabuluculuk

Sermaye şirketlerinde zorunlu arabuluculuk - Ulusan, Banu (Galatasaray Üniversitesi, 2024)
Çalışma 06.12.2018 tarihinde 7155 sayılı Kanun ile Türk Ticaret Kanunu'na eklenen TTK m. 5A hükmüyle getirilmiş zorunlu arabuluculuğun, sermaye şirketleri çerçevesinde incelenmesini konu almaktadır. TTK m. 5A hükmüyle önce, ticari davalardan, konusu bir miktar paranın ödenmesi olan, alacak ve tazminat davalarının zorunlu arabuluculuğa tabi olduğu düzenlenmiştir. Daha sonra, 28.02.2023 tarihli ve 7445 sayılı Kanun ile yine ticari dava olmaları kaydıyla, menfi tespit, itirazın iptâlî ve istirdat davalarını da zorunlu arabuluculuk kapsamına almıştır. TTK lafzıyla dava şartı arabuluculuk olarak da nitelendirilen zorunlu arabuluculuk kavramı, Türk hukuku bakımından yeni bir kavram sayılabilir. İlk olarak 2017 yılında 7036 sayılı Kanun ile iş uyuşmazlıkları için düzenlenen zorunlu arabuluculuk kavramı, daha sonra ticari uyuşmazlıklar ve tüketici uyuşmazlıkları için de düzenlenmiştir ve Türk hukukunda zorunlu arabuluculuğun uygulama alanı git gide genişleme eğilimi göstermektedir. Bu sebeple, doktrinde pek çok eleştiriye de uğrayan zorunlu arabuluculuk kavramının, özellikle sermaye şirketleri bağlamında incelenmesi amaçlanmıştır. Her ne kadar Türk hukukunda yeni bir kavram olsa da, karşılaştırmalı hukukta zorunlu arabuluculuk uzun zamandan beri uygulanan ve tartışilânbir konu olagelmiştir. Karşılaştırmalı hukuk bağlamında bir inceleme yapıldığında öncelikle, özellikle zorunlu arabuluculuğun menşei sayılabilecek Amerikan hukukunda, konu özellikle doktrinde farklı açılardan ele alınmıştır. Çalışmanın birinci bölümünde bu çerçevede bir inceleme yapılmış, zorunlu arabuluculuğun tabi olması gereken kıstaslar ortaya konulmaya çalışılmıştır. Bu kıstaslar, çalışmanın ilerleyen bölümlerinde yapılacak değerlendirmeler için de önem taşımaktadır. Bunun yanı sıra zorunlu arabuluculuğun türleri ve zorunlu arabuluculuğa aykırı davranışlara bağlanan yaptırımlar üzerinde de durulmuştur. Zorunlu arabuluculuğun ve benzeri uygulamaların farklı hukuk sistemlerinde ne şekilde yer aldığı değerlendirilmiştir. Bu değerlendirmeler kapsamında Alman hukuku bakımından ZPO §278 ile EGZPO §15a incelenmiştir. İsviçre hukuku bakımından ise ZPO §197 vd. hükümleri incelenmiştir. Her iki hukuk sistemi de zorunlu arabuluculuğu düzenlememiş, bunun yerine medeni usûl kanunlarında davanın görüleceği mahkemeler nezdinde uyuşmazlık çözüm sürecini düzenlemiştir. İtalya ve Fransa'da ise zorunlu arabuluculuk uygulamaları mevcut ise de bu, Türk hukukunun aksine, son derece sınırlı bir şekilde gerçekleşmiştir. Zorunlu arabuluculuğun kaynağı olan Amerikan hukukunda ise arabuluculuk, zorunlu tutulan tek uyuşmazlık çözüm yöntemi olmamıştır. Ayrıca zorunluluk hususu kanunla değil, genellikle her bir dava için mahkemenin yönlendirmesiyle sağlanmaktadır. Tüm bu ülkelerin ortak özelliği ise ticari uyuşmazlıkları zorunlu arabuluculuğa ya hiç tabi tutmamaları ya da çok dar bir kapsamda tabi tutmalarıdır. Arabuluculuk her ne kadar bir yargılama faaliyeti olmasa da zorunlu arabuluculuk dava öncesinde yer alan bir aşama olduğundan, kanaatimizce medeni usûl hukukuna hâkim olan ilkeler bakımından da incelenmelidir. Bu kapsamda zorunlu arabuluculuğun öncelikle adil yargılanma ilkesi ve mahkemeye erişim hakkı kapsamında tartışmalara sebep olduğu görülmektedir. Bunun yanı sıra usûl ekonomisi ilkesi, aleniyet ilkesi, tasarruf ilkesi ve dürüst davranma yükümlülüğü bakımından da değerlendirmelere yer verilmiştir. Aleniyet ilkesi bağlamında arabuluculuğa hâkim olan ilkelerden gizlilik ilkesinin ticari uyuşmazlıklar bakımından bir avantaj oluşturduğu söylenebilir. Tasarruf ilkesinde yapılandeğerlendirme maddî hukuk ve usûl hukuku çerçevelerinde yapılmıştır. Ayrıca zorunlu arabuluculuğun menşei Amerikan hukukunda hâkimin ve avukatların rolleri de dikkate alınarak, zorunlu arabuluculuğun Türk hukukundaki hâkimin yargılamayı sevk ve idaresi ilkesiyle tamamen bağdaşmadığı sonucuna varılmıştır. Dürüstlük ilkesi bakımından yine maddî hukukla da bağlantı kurularak bir değerlendirme yapılmış, zorunlu arabuluculuk süreci sonunda varılacak anlaşmanın dürüstlük kuralına uygun yapılması için yeterli mekanizmaların bulunmadığı kanaatine varılmıştır. Bunun dışında HUAK m. 18A/11 hükmü uyarınca zorunlu arabuluculuk sürecinin ilk toplantısına mazeretsiz katılmayan tarafın her durumda yargılama giderlerinin tümünden sorumlu olması ve lehine vekalet ücretine hükmedilememesinin orantısız bir yaptırım olduğu, ayrıca bu sebeple hiçbir durumda yargılama giderlerinden sorumlu olmayacağını bilen tarafın, açılacak dava sürecinde davayı uzatacak veya yanlış yönlendirecek ve dürüstlük kuralına uymayacak her tür davranışı yapabileceği kanaatine varılmıştır. Çalışmanın ikinci bölümü TTK m. 5A hükmünün uygulama koşullarına yoğunlaşmaktadır. Bu kapsamda, ticari davalar bakımından karşılaştırmalı bir değerlendirme yapılmak istenmiştir. Türk hukukunda TTK m. 4 hükmüyle ayrıca düzenlenen ticari davalar, diğer hukuk sistemlerinde ticaret mahkemeleriyle ilişkili olarak düzenlenmiştir. Bu değerlendirmede dikkat çeken husus, davaların ucuz, hızlı ve etkin bir şekilde sonuçlandırılmasının amaçlandığı diğer hukuk sistemlerinde hukukçu olmayan hâkimlerin de görev yaptığıdır. Türk doktrininde ise böyle bir uygulamanın uygun olmayacağı haklı olarak belirtilmiş, bu bağlamda zorunlu arabuluculuk uygulamasının daha uygun olduğu kanaatine varılmıştır. Ticari davalarda dava şartını düzenleyen TTK m. 5A hem medeni usûl hukuku hem de ticaret hukuku bakımından incelenmiştir. Medeni usûl hukukun bakımından yapılanincelemede dava şartı kavramı ve hükmün dava türlerine göre gösterdiği özellikler incelenmiştir. Ticaret hukuku bakımından ise, arabuluculuk süreci sonucunda varılacak anlaşmanın bir maddî hukuk sözleşmesi oluşundan da yola çıkarak basiretli tacir kavramı incelenmiştir. Ayrıca zorunlu arabuluculuğun HUAK m. 5 hükmü ve gizlilik ilkesi nedeniyle göstereceği özellikler nedeniyle, ticari sırların korunması bağlamında da bir değerlendirme yapılmıştır. Çalışmanın üçüncü ve son kısmı sermaye şirketlerinde zorunlu arabuluculuğun incelenmesine ayrılmıştır. Bunun için öncelikle Alman hukukunda pay sahipleri davaları olarak adlandırilândavalar hakkında değerlendirme yapılmaya çalışılmıştır. Bu değerlendirmeyle adi şirketlerden farklı olarak pay sahipleri davalarının genel olarak ortağa değil şirket tüzel kişiliğine yöneltilmesi gerektiği, bunun yanı sıra pay sahiplerinin şirketin menfaatleri için dava haklarını kullanabildiği görülmüştür. Bu değerlendirmenin, sermaye şirketleri uyuşmazlıklarında zorunlu arabuluculuk sürecinde başvuru yapacak taraflar ve anlaşmanın etkileyeceği kişilerin tespitinde yararlı olduğu kanaatindeyiz. Bu değerlendirmenin ardından TTK m. 5A kapsamına girebilecek sermaye şirketi uyuşmazlıkları tespit edilerek, her biri için zorunlu arabuluculuğun göstereceği özelliklerin belirlenmesine çalışılmıştır. Bu belirleme yapılırken her bir uyuşmazlık konusu hakkında genel bir çerçeve sunulmuş, açılabilecek davalar hakkında bilgi verilmiş ve bu bilgiler ışığında zorunlu arabuluculuğun uygulama koşulları ile doğurabileceği sakıncalar üzerinde durulmuştur. Son olarak, yapılantüm değerlendirmeler ışığında sermaye şirketlerinde zorunlu arabuluculukla ilgili de lege ferenda görüşümüze yer verilmiştir. Bu kapsamda sermaye şirketleri uyuşmazlıklarının, dava konularının şirketler hukuku kısıtlarına ve emredici kurallara tabi olması sebebiyle, zorunlu arabuluculuğa her zaman uyumlu olmayabileceği sonucuna varılmıştır. Üstelik, bazı arabuluculuk türlerinde yapılması elzem hukuki denetimin ve arabulucunun bu denetimi yapamayacak olmasının yaratacağı sakıncalara da değinilmiştir. Bunun sonucunda İsviçre ve Almanya örneklerinde olduğu gibi mahkeme bağlantılı uyuşmazlık çözümlerinin düzenlenmesinin daha uygun olduğu kanaatine varılmıştır. İflas bakımından bir değerlendirme yapıldığında ise, İİK m. 226 hükmü nedeniyle doğabilecek sorunlara dikkat çekilmiş, bu bağlamda zorunlu arabuluculuğa başvuru kapsamında düzenleme yapılması önerilmiştir. Son olarak zorunlu arabuluculuk ile varılmak istenen amaçlar da dikkate alındığında, bu amaçlara ulaşmak için taraflara arabuluculuk dışında uyuşmazlık çözüm yollarına başvurabilmelerine imkân verilmesi gerektiği kanaatine varılmıştır. Bu şekilde hem çabuk ve ucuz bir şekilde uyuşmazlıkların çözümü amacına ulaşabilecek, hem de tarafların ihtiyaçlarına daha uygun bir yöntem seçmelerine imkân tanınacaktır. […] This study focuses on application of Turkish Commercial Code Art. 5A, which is amended with Code Nr. 7155 in 2018, to equity companies. TCC Art. 5A regulated mandatory mediation for commercial cases with monetary claims at the beginning. However, through amendment with Code Nr. 7445 in 2023, negative declaratory actions, actions for annulment of objections and actions for restitution were taken into scope of this regulation. Mandatory mediation, which can also be named mediation as cause of action according to TCC m. 5A, can be deemed as a new context in Turkish law. Regulated for the first time for some labour law conflicts with Code Nr. 7036 in 2017, mandatory mediation is regulated also for commercial conflicts as well as consumer law conflicts. Thus, it can be observed that scope of mandatory mediation in Turkish law has a tendency to spread within time. Therefore, as a concept subject to various critics, mandatory mediation is to be evaluated in context of equity companies within this study. Although mandatory mediation is considered to be a relatively new concept in Turkish law, in frame of comparative law, it has a long history of application and has been subject to critics for a long time. It is observed that in comparative law, especially in American law, which can be considered as the source, mandatory mediation has been taken into consideration with many aspects. The first chapter of this study conducts an evaluation within this frame and aims to set the criterias for a better application of mandatory mediation. These criterias are important for evaluation in following chapters of this study. In addition, the variations of mandatory mediations and sanctions applied to the acts contrary to mandatory mediations are observed. Mandatory mediation and similar applications in different law systems are also examined. Within light of this examination, ZPO §278 and EGZPO §15a in German law is taken into consideration, as well as ZPO §197 ff. in Swiss law. Both systems do not regulate mandatory mediation and instead, regulated dispute resolution process within their Civil Procedure Codes. Although mandatory mediation is regulated in Itâlîan and French law systems, these regulations have strictly limited scope. American law, the origin of mandatory mediation, applies other means of dispute resolution as well. Moreover, mandatory mediation in American law is not regulated by a code; it is court oriented in general. The common point of these countries is that none of them applies mandatory mediation within a wide scope on commercial disputes. Although mediation cannot be considered as an act of judication, since mandatory mediation is a step before courts, it should be evaluated with regard of principals of civil procedure law. In this context, it is observed that mandatory mediation gave reason to many arguments related to fair trial and access to court. In addition, evaluations on principals pf procedural economy, publicity, power of disposition and honesty are conducted. With regard of principal of publicity, it can be considered that principal of confidentiality of mediation is an advantage. The evaluations on principal of power of disposition are made in frame of substantial and procedural law. Furthermore, taking the features of American civil procedure law, it is concluded that mandatory mediation is not compatible with the role of judge in Turkish law. With regard of principal of honesty, an evaluation in the light of substantial law is also made and it is concluded that rules to maintain honesty in mandatory mediation are not sufficient in Turkish law. As an addition, it is also stated that sanction in Code of Mediation Art. 18A/11 is unproportionate in context of principal of honesty before courts. The second chapter of this study focuses on conditions of TCC Art. 5A. With this regard, a comparative evaluation on commercial actions is made. Commercial actions, regulated with TCC Art. 4 in Turkish law, are regulated in relation with commercial courts in other law systems. With this evaluation, it is noted that in commercial courts, which aims to solve disputes in a cheap, quick and effective manner, gives place to judges who have not a judicial notion in other law systems. In Turkish literature, it is rightly emphasized that such an application is not appropriate for Turkish law. TCC Art. 5A is also examined within frame of civil procedure and commercial law. Within civil procedure law frame, the concept of cause of action is examined, as well as features of TCC Art 5A in relation to claim in actions. Within commercial law frame, since the agreement concluded within mediation is a contract in context of substantial law, the notion of prudent merchant is evaluated. Furtermore, for mandatory mediation demonstrates features within light of Code of Mediation Art. 5 and principal of confidentiality, an evaluation of trade secrets are also conducted. The third and last chapter concentrates on examination of mediation as a cause of action in equity company disputes. Thus, an action named shareholders' action in German law, which is clarified using notion of actio pro socio, is evaluated. According to this evaluation it is concluded that, unlike simple partnerships, shareholders shall submit their claims against legal entity of equity companies and not against other shareholders. Neverthless, it is also observed that in some cases shareholders are entitled to submit the tools of defence of equity companies for interests of company. This evaluation is essential in order to determine the parties of dispute and the persons effected from the agreement reached at the end of mandatory mediation process. Following this evaluation, the kinds of disputes in equity companies, which fall into scope of TCC Art. 5A, are determined and the features demonstrated by them in context of mediation as a cause of action are defined. In order to comply with this evaluation, information on each subject of action is given, features of the relevant actions are explained and in the light of all evaluations, conditions of application of mediation as a cause of action are explained. Finally, in light of evaluations made within this study, our de lege ferenda opinions on mandatory mediation in equity companies are set. Within this frame, since dispute in equity companies are subject to limitations on equity company law and compulsory legal rules, it is stated that they might not always compatible with mediation as a cause of action. In addition, possible problems arisen from lack of legal supervision in mediation process are also mentioned. As a result, it is concluded that, it would be more convenient to regulate court annexed dispute resolution tools, similar with examples of Germany and Switzerland. With regard to bankruptcy proceedings, it is concluded that possible problems in relation to Turkish Code of Bankruptcy and Enforcement Art. 226 are highlighted and it is suggested that, in order to eliminate such problems, necesarry regulations by legislator should be made. Lastly, taking the goals of mediation into consideration, in order to reach these goals effectively, the importance of giving parties the opportunity to be able to choose other means of dispute resolution apart from mandatory mediation, is found to be essential. Thus, dispute resolution process will take place in a quick and cheap manner and parties will have the chance to be able to choose a dispute resolution method that suits their needs and interests.
Keywords: MARD; Mediación; Mediation; Mediação; Médiation

Arabulucu mesleki sorumluluk sigortası bir uygulama - Yildirim, Ferhat (Marmara Üniversitesi, 2024)
Riskleri bertaraf etmenin çeşitli yolları olmakla birlikte sigorta bu yöntemler içerisinde en bilinen ve tercih edilenidir. Risklerin çeşitliliği, farklı sigorta türlerinin oluşumuna neden olmaktadır. Duyulan ihtiyaçlara, mevcut risklere göre sigortanın şekillenmesi, öznelleştirilmesi mümkündür. İfa edilen meslek nedeniyle üçüncü kişilere verilecek zarardan ötürü oluşan sorumluluğun sigortacıya devrini esas alan mesleki sorumluluk sigortası da farklı sigorta türlerinden sadece bir tanesidir. Alternatif uyuşmazlık çözüm yöntemlerinden olan arabuluculuk, 2012 yılında 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu ile Türk hukuk sistemine dahil olmuştur. Kanunun yürürlüğe girdiği tarihten bu yana arabuluculuk yönteminin kullanımı hızla yaygınlaşmış ve uyuşmazlığın taraflarınca tercih görmesi, arabuluculuğu en popüler alternatif uyuşmazlık çözüm yöntemlerinden biri haline getirmiştir. Buna bağlı olarak da Türkiye'de arabulucu sayısı gün geçtikçe artış göstermeye devam etmektedir. Arabulucular siciline kayıtlı arabulucuların, arabuluculuk uygulamalarında karşı karşıya kaldıkları risklerin varlığı, yasal düzenleme dışında da bir takım koruyucu mekanizmaların devreye girmesini zaruri kılmaktadır. Özellikle mesleğin ifası esnasında meslek nedeniyle üçüncü kişilere karşı sorumluluğun doğumuna yol açan hallerin varlığında sigorta önemli bir enstrüman olarak görülmektedir. Çalışma ile İstanbul ilinde (Avrupa-Anadolu yakasında) aktif olarak faaliyet gösteren ve Arabuluculuk Daire Başkanlığı tarafından tutulan arabulucular siciline kayıtlı olan 30 arabulucu ile yapılan derinlemesine görüşme neticesinde, arabuluculuğun katılımcıların çoğunluğu tarafından meslek olarak görülmesi, mehaz olarak kabul edilen Avusturya Hukuk Uyuşmazlıklarında Arabuluculuk Federal Kanunu uygulamasında yer alan ve mesleğin ifası için ön koşul olarak sunulan arabulucu mesleki sorumluluk sigortasının Türkiye açısından ne denli uygulanabileceği ve tercih göreceği sorusunu ortaya çıkarmış ve böyle bir sigortanın tesis edilmesi durumunda arabulucuların bu sigortaya duydukları ihtiyaç ve yaklaşımları ele alınmış ve irdelenmiştir. While there are various ways to eliminate risks, insurance is the most well-known and preferred one among such methods. The diversity of risks leads to the occurrence of different types of insurance. It is possible to shape and subjectivize insurance depending on the needs and existing risks. Professional liability insurance, which is based on the transfer of liability to the insurer for damage to third parties due to the profession being performed, is just one of the different types of insurance. Mediation, one of the alternative dispute resolution methods, was introduced to the Turkish legal system in 2012 with the Law No. 6325 on Mediation in Civil Disputes. Since the date the law came into force, the use of the mediation method has become widespread rapidly and its preference by the parties to the disputes has rendered mediation one of the most popular alternative dispute resolution methods. Accordingly, the number of mediators in Türkiye continues to increase day by day. The existence of risks faced by the mediators registered with the registry of mediators in mediation practices necessitates the introduction of certain protective mechanisms in addition to the statutory provisions. Insurance is considered as an important instrument, particularly in the existence of cases that lead to the emergence of liability against third parties due to the profession while the profession is being performed. With the study, as a result of the in-depth interviews conducted with 30 mediators who are active in the province of Istanbul (European and Anatolian sides) and registered with the registry of mediators maintained by the Department of Mediation, the fact that mediation is considered as a profession by the majority of the participants reveals the question of to what extent the mediator professional liability insurance, which is included in the practice of the model law i.e., the Austrian Federal Law on Mediation in Civil Disputes and presented as a prerequisite to perform the profession, is applicable and preferable for Türkiye; and the mediators' needs and approaches to this insurance in case of creation of such insurance are discussed and analyzed in the study.
Keywords: Assurance; Geçmişe etkili sigorta; Liability insurance; Mandatory mediation; Mesleki sorumluluk sigortası; Mesuliyet sigortası; Médiateur; Private insurance; Private insurances; Professional liability insurance; Recroactive insurance; Responsabilité professionnelle; Sorumluluk sigortası; Zorunlu arabuluculuk; Özel sigortacılık; Özel sigortalar

Anonim şirkette imtiyazlı pay sahipleri özel kurulu - Yilmaz, Hümeyra (İstanbul Üniversitesi, 2024)
Bu doktora tezi, 6102 sayılı Türk Ticaret Kanunu'nun 454. maddesinde düzenlenen imtiyazlı pay sahipleri özel kurulunu konu almaktadır. Çalışmanın ilk bölümünde imtiyaza ilişkin genel bilgiler verildikten sonra ikinci bölümünde imtiyazlı pay sahipleri özel kurulunun yapısı, yetkisi, hukuki niteliği üzerinde durulmuştur. Çalışmanın üçüncü ve dördüncü bölümlerinde, imtiyazlı pay sahipleri özel kurulunun toplanma şartları ile toplantı süreci kapsamlı bir şekilde ele alınmıştır. Çalışmanın son bölümünde ise imtiyazlı pay sahipleri özel kurul kararlarının hukuki niteliği, etkisi ve hükümsüzlüğü irdelenmiştir. Çalışmanın hazırlanmasında, Türk hukukundaki ilgili mevzuat hükümleri başta olmak üzere karşılaştırmalı hukuktaki dikkate değer yasal düzenlemeler, öğretideki görüşler ve yargı kararlarından faydalanılmıştır. Anahtar kelimeler: Anonim şirketler, imtiyaz, TTK m. 454, imtiyazlı pay, imtiyazlı pay sahipleri özel kurulu. This doctoral thesis deals with the special committee of privileged shareholders regulated under Article 454 of the Turkish Commercial Code No. 6102. After giving general information about privilege in the first part of the study, the structure, authority, and legal nature of the special committee of privileged shareholders are mentioned in the second part. In the third and fourth parts of the study, the conditions for the meeting and the meeting process of the special committee of privileged shareholders are extensively discussed. In the last part of the study, the legal effect, nature, and invalidity of the special committee decisions of privileged shareholders are examined. In the preparation of the study, notable legal regulations in comparative law, doctrines and judicial decisions, especially related legislation in Turkish law have been benefited from. Key Words: Joint Stock Companies, privilege, the article 454 of the Turkish Commercial Code No. 6102, privileged share, the special committee of privileged shareholders.
Keywords: Anonim şirketler; Joint stock company; Special meeting; Turkish commercial law; Türk ticaret hukuku; Özel kurul

Ticari İşlemlerde Taşınır Rehni Kanunu uyarınca ticari işletme rehninin kuruluşu - Balkan, Nurdan (İstanbul Üniversitesi, 2023)
6750 sayılı Ticari İşlemlerde Taşınır Rehni Kanunu (TİTRK) 01.01.2017 tarihi itibariyle yürürlüğe girmiştir. TİTRK'de de ticari işletme, üzerinde rehin kurulabilecek taşınır varlıklardan biri olarak düzenlenmiştir. Hukuki niteliği itibariyle taşınır olarak kabul edilmeyen ticari işletmenin, taşınır varlıkların rehninin düzenlendiği bir Kanun'da kapsamlıca düzenlenemediği ilk bakışta görülmektedir. Bu nedenle ticari işletme rehninin kuruluşu tez konusu olarak seçilmiştir. Çalışmamızda TİTRK ile yapılan değişiklikler ve yenilikler ticari işletme rehninin kuruluşu özelinde incelenmiştir. Bu kapsamda ticari işletme rehninin kuruluşu konusu, TİTRK ve ikincil mevzuat, yeri geldikçe mülga TİRK ve TİTRK'nin mehazı olduğunu düşündüğümüz Uncitral Secured Transactions Model Law ile karşılaştırmalı olarak değerlendirilmiştir. Ticari işletme rehninin kuruluşu, ticaret hukuku, medeni hukuk ve borçlar hukukunun ilgili düzenlemelerinin bir bütün olarak incelenmesini gerekli kıldığından yeri geldikçe, TTK, TMK ve TBK'nın ilgili düzenlemeleri, tez konumuz özelinde incelenmiştir. The Law Numbered 6750 "The Law On Pledge Over Movable Assets In Commercial Transactions (TITRK)", which is a regulation that allows not only commercial enterprises but also many movable assets to be pledged without delivery entered into force as of 01.01.2017. In TITRK, a commercial enterprise is regulated as one of the movable assets that can be pledged too. However, it can be seen at first glance that the commercial enterprise, which is not considered as movable due to its legal nature, cannot be comprehensively regulated in the Law that regulates the pledge of movable assets. For this reason, the establishment of the commercial enterprise pledge has been chosen as the thesis topic. In our study, the changes and innovations made with TITRK were examined in terms of the establishment of the commercial enterprise pledge. In this context, the establishment of the commercial enterprise pledge have been examined in comparison with TITRK, its secondary legislation, mulga TIRK and Uncitral Secured Transactions Model Law, which we think is the basis of TITRK. Since the establishment of the commercial enterprise pledge requires the examination of the relevant regulations of the commercial law, civil law and law of obligations as a whole, the relevant regulations of the Turkish Commercial Code, Turkish Civil Code and Turkish Code of Obligations have been examined specifically for our thesis topic. In this section the secured transactions arrangements in comparative law will be discussed too.
Keywords: Commercial Transactions; Commercial institutes; Hypotheca; Movable Assets; Pledge of assets agreement; Rehin hakkı; Taşınır mal; Ticari işlemler; Ticari işletme rehni sözleşmesi; Ticari işletmeler; Ticari İşlemlerde Taşınır Rehni Kanunu; Trading operations

Kurumsal yönetim bakış açısıyla mali durumu bozulan anonim şirketlerde alacaklıların menfaatinin korunması - Demi̇rel Özdemi̇r, Duygu (Kocaeli Üniversitesi, 2023)
Anonim şirketler hukukunda alacaklılar, şirketlerin dış finansman kaynaklarının merkezini oluşturmakta ve bu nedenle de son derece önemli bir menfaat grubunu teşkil etmektedirler. Bu durum şirket alacaklılarının çıkarlarının etkin bir biçimde gözetilmesi ve korunmasını gerekli kılmaktadır. Zira alacaklıların alacaklarına kavuşabilmeleri için müracaat edebilecekleri tek kaynak şirketin malvarlığıdır. Dolayısıyla anonim şirketin mali durumunun bozulması sonucu malvarlığının kayba uğraması veya uğrama tehlikesi altında olması, alacaklıların menfaatlerini zedeleyici niteliktedir. Bu durum mali durumu bozulan anonim şirketlerde, alacaklıların menfaatlerinin gözetilmesini ve özellikle de öncül (ex-ante) koruma imkânlarıyla bu risk gerçekleşmeden önce bu konuda tedbirler alınmasını gerektirmektedir. Kurumsal yönetim anlayışı, anonim şirketlerde menfaat grupları arasındaki çıkar çatışmalarının en iyi, en adil şekilde dengelenmesini hedeflemektedir. Bu itibarla bu tez çalışmasında söz konusu menfaat çatışmaları özelinde kurumsal yönetimin şeffaflık, adillik, hesap verilebilirlik ve sorumluluk ilkeleri çerçevesinde bir menfaat grubu olarak şirket alacaklılarının menfaatlerinin, mali durumu bozulan veya bozulma tehlikesi altında olan anonim şirketlerde nasıl gözetilmesi ve korunması gerektiği hususunda bir bakış açısı sunulması hedeflenmektedir. Bu bakış açısından hareketle sermaye kaybı yaşayan, borca batık hale gelen anonim şirketlerin mali durumlarının iyileştirilmesi maksadıyla sermayenin korunması esası benimsenerek öngörülen TTK m.376 hükmü ile bu hükmün uygulanmasına ilişkin Tebliğ kapsamında öngörülen düzenlemelerin, alacaklıların menfaatlerinin korunması bakımından etkileri tartışılmaktadır. Ayrıca ilgili hükümlerin, şirketlerin mali yapılarının güçlendirilmesi bakımından yeterlilikleri ve yerindelikleri, karşılaştırmalı hukuk düzenlemeleri de göz önünde bulundurularak eleştirel bir bakış açıyla ayrıntılı şekilde incelenmektedir. Creditors are the key to external financing sources for companies under the statute of joint stock companies, and hence represent an important figure interest group. This situation needs the effective supervision and protection of the company's creditors' interests. This is because the company's assets are the only source to which creditors can turn to acquire receivables. Hence, the loss or threatened loss of the joint stock company's assets because of its worsening financial situation is detrimental to the creditors' interests. This circumstance necessitates that the interests of the creditors of companies with a worsening financial situation be considered and that steps be taken in this respect prior to the realization of this danger, particularly with ex-ante protection opportunities. The corporate governance method strives to achieve the most equitable resolution of conflicts of interest between interest groups in joint stock companies. This thesis aims to provide a perspective on how the interests of company creditors, as an interest group, should be observed and protected in joint stock companies whose financial situation deteriorates or is at risk of deterioration, within the framework of the principles of transparency, fairness, accountability, and responsibility of corporate governance. From this perspective, to improve the financial situation of companies that have capital loss and become over-indebted, the effects of the provisions of TCC art.376 and the Communiqué, which are envisioned based on the principle of capital maintenance, are discussed in terms of protecting the interests of creditors. In addition, the adequacy and suitability of the relevant rules in terms of strengthening the financial structures of corporations are analysed in depth from a critical standpoint, considering the norms of comparative law.
Keywords: Corporate governance; Creditors; Financial distress; Joint stock company

Milletlerarası ticari tahkimde hakem kararlarının iptali - Ersari̇, Danyal (Marmara Üniversitesi, 2023)
Günümüzde ticaretin globalleşmesi ile birlikte tahkim, uluslararası uyuşmazlıkların çözümünde devlet mahkemelerine nazaran kişiler, şirketler ve devletler tarafından daha çok tercih edilir hale gelmiştir. Bu tercihin en önemli sebeplerinden biri tahkim yargılaması sonucunda verilen hakem kararlarının tıpkı mahkeme kararlarında olduğu gibi kesin ve bağlayıcı olmasıdır. Ancak aleyhine karar verilen taraf, ilgili hakem kararının adalete uygun olmadığını düşünebilir. Bu bağlamda hakem kararlarının devlet mahkemeleri tarafından denetlenebilmesi için neredeyse tüm milli hukuk sistemlerinde hakem kararlarına karşı denetim yolu olarak "iptal davası" öngörülmüştür. İptal talebinde bulunan taraf belirli sebeplerin olması halinde tahkim yeri mahkemesinde iptal davası açabilecektir. Hakem kararına karşı iptal talebinde bulunan tarafın amacı, kararın bir kısmını ya da tamamını geçersiz hale getirmek ve icrasını engellemektir. UNCITRAL Model Kanun ve ulusal hukuk sistemlerinde iptal sebepleri sınırlı şekilde sayılmıştır. Ancak bazen bu iptal sebeplerinin faklı şekillerde yorumlandığı görülmüştür. İptal sebeplerinin geniş yorumlanması hakem kararlarının iptal olasılığını orantısız şekilde arttıracaktır. Bu durum alternatif uyuşmazlık çözüm yolu olan tahkimin güvenirliğine zarar verdiği gibi uzun, meşakkatli ve masraflı tahkim yargılama sürecini de boşa çıkaracaktır. Ancak, iptal sebeplerin adaletsizliğe yol açacak şekilde çok dar yorumlanması da keyfiliğe, tutarsızlığa ve tarafların istemediği sonuçlara yol açacaktır. Bu çerçevede Türk kanunları dahil çeşitli ülkelerdeki kanunları ve mahkeme uygulamalarını dikkate alarak kanımızca iptal sebepleri bakımından doğru yaklaşımları ortaya koymaya çalışacağız. Çalışmamız üç bölümden oluşmaktadır. İlk bölümde milletlerarası tahkime ilişkin genel bilgiler, yabancı hakem kararlarının tabiiyetinin belirlenmesi ve iptal davasına konu olabilecek yabancı hakem kararlarının türleri yer almaktadır. Bunun devamında, ikinci bölümde, çeşitli ülkelerin tahkime ilişkin kanunları, tahkime ilişkin milletlerarası literatürde kabul gören hukuki metinleri de dikkate alınarak iptal sebepleri ortaya konulacaktır. Aynı zamanda, konu ile ilgili doktrindeki görüşlere yer verilerek çeşitli ülkelerde verilen mahkeme kararları çerçevesinde iptal sebeplerine ilişkin yaklaşımlara ver verilecektir. Çalışmamızın üçüncü ve son bölümünde ise iptal davasının tarafları, iptal davasında görevli ve yetkili mahkeme ve iptal davasından feragat konuları Türk hukuku ve karşılaştırmalı hukuk bakımından incelenmeye çalışılmaktadır. Along with the globalization of trade, arbitration has become more preferred by individuals, companies and states than state courts in resolving international disputes. One of the most important reasons for this preference is that the arbitral awards given after the arbitration proceedings are final and binding, just as the court decisions. However, the party rendered against the award may consider it unjust. In this context, in order for the arbitral awards to be audited by the state courts, "annulment case" is designed as a legal remedy in almost all national legal systems. The party requesting annulment may file an action for annulment in the court of the place of arbitration if there are certain reasons. The purpose of the party requesting annulment against the arbitral award is to invalidate some or all of the decision and to prevent its execution. Although the reasons for annulment are limited and similar in many legal systems, the interpretation of these reasons is of great importance. A broad interpretation of the grounds for annulment will disproportionately increase the possibility of annulment of arbitral awards. This situation will not only harm the reliability of arbitration, which is an alternative dispute resolution method, but will also nullify the long, laboursome and costly arbitration proceedings. On the other hand, much narrower interpretation of the grounds for annulment in a way that leads to injustice may lead to arbitrariness and inconsistency, as well as result in undesirable results by the parties. Considering these, we will try to put forward approaches that can be consistent in terms of the grounds for annulment, taking into account the laws and court practices in various countries, including Turkish laws. This study consists of three parts. In the first part, general information about international arbitration, determination of the nationality of foreign arbitral awards and types of foreign arbitral awards that may be subject to annulment proceedings are included. Following this, in the second part, the reasons for annulment will be presented considering the arbitration laws of various countries and the internationally accepted legal texts on arbitration. At the same time, we try to put forward the approaches regarding the reasons for annulment within the framework of the court decisions given in various countries by giving place to the opinions in the doctrine on the subject. In the third and final part of our study, the parties of the annulment case, the competent court in charge of the annulment case and the waiver of the annulment case are to be examined in terms of Turkish law and comparative law.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitral Awards; Arbitration; International commercial arbitration

Anonim şirketlerde imtiyazlı paylar - Erten, Cengiz (Kocaeli Üniversitesi, 2023)
6102 sayılı Türk Ticaret Kanunu (TTK) ile Türk Ticaret Hukuku'nda özellikle anonim şirketler hukukunda yapılan değişiklikler arasında imtiyazlı paylarla ilgili düzenlemeler de bulunmaktadır. Mülga 6762 sayılı Türk Ticaret Kanunundaki (eTK) hükümlere benzerlik gösteren yönleri olsa da imtiyazlı paylarla ilgili daha ayrıntılı, yenilikler getiren ve önceki Kanun döneminde karşılaşılan sorunları gidermeye çalışan düzenlemelerin yapıldığı görülmektedir. TTK'daki imtiyazlı paylarla ilgili düzenlemelerin eTK döneminde ortaya çıkan sorunları giderip gidermediğinin ya da yeni sorunlara, belirsizliklere ve tartışmalara yol açıp açmadığının tespit edilerek değerlendirilmesi amacı bu tezin yazılmasına sebep oluşturmaktadır. Birinci bölümde önce genel olarak pay kavramı, imtiyazlı payın tanınması koşulları, imtiyaz kavramının terminolojik yönü ve mevzuatımızda konuyla ilgili düzenlemelerle hukuk sistemimize esin kaynağı olan yabancı hukuk sistemlerindeki düzenlemeler incelenmiştir. Ardından, imtiyaz tanınan hakların, eşitlik ilkesi, müktesep hak ve vazgeçilmez hak ile olan ilişkilerine değinilmiş ve imtiyazlı pay kavramının nasıl tanımlanması gerektiği üzerinde durulmuştur. Tezin asıl omurgasını oluşturan ikinci bölümde, imtiyaza konu haklar, malvarlığı hakları ve yönetim hakları olarak iki asıl eksen üzerinde incelenmiştir. İkinci bölüm için en fazla tartışılmış bulunan konu, yönetim haklarında imtiyaza ilişkindir. Yönetim haklarında imtiyazı oluşturan iki alt başlık, oy hakkında imtiyaz ve yönetim kurulunda temsilde imtiyaz ayrıntılı bir şekilde incelenmeye çalışılmış, imtiyazın kanundan kaynaklanan nedenlerle engellenmesinden bahsedilmiş ve diğer haklarda imtiyaza değinilmiştir. Tezin üçüncü bölümü imtiyazların korunması konusuna ayrılmıştır. Bu bölümde imtiyazlı pay sahipleri özel kurulunun (İPSÖK) yapısı, niteliği ve toplanması ile özel kurulun onayına bağlı kararlar halka açık olan ve olmayan şirketler dikkate alınarak açıklanmıştır. Üçüncü bölümde ayrıca İPSÖK kararlarına karşı açılacak iptal davalarıyla ilgili değerlendirmeler yapılmıştır. It is observed that although there are some similarities with the previous one, the new Turkish Commercial Code, Law No: 6102, introduces more detailed and innovative arrangements which is intended to provide an answer to the problems experienced during the abrogated code was in force in relation to preference shares. It is easily can be said that, by and large, the topic "preference shares" is the one of the most radically altered topic in the new code. The main purpose of this thesis is to shed light whether these innovative arrangements in the new code actually solving the problems that is intended to solve or, rather opposite, causing new problems and ambiguities. For this purpose, the first section of this thesis is allocated to analyse the concept of "share" in general and under which conditions the preference shares are granted first and then the meaning of the concept of "preference" is investigated. It is followed by subsections devised to identify the current domestic law, and comprative law that inspried the law makers in this area. In the following subsections it is attempted to explain where preference shares stand with respect to principle of equality, vested interests and inalienable rights, and how the concept of preference shares should be defined. In the second section, which constitutes the backbone of this thesis, the rights that are being subject of the preference shares are examined on the axis of the assest rights and the administrative rights. The topic of the administrative rights attached to preference shares is the most debated topic in this section. In this context under the head of the administrative rights, the issues related to priveleges in votes and the representation on the executive board are examined seperately in two separate subsections. Also in this subsection the issues of statutory basis of the prevention of preferences and the preferences in relation to other rights are grappled. The third section of the thesis is completely devised to the issues related to the protection of the preference shares. In this section the structure, qualifications, gathering of the board of preference shares owners and the decisions subject to approval of this board are explained in the context of private and public companies. In this section the suits that could be brought for the annulment of this board decision is evaluated briefly.
Keywords: Joint stock company; Preference Shares

İcra ve iflâs hukukunda ticarî işletmenin bir bütün hâlinde paraya çevrilmesi - Erzeybek, Hakan (Ankara Hacı Bayram Veli Üniversitesi, 2023)
Ticarî işletme, kendisine özgülenen malvarlığı unsurlarının tamamı ile kapsamlı bir organizasyon niteliğini haiz olup, ticarî ve ekonomik bir bütünlük arz etmektedir. Ticarî işletme, ticarî bir amaca özgülenen ve bütünlük arz eden yapısı gereği, tacire ait malvarlığı unsurlarından belki de en değerlisidir. Bu yapısı gereği ticarî işletme, cebri icra hukukunda alacaklıların ilk müracaat edeceği malvarlığı unsurudur. Alacaklıların borçluya ait mal veya hakların paraya çevrilmesi sonucu tatmin edilmesi, cebri icra hukukuna hâkim olan genel bir ilkedir. Ticarî işletmenin cebri icra hukukunda paraya çevrilmesi, kapsamında bulunan mal veya hakların niteliği ve çeşitliliği gözetildiğinde ayrı bir önem taşımaktadır. Ticarî işletmeye özgülenen mal veya hakların ayrı ayrı paraya çevrilmesi, bu mal veya hakların parçalanmasına sebep olacağından, işletme faaliyetinin sona ermesine yol açar. Ticarî işletme faaliyetinin devamlılığının zedelenmesi, alacaklı ve borçlu menfaatlerini doğrudan etkilediği gibi ekonomik, sosyal ve toplumsal bir kısım olumsuz etkileri de beraberinde getirir. Bu nedenle, cebri icra prosedürleri içerisinde ticarî işletme bütünlüğünün bozulmaması büyük önem arz eder. Ticarî işletmenin cebri icra yoluyla bir bütün hâlinde paraya çevrilmesi, işletmeye özgülenen mal veya hakların bütünlüğünün bozulmasının önüne geçerek, faaliyetin devamlılığını sağlayan bir paraya çevirme şekli olarak karşımıza çıkmaktadır. Bunun yanında, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi ile ayrı ayrı paraya çevirmeye nazaran daha yüksek gelir elde edilir. Çalışmamızda, öncelikle, ticarî işletmenin bir bütün hâlinde paraya çevrilmesi açısından karşılaştırmalı hukuk sistemlerinde yer alan bazı düzenlemeler incelenmiştir. Daha sonra, ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin İcra ve İflâs Kanunu'nda yer alan her bir paraya çevirme türü açısından durumu ve ticarî işletmenin bir bütün hâlinde paraya çevrilmesinin yerine getirilme usulü ile paraya çevirmenin etki ve sonuçları ortaya konulmaya çalışılmıştır. A commercial enterprise has the character of a comprehensive organization with all the elements of assets specific to it, and it offers a commercial and economic integrity. A commercial enterprise, due to its structure that is specific to a commercial purpose and offers integrity, is perhaps the most valuable of the elements of the merchant's assets. Due to this structure, a commercial enterprise is the first asset element that creditors will apply for in forced execution law. The satisfaction of creditors as a result of the conversion of the debtor's goods or rights into money is a general principle that dominates the enforcement law. The conversion of a commercial enterprise into money in compulsory enforcement law is of particular importance when the nature and diversity of the goods or rights covered by it are taken into account. The conversion of goods or rights specific to the commercial enterprise into money separately leads to the termination of the business activity, as this will lead to the fragmentation of these goods or rights. Damage to the continuity of commercial business activity directly affects the interests of creditors and debtors, as well as brings with it some negative economic, social and social effects. For this reason, it is of great importance that the integrity of the commercial enterprise is not disrupted within the forced execution procedures. The conversion of a commercial enterprise into money as a whole through forced execution appears as a form of conversion into money that ensures the continuity of activity by preventing the deterioration of the integrity of the goods or rights specific to the enterprise. In addition, a higher income is obtained by converting the commercial enterprise into money as a whole than by converting it into money separately. In our study, first of all, some regulations in comparative legal systems have been examined in terms of the conversion of commercial enterprise into money as a whole. Subsequently, the situation of the conversion of the commercial enterprise into money as a whole in terms of each type of conversion contained in the Execution and Bankruptcy Code, as well as the procedure for performing the conversion of the commercial enterprise into money as a whole, as well as the effects and consequences of the conversion into money have been tried to be revealed.
Keywords: Cebri icra hukuku; Commercial institutes; Compulsory enforcement law; Ticari işletmeler; Turkish commercial law; Türk ticaret hukuku

Bireysel iş hukukunda arabuluculuk - Gül Küçükkaya, Hande (Marmara Üniversitesi, 2023)
Arabuluculuk tarafların tarafsız bir üçüncü bir kişinin yardımı ile ihtilaflarını çözmeye yardımcı olması olarak tanımlanabilir. Türkiye'de özel hukuktan doğan ve tarafların üzerinde serbestçe tasarruf edebilecekleri uyuşmazlıkların arabuluculuk ile çözümüne ilişkin 6325 sayılı Hukuk Uyuşmazlıklarında Arabuluculuk Kanunu'nun 2013 yılında kabulü ile arabuluculuk uygulamasına geçilmiştir. 7036 sayılı İş Mahkemeleri Kanunu ile 2018 yılı itibariyle dava şartı arabuluculuk kavramı Türk hukuk literatürüne girmiştir. 7036 sayılı İş Mahkemeleri Kanunu md.3 uyarınca kanuna, bireysel iş sözleşmesine, toplu iş sözleşmesine dayanan alacak, tazminat veya işe iade talebi ile açılan davalarda arabuluculuğa başvurulması dava şartıdır. İtalya, Almanya ve ABD'nin bazı eyaletlerinde iş hukukunda dava şartı arabuluculuk uygulaması yoktur. İngiltere'de iş mahkemelerine başvurmak için önce ACAS isimli kuruma başvurmak gerekir. ABD 'de ise iş ilişkilerindeki ayrımcılık iddiaları öncelikle EEOC'de görülmektedir. Bireysel İş Hukukunda Arabuluculuk başlıklı doktora tezi çalışmamız dört bölümden oluşmaktadır. Çalışmanın birinci bölümünde alternatif uyuşmazlık çözüm yöntemleri kavramı ve belli başlı alternatif uyuşmazlık yöntemleri irdelenerek incelenmiş, ikinci bölümde arabuluculuk kurumu, amacı, prensipleri, türleri, arabulucunun hak ve yükümlülükleri, arabulucu ve arabuluculuk sözleşmelerinin hukuki mahiyeti ve arabuluculuk etiği gibi konular çalışılmıştır. Mukayeseli İş Hukukunda Arabuluculuk başlıklı üçüncü bölümde, arabuluculuğun anavatanı olan Amerika Birleşik Devletleri, Birleşik Krallık gibi Anglo Sakson sistemindeki devletlerde, İtalya, Almanya, Fransa gibi Roma Cermen sistemindeki devletlerde ve Avrupa Birliği müktesabatında arabuluculuğun nasıl düzenlendiği ve son olarak dördüncü bölüm olan Türk İş Hukukunda Arabuluculuk başlığı altında, dava şartı arabuluculuk kavramına ilişkin konular yargı kararları da işlenerek ayrıntılı olarak irdelenmiştir. Mediation can be defined as helping parties resolve their disputes with the help of a third party. With the adoption of the Law No. 6325 on Mediation in Civil Disputes in 2013, mediation has been implemented regarding the resolution of disputes arising from private law and on which the parties can freely dispose of. As of 2018, with the adoption of the Labor Courts Law numbered 7036 the concept of mediation as a cause of action in employment disputes litigation introduced in our legal literature. Pursuant to Article 3 of Labor Courts Law numbered 7036, lawsuits filed with the demand for receivables, compensation or reemployment based on the law, individual employment contract, collective bargaining agreement are subject to mediation as a cause of action. In Italy and Germany mediation in employment disputes does not exist. In England, in order to apply to the labor courts, firstly it must be applied to ACAS. In the United States of America, for discriminatory allegations in the employment relation firstly EEOC must be addressed. The doctoral thesis titled Mediation in Individual Employment Law consists of four parts. In the first part of the study, the concept of the alternative dispute resolution methods is investigated by examining the main alternative dispute methods, in the second part, the mediation institution, its purpose, principles, types, rights and responsibilities of the mediator, the legal nature of the mediator and mediation agreemets and mediation ethics are studied. In the third part titled Mediation in Comparative Employment Law, the Anglo-Saxon countries such as the United States of America and the United Kingdom, which are the homeland of mediation, in the Roman Germanic system states such as Italy, Germany France and in European Union legal system are explained and lastly under the title of Mediation in Turkish Employment Law, which is the fourth part, the issues related to the concept of mediation as a cause of action are also discussed in detail adding judicial decisions.
Keywords: ACAS; Arabuluculuk; Cause of action; Comparative law; Danışma; Dava şartı; Karşılaştırmalı hukuk; Labour disagrement; Labour dispute; Labour law; Mediation; Uzlaşma ve Tahkim Servisi; İş hukuku; İş uyuşmazlıkları

Anonim ortaklıkta yönetim ve temsil yetkisinin devrinde yönetim kurulu üyelerinin hukuki sorumluluğu - Kalender, Süleyman (Çukurova Üniversitesi, 2023)
Anonim şirketlerde yönetim veya temsil yetkisi kural olarak yönetim kurulu tarafından kullanılmakla birlikte, özellikle halka açık veya büyük ölçekli ortaklıklarda söz konusu yetkilerin tamamının yönetim kurulu tarafından bizzat yerine getirilmesi uygulamada sık rastlanan bir durum değildir. Bu nedenle kanunda, yönetim kuruluna, yönetim veya temsil yetkisinin 6102 sayılı Türk Ticaret Kanunu' nun 367/I ve 370/II hükümlerinde yer alan şartlara uygun olarak, mevcut yönetim kurulu üyelerinden bir veya birkaçına yahut üçüncü kişilere devretmek suretiyle, şirketin yönetim teşkilatını belirleme yetkisi tanınmıştır. Şirket yönetimi konusunda uzmanlaşmış ve yeterli mesleki tecrübeye sahip olan kişilere yetkilerin devredilmesi, bir yandan şirkette profesyonelleşmeyi sağlamakta, diğer yandan kural olarak, devredilen yetkilerle birlikte bu kapsamda ortaya çıkabilecek hukuki sorumluluk da devredilmiş sayılacağından, yönetim kurulu üyelerinin hukuki sorumluluğunu sınırlandırmaktadır. Yönetim veya temsil yetkilerinin geçerli bir şekilde devredilmesi halinde, devredilen yetkilerle ilgili olarak yönetim kurulu üyelerinin hukuki sorumluluğu; murahhasların seçiminde, onlara verilecek talimatlarda ve murahhasların üst gözetiminde göstermeleri gereken makul derecede özen yükümlülüğü ile sınırlı olarak devam eder. Çalışmamızda, geçerli ve geçersiz yetki devri hallerinde, yönetim kurulu üyelerinin hukuki sorumluluğunun ne şekilde ortaya çıkacağı meselesi, mehaz İsviçre hukukundaki görüş ve yargı kararlarına yer verilmek suretiyle, detaylı bir şekilde incelenmiştir. Although the management or representation authority in joint stock companies is used by the board of directors as a rule, it is not common in practice that all of the said authorities are personally exercised by the board of directors, especially in publicly held or large-scale partnerships. For this reason, in the law, the board of directors is authorized to determine the management organization of the company by delegating the management or representation authority to one or more of the existing board members or to third parties in accordance with the provisions of the Turkish Commercial Code numbered 6102, 367/I and 370/II has been recognized. Delegation of powers to people who are specialized in company management and have sufficient professional experience, on the one hand, ensures professionalization in the company, and on the other hand, as a rule, legal responsibility that may arise in this context together with the delegated powers will be deemed to have been transferred, thus limiting the legal liability of the members of the board of directors. In case of a valid transfer of management or representation powers, the legal responsibility of the members of the board of directors regarding the delegated powers; limited to the reasonable care obligation that they must show in the selection of the executive directors, in the instructions to be given to them and under the supervision of the executive directors. In our study, the issue of how the legal responsibility of the members of the board of directors will arise in cases of valid and invalid delegation of authority has been examined in detail by including the opinions and judicial decisions in the Swiss law.
Keywords: Board of directors; Joint stock company

Milletlerarası ticari tahkimde delillerin değerlendirilmesi - Kesi̇kli̇, Ömer (Galatasaray Üniversitesi, 2023)
It is nowadays generally accepted that international commercial arbitration is the most popular method of resolving international disputes between commercial parties. This popularity is the cumulative result of many advantages that international commercial arbitration offers to the parties. It is suggested in the literature that one of these advantages is the freedom of parties and the resulting procedural flexibility. In virtue of this principle, the parties have the opportunity to establish a specific method of adjudication adapted to the nature of their dispute. This opportunity is provided by the fact that the arbitration regulations do not include detailed rules on the collection of evidence, thus leaving the parties and the arbitrators' range of motion. Therefore, we consider that this procedural flexibility has emerged as a possibility obtained at the expense of certainty in international commercial arbitration proceedings. This uncertainty is to such an extent that it also warrants the question as to whether there is an applicable law to take evidence in international commercial arbitration proceedings. Such procedural flexibility afforded to the parties, however, comes at a price of uncertainty with respect to arbitral procedure. International commercial arbitration developed as a reaction to the failings of proceedings in domestic courts, which were subject to detailed rules of evidence. Thus, the consensus in the arbitration community is that party freedom and the procedural flexibility that comes with it are fundamental attributes of arbitration. Although this presumption is theoretically correct; in other words, the parties are indeed able to craft such a procedure that would perfectly fit for adjudication of their disputes, mostly it does not reflect the practical reality. In practice, when parties are negotiating the terms of an agreement to govern their business relationship, they generally tend to avoid discussions as to what will happen if things go wrong. As a matter of fact, according to our practice experiences, when one of the parties' legal counsel tries to address such hypothetical scenarios, the parties generally prefer to suppress such "negative thoughts" and refuse to make in-depth discussions as to how a possible dispute is to be handled. Hereby, this leaves open the question of the procedure to be followed in arbitration proceedings in case of potential disputes. As a result, the provisions on how to resolve disputes that may arise between the parties, in other words, the "dispute resolution" provisions, are left to the very end of the negotiations and passed over in a few sentences. When the relationship between the parties becomes truly strained and a dispute comes to an unavoidable stage, it becomes even less likely that the parties will agree on how to gather evidence on the dispute in question. In a such situation, any suggestions made by one party regarding the procedure for the taking of evidence will be viewed with suspicion by the other party. In an environment of suspicion and animosity, it is often unrealistic to expect productive negotiations to take place on procedural matters. As a result, although the parties have a wide range of motions to make agreements regarding the method of collecting evidence in arbitration proceedings, they are often unable to exercise this authority in practice. As the parties are not exercising their rule-making powers, this important task, which is decisive for the resolution of the dispute, shifts to the arbitrators. Therefore, in our opinion, it would not be a wrong assessment to say that the freedom of the parties has turned into the freedom of the arbitrator in practice. Once appointed, arbitrators have to decide on many issues with respect to the taking of evidence as rules applicable to arbitration are generally silent as to these matters. Although arbitrators have the opportunity to be guided by some non-binding rules, such as the IBA Rules and the Prague Rules, which are considered to be effective and instructive in the arbitration community, they are ultimately left to make their assessments and reach an award based on their judgment. The above-mentioned non-binding rules can undoubtedly assist arbitral tribunals to a certain extent with regard to the taking of evidence. However, it is not possible to say that these rules are enforceable guidelines that can be blindly followed by arbitral tribunals. A closer look at these rules reveals that they leave many issues to the discretion of the arbitral tribunals. Of course, any decision regarding the taking of evidence in international commercial arbitration is already within the discretion of the arbitral tribunals, even in the absence of these rules. Therefore, these provisions, which have been drafted to allow the arbitral tribunals to decide as they see fit, are no more than general guidance on how to exercise their discretion. For these reasons, even if the parties have agreed on the application of these non-binding rules, the fact remains that the collection and evaluation of evidence are still left to the discretion of the arbitral tribunals. This study takes an inductive approach by analyzing the normative and non-binding rules of law applicable to evidence in international commercial arbitration. Firstly, this study examines whether there is a body of rules that can be characterized as the law of evidence in international commercial arbitration. It is determined that there is a law of evidence in international commercial arbitration; however, its content is rather composed of general principles. After determining that these rules have normative value, it is examined how and to what extent these general principles are concretized in terms of the types of evidence used in international commercial arbitration. Although the degree of concretization of these principles varies according to the types of evidence, as a general characteristic, it is determined that arbitral tribunals are left with a very wide discretionary power. It is concluded that arbitral tribunals have a wide latitude of action with respect to the submission of documents, the presentation of witness testimony, the use of expert testimony, the use of discovery and the extent of the res judicata effect of a prior award. Subsequently, the rules on the admissibility and evaluation of evidence are analyzed and it is concluded that the arbitral tribunals have wide discretion in international commercial arbitration, as in other matters relating to evidence and even the discretion regarding the evaluation of evidence is relatively wider. Since it is difficult to review the discretionary power exercised in these matters, it is observed that the arbitral tribunals' decisions on evidentiary issues fall outside the scope of judicial review. This leads to a further blurring of the already grey evidentiary issues in international commercial arbitration proceedings. This is because it is not possible to determine the extent to which the arbitral tribunal has relied on evidence that ostensibly played a role during the proceedings. In the last instance, although the arbitrators' discretionary powers are limited by general principles such as due process and opportunity to be heard, the limits of such discretionary powers are, generally speaking, somewhat blurred as these are general principles. Another issue is that arbitral tribunals are often subject to pressure from the parties when making their decisions on the taking of evidence during the arbitral proceedings. The parties are more interested in being the winner of the concrete proceedings than in the proper conduct of the proceedings in accordance with the law, procedure and rules. In this sense, a party whose request for evidence is likely to be rejected will often argue that the arbitral tribunal's decision violates the principle of a fair trial, even if this is not the case. It is in these circumstances that arbitral tribunals must strike a balance between a fair trial and an efficient trial and make appropriate decisions on evidentiary issues. If arbitral tribunals emphasize procedural efficiency and defer to the parties' presentation of their claims and defences, this may not in itself constitute an obstacle to legally correct decisions. However, this would violate the fundamental procedural safeguards of the participants in the proceedings and may even lead to arbitration proceedings becoming a mechanism for arbitrary and haphazard decision-making. If the opposite approach is taken, in other words, if the priority is to uncover the material truth at all costs and the procedural economy is put on the back burner, this will result in costly and protracted proceedings that will far exceed the limits of reasonableness. Given the limited scope of the guidelines available to arbitrators on the collection and evaluation of evidence, striking this balance is not an easy task. Therefore, it is quite understandable that arbitral tribunals, when deciding on evidentiary issues, may prefer the safer route and give precedence to claims of breach of the principle of a fair trial, even at the expense of the efficiency of the proceedings. Additionally, the confidential nature of the international commercial arbitral proceedings also amplifies the problem. As a result of this principle, the available knowledge as to the practice of arbitration becomes limited to anecdotal stories as to what has happened in certain individual international commercial arbitration proceedings. The arbitrators do not have sufficient opportunity to know about how their colleagues have dealt with certain issues that may have similarities with the issues that they have been trying to solve. In conclusion, in light of the foregoing, since the arbitral tribunals are the rule-makers of arbitration proceedings, the extent to which arbitration proceedings will function correctly and efficiently depends on the experience of the arbitral tribunals and their knowledge of the law, procedure and rules. Basing a correct and efficient arbitration procedure solely on the initiative of experienced arbitrators reduces the 'certainty' of the arbitral procedure. In the face of this situation, it may be tempting to argue that it is inappropriate for arbitrators to have so much freedom and that the rules applicable to arbitral proceedings should be revised to be more detailed. Indeed, there are those who argue that such a change should take place. In the final analysis, a good system should be able to function well regardless of how qualified (or unqualified) its participants are. It is obvious that an argument that sees detailed procedural rules as a remedy for this would contradict the historical development of arbitration and therefore would not be accepted by the international arbitration community. Likewise, from the other side of the coin, it could be argued that detailed procedural rules that are not appropriate to the nature of the individual dispute would prevent qualified and experienced arbitral tribunals from formulating rules that are appropriate to the resolution of the dispute in question, and that the hands of arbitral tribunals may be tied in this way. Although it may be argued that these counter-arguments are equally justified, they do not negate the fact that certainty should be ensured in international commercial arbitration proceedings. Therefore, this suggests that it may be appropriate to resort to alternative methods to ensure certainty. Indeed, it would be a mistake to assume that the only way to achieve certainty is through a detailed set of rules, as we, as legal practitioners in the Continental European legal system, are accustomed to. In the countries subject to the Common Law system, many branches of law do not have such a detailed set of rules and therefore it is not possible to claim that these legal systems lack certainty. Especially in the common law, certainty is provided by case law. If the same logic were to be applied to international commercial arbitration proceedings, it would mean that making information on arbitration proceedings more accessible could help to achieve the goal of certainty. In recent years, there have been some initiatives recognizing the benefits of this approach. While arbitral tribunals are under no obligation to follow the decisions of other arbitral tribunals, having the opportunity to see that there is a consistent pattern of decisions on a particular issue would undoubtedly provide valuable guidance for arbitral tribunals. As the pool of information available to arbitral tribunals and the parties expands, it is obvious that the grey areas regarding evidence in international commercial arbitration will diminish over time. In this way, it will be possible to achieve greater certainty without undermining the fundamental values of the arbitral procedure. Reducing the uncertainty caused by procedural flexibility on procedural certainty in this way will contribute significantly to the development of international commercial arbitration.
Keywords: Arbitrage; Arbitragem; Arbitraje; Arbitration; Delil; Evidence; International Arbitiation Law; Milletlerarası Tahkim Kanunu; Proof (presentation); Tahkim; İbraz (İspat)

Ticari davalarda arabuluculuk - Yildirimoğlu, Hakan (İstanbul Ticaret Üniversitesi, 2023)
Dünya genelinde, uyuşmazlıkların mahkeme dışında alternatif uyuşmazlık çözüm yolları ile çözülmesi konusunda artan bir eğilim bulunmaktadır. Alternatif uyuşmazlık çözüm yollarından biri de arabuluculuktur. Arabuluculuk gönüllülük esasına dayanan bir uyuşmazlık çözme biçimidir. Arabuluculuk sistemi, AB'ye üye bazı ülkeler başta olmak üzere birçok ülkede özellikle ticari uyuşmazlıklarda uygulanmakta ve sonuçları itibariyle tarafları memnun etmekte, yargının yükünün de ciddi şekilde azaltılmasına destek olmaktadır. Yargının iş yükünün hızla arttığı, yargılamadaki gecikmeler nedeniyle adalete duyulan güvenin azaldığı bir ortamda arabuluculuk uygulamaları birçok ülkeye örnek olmaktadır. Ülkemizde de arabuluculuk uygulanmaya başlanmış; hatta en sık karşılaşılan uyuşmazlıklardan iş uyuşmazlıkları, ticari uyuşmazlıklar ve tüketici uyuşmazlıkları dava şartı arabuluculuk kapsamına alınmıştır. Ticari davaların zorunlu arabuluculuk yoluyla çözülmesi uygulamada bazı sorunlara ve çelişkili yargı kararlarının ortaya çıkmasına neden olmuştur. Arabuluculuk, Ticari Davalar, Ticari Davalarda Arabuluculuk, Avrupa Birliği, Zorunlu Arabuluculuk, Alternatif Uyuşmazlık Çözüm Yolları, Dava Şartı Arabuluculuk, Uzlaşma. There is an increasing trend around the world related with the resolution of disputes through alternative dispute resolution methods out of court. One of the alternative dispute resolution methods' is mediation. Mediation is a form of dispute resolution on a voluntary basis. The mediation system is applied especially in commercial disputes in many countries, also in some member countries of European Union. The mediation not only satisfies the parties in terms of its results but also helps to reduce the burden of the judiciary. In a world where the workload of the judiciary increases rapidly and trust in justice decreases due to delays in the trial, commercial mediation practices in European countries set an example for many other countries. Mediation is not also practised in Turkiye but also mandatory in labor disputes, commercial disputes and consumer disputes. Contradiction and discrepancy between the court decisions and other judicial problems arised arised as a result of mandatory mediation. Mediation, Commercial Disputes, Mediation in Commercial Disputes, European Union, Mandatory Mediation, Alternative Dispute Resolution, Condition of Litigation, Commercial Mediation. Reconciliation, Voluntary Mediation
Keywords: Alternate dispute; Alternatif uyuşmazlık; Arabuluculuk; Avrupa Birliği; Commercial cases; Commercial disputes; European Union; Hukuk düzeni; Incompatibility; Judicial decisions; Law order; Mandatory mediation; Mediation; Ticari davalar; Ticari uyuşmazlıklar; Uyuşmazlık; Yargı kararları; Zorunlu arabuluculuk

Multimodal taşıma operatörünün sorumluluğu - Alhan, Yunus (Akdeniz Üniversitesi, 2022)
Multimodal taşıma; multimodal taşıma sözleşmesine binaen multimodal taşıma operatörünün eşyaların bir yerden farklı yerdeki teslimat için belirlenmiş bir noktaya taşınmasını en az iki farklı taşıma türü ile gerçekleştirmeyi taahhüt ettiği bir taşımadır. Konteyner kullanımının yaygınlaşması, günümüzde uluslararası eşya taşımalarının birden fazla taşıma türü kullanılarak kapıdan kapıya şeklinde yapılmasına olanak sağlamıştır. Bu sayede multimodal taşıma tüm dünyada yaygın hale gelmiştir. Taşıma sektöründe sıklıkla kullanılan bu taşıma türünün hukuki açıdan izahı önem arz etmektedir. Bu sebeple, multimodal taşımanın tanımı ve unsurları ele alınmıştır. Bu taşımanın diğer taşıma türleri ile benzerlik ve farklıkları değerlendirilmiştir. Her bir taşıma türüne ilişkin konvansiyonlar, ülkelerin ulusal hukuk düzenlemeleri ve multimodal taşımaya ilişkin yeknesak kurallar oluşturma amacıyla getirilen düzenleme çalışmaları ve düzenlemeler göz önüne alındığında multimodal taşımaya hangi hukuk düzenlemelerinin uygulanacağını öngörmek zordur. Multimodal taşımalarda sorumluluğu yeknesaklaştırmak adına en önemli düzenlemeler 1975 ve 1992 tarihli Milletlerarası Ticaret Odası (ICC) Kuralları ve halen yürürlüğe girmemiş olan 1980 Tarihli Multimodal Taşıma Konvansiyonu (MTC), 2009 tarihinde imzaya açılan Eşyaların Tamamen veya Kısmen Deniz Yoluyla Uluslararası Taşınmasına İlişkin Konvansiyondur (Rotterdam Kuralları-RK). Bu düzenlemelerden esinlenilerek ortaya çıkmış çeşitli bölgesel düzenlemeler söz konusudur. Bunun yanı sıra multimodal taşımanın ülke sınırları içerisinde gerçekleşebilmesi sebebiyle bazı ülkeler bu konuyu düzenleyen kanunlar yapmışlardır. Türk Hukunda ise multimodal taşımaya ilk kez 6102 sayılı Türk Ticaret Kanunu'nda (TTK), 'Değişik Tür Araçlar İle Taşıma' başlığı altında yer verilmiştir. MTO'nun zıya, hasar ve geç teslime dayalı sözleşme kaynaklı sorumluluğu zarar yerinin belirlenebilir olup olmamasına göre farklı kurallara tabidir. Zarar yerinin belirlenmesi ve multimodal taşıma sözleşmesinin taraflarından birinin zararın hangi taşıma türünde oluştuğunu ispatlaması durumunda, multimodal taşıma birden fazla taşıma türünü içerdiğinden denizyolu, havayolu, karayolu, demiryolu ve ülke iç suyolu gibi her bir taşıma türünü ayrı ayrı düzenleyen ve her biri kendi sorumluluk rejimini içeren uluslararası unimodal (tekil) taşıma konvansiyonlarından usulüne göre yürürlüğe girmiş olanları öncelikli olmak üzere, ilgili taşıma türünü özel olarak düzenleyen kurallar uygulanacaktır. Zararın gerçekleştiği taşıma türünün tespit edilememesi durumunda genel hüküm olarak adlandırabileceğimiz TTK hükümleri uygulama alanı bulacaktır. Çalışmada, Türk Hukukunda MTO'nun sorumluluğu ilgili konvansiyonlar ve TTK ışığında ele alınmış, uygulanacak hükümler ortaya konmaya çalışılmıştır. Anahtar Kelimeler: Multimodal Taşıma, Multimodal Taşıma Sözleşmesi, Multimodal Taşıma Operatörü, Multimodal Taşıma Operatörünün Sorumluluğu. Multimodal transport is a carriage in which multimodal transport operator, who assumes the responsibility of performing the carriage under the multimodal transport contract, undertakes to perform the carriage of goods by at least two modes of transport from one place to another place designated for delivery. Widespread use of containers today allows international transport of goods to be in the form of door-to-door transport using more than one mode of transport. Thus, multimodal transport becomes more widespread all over the world. Explaining this mode of transport, which is frequently used in the transport industry, from the legal perspective is of high importance. Hence, in this study, the definition and elements of multimodal transport are studied. The similarities and differences of this mode of transport with other modes of transport are evaluated. Considering different conventions regulating each mode of transport, national transport legislations and regulations aimed at setting forth uniform provisions, it is clearly difficult to determine rules that are applicable for the multimodal transport contract. Major regulations to uniform the liability in multimodal carriages are the 1975 and 1992 International Chamber of Commerce Rules, the 1980 Multimodal Transport Convention (MTC) and the United Nations Convention on Contracts for the International Carriage of Goods Wholly or Partly by Sea (Rotterdam Rules-RT), which was open for signature in 2009. There are also regional regulations inspired by these instruments. In addition, a number of countries enact laws regulating multimodal transport, as multimodal transport may be performed within national boundaries, and there are no uniform rules regulating it. In Turkish law, certain rules on multimodal transport in the Turkish Commercial Law (TTK) No.6102 under the heading of 'Carriage by Various Modes of Transport (Multimodal Transport)' were introduced. The MTO's contractual liability for loss of or damage to goods or delay in delivery is subject to different rules depending on whether the place of loss can be located. If the place of loss is located, and the leg of transport in which the loss occurs is proved by any party of the multimodal transport contract, as the transport involves more than one mode of transport, rules specifically regulating that mode of transport, in particular unimodal conventions, which duly entered into effect, individually governing each mode of transport such as sea, air, road, rail and inland waterway transports and having its own liability regime, will be applicable. If the mode of transport in which the loss occurs cannot be ascertained, TTK provisions, which we may call general rules, will be applicable. In the present study, we analyse the liability of MTO within the framework of relevant conventions and TTK and seek to reveal applicable provisions. Keywords: Multimodal Transport, Multimodal Transport Contract Multimodal Transport Operator, Liability of Multimodal Transport Operator
Keywords: Carrier's responsibility; Contract of carriage; Multimodal taşımacılık; Multimodal transport; Taşıma sorumluluğu; Taşıma sözleşmesi; Taşımacılık; Transportation; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

İslam borçlar hukuku açısından ticari ihtilafların çözümünde 'Arabuluculuk' - Almasri, Raed (Ankara Üniversitesi, 2022)
Bu tez, anlaşmazlıkları çözmede arabuluculuk konusunu ele almaktadır. Arabuluculuk konusu ticari mali muamelelerdeki anlaşmazlıklar ile sınırlıdır. Dolayısıyla tez ailevi anlaşmazlıklardaki nafaka gibi diğer mali anlaşmazlıklara değinmemektedir. Tez konusu fıkhi açıdan ele alındığı için, dört fıkhi mezhebin konuyla ilgili görüşleri, mukayeseli olarak işlenmiş, mezhepler arasında ihtilaf ve ittifak edilen noktalar ele alınmış ve görüşler arasında tercih yapılarak ortaya konulmuştur. Tez; bir mukaddime, üç bölüm, bir sonuç ve kaynakçadan meydana gelmektedir. Mukaddime de tezin planı, fihrist ve içerik ele alınmıştır. Tezin birinci bölümünde; arabuluculuk kavramının tanımı ve meşruiyeti, ikinci bölümde; arabuluculuğun rükünleri ve arabuluculukla ilgili hükümler ve şartlar, üçüncü bölümde ise; arabuluculuğun sonuçları ve etkisi ele alınmıştır. The dissertation aims to cover the subject of mediation in dispute resolutions exclusively in commercial disputes. Therefore, the research does not cover mediation in other disputes such as domestic disputes even when it's related to financial matters such as alimony. The research also studies mediation in commercial disputes from a jurisprudential perspective. Hence the jurists' opinions are presented and analyzed in a comparative approach to show its similarities, differences and present a jurisprudential preference. The dissertation is presented in an introduction, three chapters, a conclusion followed by the list of references and resources. The introduction provides an insight into the research contents and methodology. The first chapter discuss the definition of mediations and its legitimacy. The second chapter tackle the main pillars of mediations and clarify its ruling and conditions. Finally, the third chapter view the results of mediations and its expected impacts.
Keywords: Arabuluculuk; Borçlar hukuku; Commercial disputes; Incompatibility; Islamic law; Law of obligations; Mediation; Ticari uyuşmazlıklar; Uyuşmazlık; İslam hukuku

Navlun sözleşmesinde gönderilenin sorumluluğu - Arslan, Zeynep (Kocaeli Üniversitesi, 2022)
Deniz ticaret hukukunda, varma limanında yükün teslimini talep eden kişi, gönderilen olarak tanımlanmaktadır. Gönderilen, navlun sözleşmesinin tarafı olan taşıtan olabileceği gibi sözleşme ilişkisi dışında üçüncü bir kişi de olabilir. Gönderilenin üçüncü kişi olması hâlinde navlun sözleşmesi üçüncü kişi yararına sözleşme olarak nitelendirilmektedir. Kanun koyucu, sözleşme ilişkisine taraf olmayan bu üçüncü kişi için de bir takım hak ve sorumluluklar getirmiştir. İşte bu çalışmanın konusunu üçüncü kişi sıfatını haiz gönderilenin navlun sözleşmesinden kaynaklanan sorumluluğu oluşturmaktadır. Sözleşmelerin nispiliği prensibi gereği kural olarak tarafların anlaşarak üçüncü kişiyi borç altına sokmaları mümkün değildir. Bununla birlikte üçüncü kişi gönderilenin hangi hallerde sorumlu olacağı TTK m. 1203'te düzenlenmiştir. Buna göre gönderilenin navlun sözleşmesi kapsamında sorumlu olması için ilk olarak eşyanın teslimini talep etmesi gerekmektedir. Eşyanın teslimini talep, üçüncü kişi lehine sözleşme teorisi açısından edimin kabulü olarak değerlendirilmekte ve haliyle gönderilenin borç altına girmesi tarafların kararlaştırması ile değil öncelikle kendi iradesi ile olmaktadır. Gönderilenin sorumlu tutulmasının diğer şartını, teslim talebinin dayandığı taşıma sözleşmesinde ya da deniz taşıma senetlerinde bu borçların gönderilen üzerine bırakılması oluşturmaktadır. Dolayısıyla gönderilenin yükün teslimi sözleşmeden ya da deniz taşıma senetlerinden kaynaklanan bu alacakların ödenmesi şartına bağlanmaktadır. Gönderilenin hangi alacaklardan sorumlu olduğu sözleşme şartlarına göre tespit edilmektedir. Bu kapsamda sözleşme kayıtlarının incelenmesi gerekir. Navlun sözleşmesinde gönderilen uygulamada genellikle denizaşırı alıcı olarak karşımıza çıkmaktadır. Dolayısıyla Incoterms uyarınca tarafların kararlaştırdığı teslim şekillerinin ve FIO/FIOST/FILO/LIFO gibi gönderilenin sorumluluğunu genişleten kayıtların incelenmesi önemlidir. Bu kapsamda gönderilenin navlun sözleşmesinden kaynaklanan hangi borç kalemlerinden sorumlu olduğu sözleşme hükümleri ve mevzuat ile ayrıntılı bir şekilde açıklanmıştır. The consignee is defined as a person who requesting the delivery of the cargo at the discharge port by the maritime commercial law. The consignee might be the shipper, as a party of contract of affreightment, or might be a third party of the contract. In the case of the consignee is a third party, the contract of affreightment is characterized as a third-party beneficiary contract in which determined rights and responsibilities are given to this third party by the law makers. This thesis aims to determine the responsibilities of the third-party consignee that arising from the contract of affreightment. With regard to privity of the contract principle, as a rule, parties of a contract do not have right to bind a third party with obligations. On the other hand, the conditions of responsibilities of the third party consignee is regulated in the article 1203 of TCC. With regard to the article, in order for the consignee to be liable under the freight contract, the consignee must first request the delivery of the goods. The demand for the delivery of the goods is considered as the acceptance of the performance in terms of the theory of third party beneficiary contract and as a matter of fact, the consignee do not incur a debt with the parties' decision, but primarily with his own will. The other condition of holding the consignee responsible is the transfer of these debts to the consignee in the contract of affreightment or other transport documents on which the delivery request is based. Therefore, the delivery of the cargo is subject to the payment of these debts arising from the contract or transport documents. The debts of the consignee are determined according to the terms of the contract. In this context, it is necessary to review of the terms of the contract. In practice, the consignee in the contract of affreightment usually appears as a overseas receiver of the sale contract. Therefore, it is important to examine both the delivery methods agreed by the parties with regard to INCOTERMS and clauses that expand the responsibility of the sender, such as FIO/FIOST/FILO/LIFO. In this framework, this study explains in detail the responsibilities of consignee with regard to freight contract provisions and legislations.
Keywords: Commercial law; Contracts of affreightments; Deniz hukuku; Droit maritime; Freight; Gönderenin sorumluluğu; Law of the sea; Navlun; Navlun sözleşmeleri; Responsibility; Responsibility attiribution; Senders responsibility; Sorumluluk; Sorumluluk yükleme; Sözleşmeler; Ticaret hukuku

Şirketler hukukunun geleceği üzerine bir inceleme: Şirket yönetiminde yapay zekâ - Bora Çinar, Sevda (Akdeniz Üniversitesi, 2022)
Yapay zekâ teknolojileri, insan unsurunun egemen olduğu pek çok alanı etkisi altına almaya hazırlanmaktadır. Bu alanlar arasında tıp, hukuk, eğitim, mühendislik olduğu gibi ticaret de bulunmaktadır. Yapay zekâ teknolojileri, özellikle şirketler hukukunun geleneksel yapısını kökünden sarsacak yeni bir ticari düzen ve anlayış yaratma yolundadır. Karar alma süreçlerini otomatikleştiren yapay zekâ teknolojilerinin verimliliği ve hızı, şirketlerin bu sistemleri geliştirerek pazarlamalarının yanı sıra bizzat şirket bünyelerine katarak kullanma eğilimi göstermelerine de yol açmaktadır. Bu şekilde kendi kendini besleyen bu döngü, yapay zekâ alanına sermaye yapısı güçlü şirketlerin yönelmesini ve araştırma kapsamının gittikçe genişletilmesini sağlamaktadır. Şirketlerdeki bu yönelim neticesinde, hızla gelişen yapay zekâ teknolojilerinin geleneksel şirket yapılarını etkileyebilme potansiyelinin yükselmesi olgusu, şirketler hukukunun geleceği üzerine bir inceleme yapılması gerekliliğini ortaya çıkarmaktadır. Çalışmamızda şirket yönetiminde yapay zekâ teknolojilerinin kullanımına ve bunun hukuki sonuçlarına odaklanılmakta ve konu dört temel bölüme ayrılarak incelenmektedir. Giriş bölümünde kısaca çalışmanın konusu, önemi, amacı, kapsamı ve sistematiği açıklanmakta, yapay zekâ ve şirket yönetiminin kavramsal çerçevesine yer verilmektedir. Birinci bölümde şirketler hukuku ve yapay zekâ teknolojilerinin etkileşimi incelenmektedir. Bu bölümde yapay zekâ teknolojilerinin ticaret hukuku ve şirketler hukuku ile etkileşimi incelenmekte, dijitalleşmenin şirketler hukukuna etkileri, özellikle şirket yapılarındaki ve menfaat çatışmalarındaki dönüşüm çerçevesinde ele alınmaktadır. İkinci bölümde, şirket yönetiminde yapay zekâ teknolojilerinin kullanılması bir süreç olarak incelenmektedir. Kullanım kararı alınmasından başlamak üzere, şirkete uygun yapay zekâ teknolojilerinin edinimi ve bu teknolojilerinin şirket yönetiminde kullanılma yöntemlerinin araştırıldığı bu bölümde, teknik, hukuki ve ticari başta olmak üzere ilgili beklenti ve belirsizlikler araştırılmaktadır. Üçüncü bölümde şirket yönetiminde yapay zekâ teknolojilerinin kullanılmasının hukuki sonuçları ve hukukun bu dönüşümden nasıl etkileneceği üzerinde durulmaktadır. Son bölümde ise yönetimin geleceği üzerine düşüncelerin yer altığı bir karar ağacı tasarımı içeren interaktif bir bölüme yer verilmektedir. Artificial intelligence technologies are preparing to influence many human-dominated and human-related fields. These fields include medicine, law, education, engineering as well as commerce. Artificial intelligence technologies are on the way to create a new commercial order and understanding that will shake up the traditional structure of corporate law. In particular, the efficiency and speed of artificial intelligence technologies that automate decision-making processes have led companies to tend to use these systems both by developing and marketing them and by incorporating them. In this way, this self-sustaining cycle has led companies with strong capital structures to move towards the field of artificial intelligence, and the scope of research has been gradually expanded. This orientation in companies and the high potential of rapidly developing artificial intelligence technologies to affect traditional company structures have revealed the necessity of conducting an examination on the future of company law. Our study focuses on the use of artificial intelligence technologies in company management and its legal consequences, and the subject is examined under four main sections. In the introduction, the subject, importance, purpose, scope and systematics of the study are briefly explained, and the conceptual framework of artificial intelligence and company management is given. In the first part, the interaction of corporate law and artificial intelligence technologies is examined. In this section, the interaction of artificial intelligence technologies with commercial law and company law is examined, the effects of digitalization on corporate law are discussed, especially within the framework of the transformation in company structures and conflicts of interest. In the second part, the use of artificial intelligence technologies in company management is examined as a process. In this section, where the acquisition of artificial intelligence technologies suitable for the company and the methods of using these technologies in company management are investigated, starting from the decision to use, all technical, legal and commercial expectations and uncertainties are investigated. The third chapter focuses on the legal consequences of the use of artificial intelligence technologies in company management and how the law will be affected by this transformation. In the last part, there is an interactive section that includes a decision tree design with thoughts on the future of management.
Keywords: AI; Anonim şirketler; Artificial Intelligence; Bilgi ve belge yönetimi; Bilgi yönetim sistemi; Bilgi yönetimi; Capital companies; Commercial companies; Financial data management system; Finansal veri yönetim sistemi; Hukuki sorumluluk; Information and records management; Information management; Information management system; Institutional responsibility; Inteligência artificial; Intelligence Artificielle; Joint stock company; Kurumsal sorumluluk; Legal responsibility; Sermaye şirketleri; Ticari şirketler; Yapay zeka

Ticari işletmenin devri - Cerenoğluak, Ceren (Yeditepe Üniversitesi, 2022)
Ticari hayatın gerekleri, ticari işletmelerin faaliyetlerini devam ettiren bir organizasyon bütünü olarak devredilebilmesi ihtiyacını doğurmaktadır. Tüzel kişilik tanınmamış ve hukuk süjesi sayılmamış olan ticari işletmeyi ilgilendiren malvarlığının, hukuki işlemlere konu olması ve özellikle devri bakımından özel bir hukuki rejim öngörülmüştür. Bunun için, Türk Ticaret Kanunu'nun 11/3 fıkrasında düzenlenen şekil ve koşullara uyularak, ticari işletmenin devri gerçekleştirilebilir. 1 Temmuz 2012 tarihinde yürürlüğe giren 6102 sayılı Türk Ticaret Kanunu 11. maddesi ile ticari işletmenin devri sözleşmesinin ve de ticari işletmeyi bir tütün halinde konu alan diğer sözleşmelerin yazılı olarak yapılacağı belirtilerek yazılı şekil şartı ilk kez hukukumuza getirilmiştir. Bununla birlikte, yeni Ticaret Kanunumuz, ticari işletmenin devri prosedürünü kolaylaştırmak adına tescilsiz kazanım öngörmekte ve de aktif unsurların devri için genel hükümlerin gerektirdiği kurucu işlemlerin yapılmasına gerek olmadan devrin gerçekleşeceğini düzenlemektedir. Bu düzenlemenin sicile güven ilkesi açısından neticeleri ve doğura bileceği hukuki sakıncalar tezimizde incelenmiştir. The requirements of commercial life may create the need to transfer the commercial enterprises as a whole organization that continues its activities. A special legal regime has been foreseen for assets of business, which is not recognised as a legal entity, to be subject to transactions, particularly to assignment. For this purpose, the transfer of a commercial enterprise is to be carried out in compliance with the forms and conditions set out in article 11/3 of the Turkish Commercial Code. The written form condition for the transfer of the commercial enterprise agreements and the other agreements in relation to the commercial enterprise has firstly regulated under the Article 11 of the Turkish Commercial Code numbered 6102, has entered in to ferce on July 1, 2012. In addition to this, in order to facilitate the transfer of the commercial enterprise procedure, New Commercial Code stipulates the acquisition without registration officially and transfers of the assets without performing the transaction required by the general provision. The results and legal inconveniency of the said regulation with respect to the believe in registration principle will be discussed in our thesis.
Keywords: Commercial institutes; Contracts; Devir; Kanunlar 6102 sayılı; Laws 6102 numbered; Sözleşmeler; Ticari işletmeler; Transfer of enterprise; Turkish Commercial Code; Turkish commercial law; Turnover; Türk Ticaret Kanunu; Türk ticaret hukuku; İşletmenin devri

Yönetim kurulu üyelerinin şahsî sorumluluğuna ilişkin davalarda maddî hukukun usûl hukukuyla etkileşimi - Eski̇ocak, Ali (Galatasaray Üniversitesi, 2022)
Les membres du conseil d'administration, qui sont l'organe représentatif et exécutif de la société anonyme, sont investis de pouvoirs et d'attributions étendus à tous les stades de leur activité (Code de Commerce turc art. 365, art. 374). En cas de perte résultant de la violation de ces obligations, il est inévitable que la responsabilité soit mise en avant. Ceci est principalement une conséquence naturelle de la règle générale de "l'équilibre autorité-responsabilité". Dans ce contexte, l'existence et l'effectivité des actions en responsabilité ont un rôle dissuasif pour que les administrateurs ne manquent pas à leurs obligations. D'autre part, en raison du principe de la responsabilité limitée avec les actifs contre les créanciers de la société anonyme (Code de Commerce turc art. 329/1), la protection des actifs est importante pour empêcher les créanciers de subir des pertes. De plus, la question de la responsabilité revêt une importance particulière au regard des principes de gouvernance d'entreprise. Parce que la comptabilité et la responsabilité sont les éléments clés du principe de gouvernance d'entreprise dans les sociétés anonymes qui sont les acteurs les plus importants de la vie économique d'aujourd'hui. Par conséquent, des réglementations détaillées prises en vertu du Code de Commerce turc concernant les obligations et les responsabilités des membres du conseil d'administration; en outre, les dispositions relatives aux poursuites en responsabilité ont été réglementées de manière plus détaillée et systématique et des changements importants ont également été introduits à cet égard. Dans ce cadre, un régime de responsabilité spéciale a été institué pour les administrateurs en dehors des dispositions de responsabilité générale, tandis que les articles 549 à 552 du Code de Commerce turc réglementent la responsabilité spéciale, l'article 553 et les articles suivants du Code de Commerce turc réglementent les dispositions relatives à la responsabilité générale. Ces articles sont relativement larges et complets par rapport à l'ancien code. Diverses études monographiques ont été réalisées en matière de responsabilité juridique des membres du conseil d'administration et ce sujet a été largement examiné dans les travaux sur le droit des sociétés anonymes. Cependant, l'aspect droit matériel de la responsabilité juridique a été principalement examiné dans la doctrine mais les questions liées aux actions en responsabilité et l'aspect procédurale de l'action ont trouvé une place limitée dans la doctrine. Les expressions similaires sont souvent utilisées concernant la nature du droit d'action des actionnaires et créanciers, mais l'aspect procédurale n'est généralement pas examiné avec une explication détaillée, des analyses et une caractérisation. Cependant, cette question est étroitement liée à des questions importantes telles que la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement et les caractéristiques des défenses. Dans notre étude, en raison de l'importance des actions en responsabilité et de l'augmentation du nombre des actions en pratique, nous essayons d'expliquer les caractéristiques de l'action en responsabilité (l'aspect procédural) ainsi que l'aspect du droit matériel. Cependant, notre étude n'est pas une thèse de procédure civile, c'est une thèse de droit matériel et il vise à examiner les questions liées au droit procédural en commençant par la nature de la responsabilité, l'engagement de l'action jusqu'à l'exécution du jugement définitif rendu. En conséquence, le sujet de notre étude est de décrire l'aspect de droit substantiel de l'action en responsabilité et d'examiner les domaines où la responsabilité des membres du conseil d'administration intersecter avec le droit procédural. Donc l'objectif de cette étude est l'aspect de droit substantiel de la responsabilité. Les problèmes procéduraux sont examinés dans cette perspective. La responsabilité civile des membres du conseil d'administration a été examiné conformément à l'article 553 et les dispositions suivantes. L'analyse a été faite pour les personnes qui ont le droit d'action avant la déclaration de faillite, mais pas pour les autres qui ont le droit d'action après la déclaration de faillite (administration de la faillite, créanciers). La responsabilité des membres du conseil d'administration et des dirigeants a été prise en considération. Par ailleurs, la responsabilité résultant de la fondation, les cas particuliers de responsabilité régis par l'article 549 et suivants du Code de Commerce turc, la responsabilité de contrôleur qui est régie par l'article 554 du Code de Commerce turc, l'action particulière en responsabilité régie par l'article 193 du Code de Commerce turc, l'action en responsabilité à l'égard d'un groupe de sociétés régi par l'article 202 et les dispositions suivantes du Code de Commerce turc et la révocation des personnes responsables entre elles selon leurs relations internes (action en révocation) sont exclues du champ de cette étude. Notre étude, préparée dans ce contexte, se compose de cinq grandes parties, dans la première partie, les principes de l'aspect droit matériel de l'action en responsabilité ont été examinés. Dans ce cadre, les réglementations légales antérieures et nouvelles en matière de responsabilité, les innovations apportées par la Code de Commerce turc, la base juridique (la source), le but, l'objet, l'intérêt qu'elle protège, ses éléments, sa relation avec divers actions et institutions et ses caractéristiques sont important. La source de responsabilité est basée sur la relation contractuelle entre les membres du conseil d'administration et la société, et les éléments de responsabilité sont l'illégalité, le dommage, le lien de causalité et la faute. La responsabilité des membres du conseil d'administration appartient à l'organe de gestion, est personnelle et fondée sur la faute. Sur cette note, la présomption de responsabilité a été révoquée et le fardeau de la preuve repose sur le demandeur. Alors que le principe de solidarité différenciée a été inclus dans l'article 557 du Code de Commerce turc, il a été mis l'accent sur l'application des dispositions de relation de causalité ainsi que les articles 51-52 du Code des Obligations turc. En ce qui concerne le devoir de diligence, la méthode de référence indirecte au devoir de diligence de l'employé qui était régie par l'article 320 du précédent Code de Commerce a été abandonnée par l'article 369 du Code de Commerce turc, et le devoir de diligence a acquis l'objectivité par l'adoption de « business judgement rule (agir avec diligence, bonne foi et loyauté en decision de gestion)». En outre, dans l'exposé des motifs de l'article, il a été clairement indiqué que le critère de prudence sont pertinents avec la « business judgement rule» Le devoir de diligence est lié à des éléments d'« illégalité » et de « faute ». Par conséquent, cet article signifie l'objectivation de la faute. De ce fait, la frontière entre les éléments d'illégalité et de faute est devenue encore plus incertaine. La délégation de gestion (art.367 du Code de Commerce turc) est une situation qui a un impact sur la responsabilité, avec une délégation valable il y aurait partage responsabilité primaire - responsabilité de surveillance (art. 553/2 du Code de Commerce turc). La nouvelle règle, régie par l'article 557/2 du Code de Commerce turc qui prévoit qu'une action en justice peut être intentée pour l'ensemble du dommage et qu'il peut être demandé au juge de déterminer l'indemnisation de chaque défendeur dans une même action en justice, est importante pour fixer qu'il n'est pas nécessaire que le demandeur tienne compte du principe de solidarité différenciée, et que ce principe est une règle qui ne s'adresse qu'au juge et à la décision qu'il établira. Dans la deuxième partie, les caractéristiques du droit d'intenter une action en responsabilité, les parties de l'action et les modalités d'exercice du droit d'action sont discutées. La caractéristique du droit d'action qui pourrait être exercé par d'autres personnes que la société est importante. Le résultat est étroitement liée aux questions critiques telles que les défenses qui pourraient être invoquées par les défendeurs, et avec quelles défenses pourraient être invoquées contre quel demandeur, la relation entre les demandeurs, la litispendance, le jugement définitif, l'exécution du jugement. Après une évaluation détaillée, notre opinion est que les actionnaires et les créanciers ont chacun individuellement un droit substantiel d'engager une action en responsabilité. En outre, la manière d'exercer le droit de la demande réglementé par la loi est également importante. Étant donné qu'il n'y a pas de disposition ou de déclaration restrictive dans la loi concernant la manière de demande du dommage de l'entreprise, il est également possible d'appliquer tous les recours disponibles en vertu du droit de la procédure civile, de l'exécution et de la faillite. Il est possible de demander des mesures provisoires. Bien qu'il existe une réglementation générale quant aux parties à l'action en responsabilité dans la loi, il est important d'examiner ce sujet. A cet égard, l'action intentée par l'actionnaire avant la faillite n'est soumise à aucune condition. Le montant (ratio) de l'action (la part) n'est pas important. En ce qui concerne le défendeur, les défendeurs sont comptés dans la loi. A ce propos, il est important de déterminer qui entrera dans le champ d'application du concept de « dirigeants», qui est réglementé pour être responsable aux côtés des membres du conseil d'administration. La position des personnes qui ont le droit d'action peut varier selon les avis sur la caractéristique du droit d'action. A notre avis, il n'y a pas d'obstacle légal au dépôt d'actions en responsabilité distinctes par des personnes ayant droit d'action, et cette situation ne constitue pas une litispendance. Dans la troisième partie de notre étude, les instruments de défense relatifs aux actions en responsabilité et à la question de la preuve sont abordés. Les moyens de défense sont importants en ce qui concerne l'instance pendante, la détermination de l'existence des éléments de responsabilité et le calcul du montant de l'indemnité. Parmi les conditions d'action, en tant que moyens de défense en matière de droit procédural, la décision de l'assemblée générale et l'intérêt à agir revêtent une importance particulière. À notre avis la décision de l'assemblée générale devait être recherchée comme condition d'action. En outre, bien que l'intérêt à agir soit une condition générale d'action, il prend plus d'importance pour le cette étude, car dans les actions en responsabilité l'événement qui constitue une violation de l'interdiction de l'abus de droit (art. 2 Code Civil turc). En outre, l'adoption du principe de solidarité différenciée a accru l'importance des motifs de défense individuels. Les motifs matériels de la défense peuvent être très divers, tels que le fait de ne pas être investi d'un organe de gestion, la libération, la prescription, la forclusion, l'exécution du devoir de diligence et la délégation de pouvoir. De plus, comme dans tous les procès, la question de la preuve est également très importante dans les actions en responsabilité. Cependant, un système de preuve spécial et une méthode de preuve n'ont pas été prévus en termes des actions en responsabilité. Par conséquent, des questions telles que la charge de la preuve, l'objet de la preuve, l'échelle de la preuve et les preuves propres doivent être déterminées en tenant compte des caractéristiques spécifiques de l'action en responsabilité, et cela a été examiné dans ce cadre dans notre étude. Dans le quatrième chapitre, le déroulement du procès, le jugement et l'exécution du jugement sont expliqués. En particulier, l'accent mis sur le lien de causalité et l'acceptation du principe de solidarité différenciée avec de nouvelles dispositions obligent le juge à procéder à un examen précis. Dans ce contexte, des questions telles que l'impossibilité du contrôle d'opportunité, la mise en œuvre du principe de solidarité différenciée et la prise en compte de la situation des responsables, qui ne sont pas parties au procès, sont les aspects originaux de la procédure. L'effet du jugement à la fin de l'action est également un sujet discuté dans la doctrine. À notre avis, le jugement ne constituera pas res iudicata (l'autorité de la chose jugée) pour les autres actions en responsabilité et les actions en révocation. Cependant, il convient de noter que l'effet de l'intervention en cas de dénonciation d'instance et d'intervention accessoire, pourrait être important en termes d'action en révocation, et de fait, il peut avoir un effet plus important que res iudicata. Une autre question importante est celle de savoir qui a le pouvoir d'exécuter le jugement et les possibilités dans cette question. Le point le plus prénant ici est que le droit de réclamation de l'actionnaire (le demandeur) comprend le pouvoir d'exécuter le jugement, mais le paiement perçu au stade de l'exécution doit être versée à la société. Dans le cinquième chapitre, quelques situations particulières liées aux actions en responsabilité sont examinées. Dans ce contexte, il a été analysé que l'effet du recouvrement partiel ou total du dommage sur les autres parties responsables dans le cadre de diverses possibilités, la transaction et le désistement d'action (la validité et caractère obligatoire), l'examen de la libération d'une ou plusieurs des personnes responsables au sens de l'article 166/3 du Code des obligations turc, la pertinence de la révocation dans le cadre de l'action en responsabilité et les opérations collusoires de l'entreprise dans le cadre de l'action en responsabilité. Notre avis a été indiqué en conjonction avec l'analyse des arguments de la doctrine et de la pratique sur ces questions.
Keywords: Borçlar hukuku; Cases; Davalar; Faulty liability; Hukuki sorumluluk; Kusurlu sorumluluk; Law of obligations; Legal responsibility; Maddi hukuk; Members of the board directors; Procedural law; Responsibility; Sorumluluk; Substantive law; Turkish Commercial Code; Türk Ticaret Kanunu; Usul hukuku; Yönetim kurulu üyeleri

Anonim ortaklıkta yönetim kurulu üyesinin rekabet yasağı - Günaydin Gülteki̇n, Burcu (Galatasaray Üniversitesi, 2022)
This subject matter of this work is the prohibition of competition with the company of members of board of directors in joint stock companies under art. 396 of the Turkish Commercial Code. The prohibition of competition is a limitation on the commercial activities and the freedom of competition of a restricted party who has access to information, means or resources due to the legal relationship between parties which grant the restricted party a leverage in competition with the other. The core idea underlying the prohibition of competition is the necessity to protect the party benefiting from this prohibition against competitive activities of the restricted party. The prohibition of competition bans the restricted party from establishing competition with the party benefiting from the prohibition through competitive actions, ultimately from becoming the competitor of the beneficiary. The said competition relationship will occur in the event the services or products serving the same or similar needs are provided to the entirety or part of the same customers or customer group. Board members in joint stock company, having the prevailing right of access to all information and resources of the company leads to the risk that it may use this power for its own or other parties' benefit instead of that of the company. Hence, the prohibition of competition on board members regulated under article 396 of the Turkish Commercial Code is one of the concrete examples of the duty of loyalty of a board member towards the company aiming to prevent such usages prioritizing the benefit of the member or of a third person over that of the company. The focal point of this work is the determination of the scope of application and conditions of this prohibition as a whole. The first chapter of this thesis aims to convey the conceptual basis of the prohibition of competition. In this scope, we first assessed the economic and legal basis of competition. Economic competition is the race/competition of two or more market actors in a specific market in order to engage in a transaction with its counterparty in the market through offering better prices, conditions, goods or services in order to be superior from its competitors. However, the intention to supersede its competitors and the efforts for this purpose may result in the misuse of the right to compete or in an act limiting or eliminating the competitive environment. The Republic of Turkey provides for a constitutional protection over a person's right to engage in commercial activities and, although not expressly regulated, right to compete. However, as is the case for all rights and liberties, the right and liberty to compete cannot be exercised without any limitation. Second, the scope of the prohibition of competition is assessed. In this regard, we tried to determine the elements of the prohibition of competition, its definition, and its legal categorization. Moreover, a comparison of the prohibition of competition with the provisions governing unjust competition aiming to establish honest and undisrupted competition as well as with the rules of Competition Law aiming to prevent disruption of competition through restrictive actions is provided in order to specify the prominent characteristics of the prohibition of competition. Third, the attributes of the provisions governing the prohibition of competition are assessed. Provisions governing prohibition of competition which do not relate to the public order but to the internal relations of parties, and which serve the personal benefit of the beneficiary, are not of a peremptory nature. The prohibition of competition, which materially limits the liberty of engaging in commercial activities protected under the constitutional law, is of an exceptional nature and hence the provisions governing the prohibition of competition need to be construed in a limited manner. Fourth, the prohibition of competition can be regulated in the letter of a contract through mutual agreement thereon by its parties, or the legislator occasionally provides for a legal provision governing the prohibition of competition by attributing a special importance to this prohibition with respect to a specific relationship between the parties. Last, in this first chapter, we identify the reflections of this prohibition of competition within the scope of the Law of Obligations, and the Law of Corporations. The second chapter of this work takes into consideration the reasons of regulating a prohibition of competition on board members, and its scope of application regarding the persons concerned. In this context we first broadly assessed the position of the board of directors, board members and affiliated commercial auxiliaries in a company. Then, the legislative provisions respectively of German Law, Swiss Law and Turkish Law governing the board members' prohibition of competition are specified. While in German Law, just as is the case in Turkish law, the prohibition of competition of board members is stipulated in § 88 of the German Stock Corporation Act, the Swiss Law does not regulate this prohibition of competition of board members with a statutory provision, nonetheless, this prohibition is accepted by the scholars. Thereafter, the reason for regulating the prohibition of competition of board members is assessed. In this scope, the duty of loyalty of a board member arises from the legal relationship between the member and the corporation being based on the principle of trust. The member must refrain from conflicting its interests with the interests of the corporation, in other words, from conflict of interests, due to its duty of loyalty. When the member engages in competition with the company, the interests of the company and the board member conflict with each other. The member is in a considerably advantageous position in this conflict compared to the company, due to the information and resources to which it has access thanks to its position within the company. For this reason, the duty of loyalty aiming to prevent the conflict of interest between the company and the member lies at the basis of the board member's prohibition of competition. Lastly, in this chapter, the persons subject to the prohibition of competition pursuant to article 396 of the Turkish Commercial Code are identified. In this respect, the members of the board of directors as well as persons to whom management authorities are delegated fall within the scope of the ratione personae of article 396 of the Turkish Commercial Code. The commercial representatives and commercial proxies of a company are prohibited from competition pursuant to the prohibition of competition regarding commercial auxiliaries pursuant to article 553 of the Turkish Code of Obligations. Whereas a shareholder is not subject to the prohibition of competition with the company; this prohibition may only be regulated by a contract subject to the Law of Obligations. Furthermore, when evaluating the prohibition of competition of shareholders, whether the shareholder has a duty of loyalty to the company has been assessed under German Law, Swiss Law and Turkish Law. The third chapter of this work sets forth the scope of application of the prohibition of competition of board members with respect to its subject matter, place, and time. In order for a board member to violate the prohibition of competition with the company, the member must engage in an activity competing with the company. Pursuant to the first paragraph of article 396 of the Turkish Commercial Code, two types of competitive actions of board members are banned. The first type is the member engaging in an action which is a commercial transaction that falls within the scope of the field of activity of the company, on behalf of itself or a third party. Accordingly, all kinds of acts and actions of the member realized on behalf of itself or third parties which fall within the scope of activity of the corporation would constitute the breach of the prohibition. The scope of this prohibition also encompasses joining the managing body of another corporation. Furthermore, depending on the specifics of a concrete case, the same member being an employee of a competitor corporation under a service contract, or providing consultancy services or extending facilities to a competitor, or benefiting from a job opportunity which belonged to the company may also be construed to be within the scope of the prohibition of competition. The second type is the member being engaged as a partner with unlimited liability in a corporation engaging in the same types of commercial activities. In this regard, if a member becomes a partner of an ordinary partnership or a collective corporation, or a partner with unlimited liability of a commandite corporation, which engages in activities that fall within the scope of activities of the joint stock company, the prohibition will be breached. The prohibition of competition of the board member with the company may be lifted by an authorization granted by the general assembly pursuant to article 396 of the Turkish Commercial Code. This permission to compete to be granted to a board member may be in the form of a prior approval or a later acknowledgement (ratification), in an expressed or implied manner. As a result of the member being permitted to compete, article 396 of the Turkish Commercial Code will no longer apply even if the member engages in activities in competition with the company. The prohibition to compete of the board member lasts for the duration of the board membership. Once the membership ends, the parties must conclude an agreement in order to continue the prohibition of competition. The said agreement regarding the prohibition of competition will be subject to form requirements to be valid. Pursuant to the liberty of contract inherent in the Law of Obligations, the parties may freely execute an agreement regarding the prohibition of competition, provided they comply with the provisions in paragraph 2 of article 23 of the Civil Code or article 26 and first paragraph of article 27 of the Turkish Commercial Code. The prohibition to compete of board members is valid as long as they execute the activities of the company, and within the geography where the clientele of the corporation is located. The fourth and last chapter of this work is devoted to the consequences of breach of the prohibition to compete by a board member. If a member of the board of directors violates this prohibition, the consequence of this breach is regulated in the first paragraph of art. 396 of the Turkish Commercial Code. Accordingly, the joint stock company is granted with certain elective rights. Such that, primarily the company may request compensation from the member in breach of the prohibition of competition. Second, it may be requested that the transaction is deemed concluded on behalf of the joint stock company, third, that the benefits arising from the agreement the member concludes on behalf of third parties belong to the joint stock company. In its request for compensation, the joint stock company must prove the action of the board member violating the prohibition of competition, that the corporation suffered losses from this activity, and the causal link between this activity and the loss of the company. In its request for the transaction to be deemed concluded on its behalf, the company requests for the economic consequences of the transactions the member concluded in violation of the prohibition of competition on its behalf. In its request for the benefits arising from the agreement, the company requests that benefits arising from the agreement the member concluded on behalf of third parties are left to itself. At this point, we materially benefited from the German doctrine and jurisprudence in explaining the claims requesting that a transaction is deemed concluded on behalf of the company and that the benefits from the transactions are left to the company. These rights granted in the first paragraph of article 396 of the Turkish Commercial Code are not cumulative but elective. Pursuant to the second paragraph of article 396 of the Turkish Commercial Code, the authority to chose one of the elective rights granted to the company belongs to the members of the board of directors, excluding the member having violated the prohibition of competition. The third paragraph of article 396 of the Turkish Commercial Code regulates a dual prescription period of three months and one year. These periods are with respect to the exercise by the company of its elective right to make a claim. The first is the period of three months whose commencement will be determined based on the knowledge by other members that an action subject to the prohibition of competition is realized or that a board member joined another corporation. The second period is the period of one year commencing from the realization of the action violating the prohibition to compete. This one-year period is independent from other members' knowledge that the prohibition to compete has been breached. The corporation may raise other claims against the member violating the prohibition of competition which are not stipulated under article 396 of the Turkish Commercial Code. Accordingly, the corporation may request that the member violating the prohibition of competition through joining a competing corporation as a partner with unlimited liability or joining the managing body of a competitive corporation resigns from this corporation or managing body. Further, the company may dismiss the member violating the prohibition of competition from board membership. Again, the company may initiate a lawsuit to cease the ongoing violation of the prohibition of competition by a board member, or a lawsuit of preclusion prior to probable breaches which have not yet occurred. In this chapter, lastly, the fourth paragraph of article 396 of the Turkish Commercial Code is assessed. This paragraph regulates that provisions governing liability of the members of the board of directors are reserved. This is a new provision which was not present in the abrogated Turkish Commercial Code no. 6762, newly introduced under the Turkish Commercial Code. In this context, we tried to determine the purpose and characteristics of this provision and concluded this work.
Keywords: Administrateurs; Anonim şirketler; Board of directors; Competition prohibition; Concurrence (interdiction); Joint stock company; Members of the board directors; Rekabet yasağı; Société par actions; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Yönetim kurulu; Yönetim kurulu üyeleri

Hâkim pay sahibinin azınlığı şirketten çıkarma hakkı (Squeeze-out) - Keski̇n, Harun (Ankara Üniversitesi, 2022)
Klasik anlamdaki şirketten çıkarma düzenlemeleri, "haklı sebep" temeline dayanmaktadır. Bu düzenlemelerin en tipik özelliği, düzenlemiş oldukları çıkarma hakkı ile şirketin feshi kurumu arasında bir bağlantıya yer vermiş olmalarıdır. Bu bağlantı, haklı sebebe dayalı çıkarma düzenlemelerinin hizmet ettiği birincil amacı da ortaya koymaktadır: Şirketin devamlılığını sağlamak suretiyle ortaklar arasındaki menfaatler dengesi korumak. Türk hukukuna 6102 sayılı Türk Ticaret Kanunu ve 6362 sayılı Sermaye Piyasası Kanunu ile kazandırılan "squeeze-out" müessesesi ise daha farklı bir kuramsal temele dayanmaktadır. Bu müessese ile, şirkette genellikle %90-95 arasında nitelikli bir pay ve/veya oy oranına ulaşmış olan hâkim pay sahibine, azınlığın paylarını herhangi bir sebep göstermeden iktisap edip, onu şirketten çıkarma hakkı tanınmıştır. Böylece çıkarmanın ekseni, "haklı sebep" olgusundan "hâkimiyet" olgusuna kaymıştır. Kanun koyucuların bu şekilde bir çıkarma hakkını öngörmelerindeki temel sebep ise kurumsal nitelikte bazı amaçları gerçekleştirmek isteyen hâkim konumdaki pay sahiplerine bir imkân sunmaktır. Tezimizde, klasik anlamdaki çıkarma müesseselerinin dayanmış olduğu kuramsal temelden ayrılan "squeeze-out" kurumunun kuramsal temeli, düzenlemenin hangi amaçlarla öngörüldüğü meseleleri ele alınmakta; bu bağlamda, kurumun karşılaştırmalı hukuktaki ne şekilde düzenlendiği, kurumun ortaya çıkardığı sorunlar ve bu sorunların çözümüne yönelik önerilere yer verilmektedir. The classic rules designed for exclusion of a partner has a simple theoretical basis: A/an justified/objective reason (or in other words "good cause"). The most typical feature of these rules is they build a bridge between the exclusion right and the dissolution of the company. This bridge also shows the the primary purpose served by these rules which is to maintain the balance of interests among the partners by ensuring the continuity of the company. In comparison with the classical rules, the "squeeze-out" rules which have been introduced into Turkish law with the Turkish Commercial Code No. 6102 and the Capital Markets Law No. 6362, have a different theoretical basis. The controlling shareholder who has reached a qualified percentage of capital and/or voting rights (usually %90-95), has been granted the right to acquire the minority's shares without asserting any justified reason and exclude him from the company. Thus the idea behind the exclusion has been changed from "good cause" to the "dominance/control". The main reason for designing such an exclusion right is to provide an opportunity to the controlling shareholders trying to achieve institutional objectives in the company. In our thesis, the theoretical basis of the "squeeze-out" rules and the reasons for designing such a new exclusion right will be examined within the framework of other squeeze-out rules in comparative law. Within this context, the most common problems in squeeze-outs and suggestions for solving these problems are analyzed.
Keywords: Actionnaire majoritaire; Actionnaire minoritaire; Anonim şirketler; Azınlık hakları; Capital companies; Dismissal from the partnership; Dominant position; Exclusion; Hakim durum; Joint stock company; Kanunlar 6362 sayılı; Laws 6362 numbered; Limited company; Limited şirketler; Minority rights; Ortaklıktan çıkarılma; Satın alma hakkı; Sermaye şirketleri; Société commerciale; Squeeze-out right; Turkish commercial law; Türk ticaret hukuku

Kripto varlıkların dış ticaret kapsamında değerlendirilmesi ve kripto varlıklar üzerine nicel bir araştırma - Koç, Tayfur Süleyman (Alanya Alaaddin Keykubat Üniversitesi, 2022)
Tez çalışmasının amacı, kripto varlıkların ödeme aracı olarak kullanımını dış ticaretin bileşenleri kapsamında değerlendirmek ve kripto varlıkların yurtdışı ödemelerde ve bireysel yatırımlarda kullanılmaları bağlamında, bireylerin tutumlarını etkileyen faktörleri incelemektir. Bu amaç doğrultusunda öncelikli olarak, kripto varlıkların para işlev ve özelliklerine ne ölçüde uyum sağladıkları hususunda tespitlerde bulunulmuştur. Ulusal paralara eşdeğer kılınan stabil fiyatlı kripto varlıkların geleneksel ve modern para işlevlerine uyumlu oldukları yönünde görüş bildirilmiştir. Para özellikleri açısından ele alındığında da "kabul edilebilirlik" ve "sıradanlık" dışındaki para özelliklerine, tüm kripto varlıkların uyum sağladıkları değerlendirilmiştir. Ayrıca kripto varlık birimleri parasal niteliklerine göre tasnif edilerek, değişken fiyatlı, stabil fiyatlı ve finansal ürünlere bağlanan kripto varlıklar olmak üzere, üç kategoriden oluşan bir sınıflandırma geliştirilmiştir. Para işlev ve özellikleri kapsamındaki tespitlerin ardından, önceden belirlenen dış ticaret bileşenlerinin özelinde kripto varlıkların mevcut ve muhtemel kullanım alanları incelenmiştir. Belirlenmiş olan dış ticaret bileşenleri, uluslararası para birimleri, uluslararası bankacılık, uluslararası lojistik, dış ticaret hukuku ve gümrük işlemleridir. Dış ticaret bileşenlerine yönelik değerlendirmelerde kripto varlıkların ödeme aracı olarak kullanımları esas alınmıştır ve değerlendirme sürecinde çalışma kapsamında oluşturulmuş olan kripto varlık sınıflandırmasının kategorileri için de görüşler oluşturulmuştur. Çalışma kapsamında kripto varlıklara yönelik bireysel tutumları irdelemek amacıyla ampirik bir araştırma gerçekleştirilmiştir. Araştırma kapsamında UTAUT-2 modelini temel alan bir araştırma modeli oluşturulmuş ve yurtdışı ödemelerde kullanım niyeti ile yatırımda bulunma niyeti olmak üzere, iki farklı bağımlı yapıyı etkileyen unsurlar irdelenmiştir. Yol katsayısı değerine (β) göre yurtdışı ödemelerde kullanım niyetini anlamlı ölçüde etkileyen yapıların önem sırasına göre, "performans beklentisi", "sosyal etki" ve "algılanan risk" adlı boyutlar olduğu bulgusuna ulaşılmıştır. Yatırımda bulunma niyetini anlamlı düzeyde etkileyen bileşenler ise sırasıyla; "performans beklentisi", "sosyal etki", "farkındalık" ve "algılanan risktir". Araştırma kapsamında bağımlı ve bağımsız yapılar arasındaki etkileşimi incelemek amacıyla etki büyüklüğü (f²) ve tahmin gücü (q²) değerleri de hesaplanmıştır. Yol katsayısı değerlerine göre modelin bağımlı yapılarını anlamlı düzeyde ve negatif yönde etkileyen "algılanan risk" boyutunun, f² değeri açısından anlamlı bir katkısının olmadığı görülmüştür. Ayrıca yol katsayılarına göre "performans beklentisi" bağımlı yapılar üzerinde en çok etkiye sahipken, etki büyüklüğüne göre en önemli yapı "sosyal etkidir". Bağımsız yapıların tahmin gücü (q²) değerleri de etki büyüklüğü (f²) değerleri ile paralel sonuçlar ortaya koymuştur. Ortaya koyulan ampirik araştırmanın sonucunda, örneklemin yurtdışı ödemelerde ve yatırım kararlarında kripto varlıkları kullanma eğilimleri açısından en önemli etmenlerin "performans beklentisi" ve "sosyal etki" olduğu sonucuna ulaşılmıştır. The aim of the thesis study is to evaluate the use of crypto assets as a payment instrument within the scope of the components of foreign trade and to examine the factors affecting the attitudes of individuals in the context of the use of crypto assets in foreign payments and individual investments. For this purpose, first, it was evaluated that to what extent crypto assets are compatible with money functions and features. It was stated that stable priced crypto assets, which are equivalent to national currencies, are compatible with traditional and modern money functions. When considered in terms of money features, it was evaluated that all crypto assets are compatible with money features other than "acceptability" and "ordinariness". In addition, crypto assets were classified according to their monetary characteristics, and a classification was developed consisting of three categories: variable priced, stable priced and crypto assets linked to financial products. After the evaluations within the scope of money functions and features, the current and possible usage areas of crypto assets were examined specifically for the previously determined foreign trade components. The determined foreign trade components are international currencies, international banking, international logistics, foreign trade law and customs procedures. Evaluations for foreign trade components were based on the use of crypto assets as a payment instrument and arguments were formed for the categories of the crypto asset classification created within the scope of the study during the evaluation process. Within the scope of the study, an empirical research was carried out to examine individual attitudes towards crypto assets. A research model based on the UTAUT-2 model was formed and the factors affecting two different dependent structures, namely "intention to use in foreign payments" and "intention to invest", were examined. According to the value of the path coefficient (β), it was found that the structures that significantly affect the intention to use in foreign payments are the dimensions called "performance expectancy", "social impact" and "perceived risk", in order of importance. The components that significantly affect the intention to invest are "performance expectancy", "social impact", "awareness", and "perceived risk", respectively. Effect size (f²) and predictive relevance (q²) values were also calculated to examine the interaction between dependent and independent structures within the scope of the research. It was seen that the "perceived risk" dimension, which affects the dependent structures of the model significantly and negatively according to the path coefficient values, does not have a significant contribution in terms of f² value. In addition, according to the path coefficients, "performance expectancy" has the largest impact on the dependent structures, while the most important structure according to the effect size is "social impact". The predictive relevance (q²) values of the independent structures also showed similar results with the effect size (f²) values. As a result of the empirical research, it was concluded that the most significant factors in terms of the tendency of the participants to use crypto assets in foreign payments and investment decisions are "performance expectancy " and "social impact".

Anonim şirketin sosyal sorumluluğu - Okuyucu, Deniz (İstanbul Üniversitesi, 2022)
Kurumsal sosyal sorumluluk her ne kadar son yıllarda Türk iş dünyasının radarına girmiş olsa da, şirketler hukukunun doğuşundan beri var olan hem bir tartışma konusu hem de bir temennidir. İşbu tez kapsamında, üzerinde uzlaşmaya varılmış bir tanımı bulunmayan kurumsal sosyal sorumluk kavramının, yıllardır bağlayıcı olmayan hukuk enstrümanları ile düzenlenmesinin bir adım ilerisine geçmesi amaçlanmaktadır. Bu adımın da, kavramın şirketler hukuku mevzuatı çerçevesinde bağlayıcı hukuk kuralı hâline getirilmesi ile mümkün olacağı savunulmaktadır. Araştırma metodolojisinde, yürürlükte olan mevzuat hükümleri analizine yoğunlaşılmış olmasının yanı sıra kavramın tarihsel gelişimi gereği bağlayıcı olmayan hukuk (soft law) düzenlemelerine de yer verilmiştir. Şirketlerin pay sahibi dışında; işçiler, alacaklılar, çevre ve toplum gibi diğer menfaat sahiplerinin de çıkarlarını göz önünde bulunduracak şekilde varlığını devam ettirmesinin hâlihazırdaki Türk hukuk mevzuatı ve özellikle de Türk Ticaret Kanunu hükümleri kapsamında mümkün olmadığı görülmektedir. Bu doğrultuda şirketin kâr elde etme amacının yumuşatılması, diğer menfaat sahiplerinin şirket içindeki konumlarının güçlendirilmesi, yönetim kurulu yapısının değiştirilmesi ve yönetim kurulu üyelerinin özen ve bağlılık yükümlülüklerinin kapsamının yeniden düzenlenmesi ile kurumsal sosyal sorumluluğun şirketler hukuku kapsamında temellendirilebileceği öne sürülmektedir. Although corporate social responsibility has entered the radar of Turkish business world in recent years, it is both a topic of discussion and a wish that has existed since the birth of corporate law. Within the scope of this thesis, it is aimed to go one step further than mentioning the concept of corporate social responsibility, which has no agreed definition, in only non-binding legal instruments for years. It is argued that this step will be possible by making the concept a binding legal rule within the framework of company law legislation. In the research methodology, besides focusing on the analysis of the legislation provisions in force, non-binding law (soft law) regulations due to the historical development of the concept are also included. Within the scope of the current Turkish legislation, especially the provisions of the Turkish Commercial Code, it is seen that it is not possible for companies to continue their existence in a way that takes into account the interests of other stakeholders such as workers, creditors, environment and society other than the shareholders. In this direction, it is claimed that corporate social responsibility can be grounded within the scope of company law by, inter alia, softening the company's aim of making profit, strengthening the positions of other stakeholders within the company, changing the structure of the Board of Directors and reorganizing the scope of Board of Directors' duty of care.
Keywords: Anonim şirketler; CSR; Company law; Corporate Social Responsibility; Corporate sustainability; Joint stock company; Kurumsal sosyal sorumluluk; Kurumsal sürdürülebilirlik; Multi-stakeholderism; Social responsibility; Sosyal sorumluluk; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku; Çok paydaşlılık; Şirketler hukuku

Kara eşya taşıma sözleşmelerinde taşıyıcıya teslimin hukuki sonuçları - Sar, Mustafa Seyfullah (İstanbul Ticaret Üniversitesi, 2022)
Mesafe ve sınırların ortadan kalkmasıyla uluslararası ticarette pozitif yönde ivme kazanılmıştır. Bu yolda uluslararası ekonomik ilişkilerin geliştirilmesi amacıyla yapılan anlaşmalar, kurulan örgütler, sağlanan teşvikler ve kaldırılan ithalat vergileri sayesinde, farklı ülkelerdeki firmalar ve bireyler, birbirleriyle daha hızlı bir şekilde alışverişe girmeye başlamış ve bunun sonucunda ticari faaliyetler ülke sınırlarını aşarak küresel boyutlara ulaşmıştır. Bunun sağlanabilmesi için taşıma sektöründe kullanılan araçlar detaylandırılarak daha güçlü hale getirilmiştir. Böylelikle malların dağıtımı daha ekonomik, güvenli ve hızlı bir şekilde gerçekleştirilmektedir. Bunun sonucu olarak taşıma sözleşmelerinin uluslararası ticaretteki yeri de giderek önem kazanmıştır. Öyle ki hakların ve borçların teminatı için sözleşme kaçınılmaz yoldur. Yakın tarihte, uluslararası alanda ticaretin daha kolay ve hızlı hale getirilmesi için yeknesak bir sistem oluşturulması ihtiyacı ortaya çıkmış ve buna binaen ulusal düzenlememiz olan TTK'nın yanında, uluslararası karayolu taşımacılığında, koşulları standardize eden, taşıyıcının sorumluluklarını belirleyen CMR Konvansiyonu oluşturulmuştur. Düzenlenen kurallar doğrultusunda, taşıyıcı eşyayı teslim aldığı andan teslim edinceye kadar zarardan ve kayıptan sorumlu olacaktır. Taşıyıcı, ancak TTK ve CMR'de yer alan genel ve özel kurtuluş karinelerinin varlığının ispatı halinde sorumluluktan muaf olabilecektir. Aksi halde taşıyıcı, meydana gelen zarar veya zayiatın oranı doğrultusunda sorumlu olacak ve buna müteakiben tazminat miktarı belirlenecektir. TTK ve CMR pek çok noktada benzerlik gösterse de bazı yönleriyle keskin farklılıklar mevcuttur. Uluslararası ticaretin bekası için önem oluşturan bu nokta özellikle sorumluluk hususunda hukuki tartışmaları da beraberinde getirmiştir. With the obstacle of distances and borders disappearing, international trade has gained speed in a positive direction. Thanks to deals and agreements that were made, organisations that were built, incentives that were provided, and removal of import taxes in order to improve economic relations with this respect, companies and people in different countries have started to be able merchandise with each other more quickly; consequently, tradal actions have crossed borders of lands and reached global level. For this to happen, vehicles used in the sector of transportation have been developed, thus made stronger and more elaborate. As a result of this, the distribution of goods can be ensured in a more economic, safer, and faster way, and the role of vehicle contracts in international trade has gradually gained importance as contracts are inevitable to ensure and guarantee rights and debts. In recent history, a need to have a uniform system that would enable international trade to be easier and faster was born, and consequently, in addition to our regulations on TTK (Turkish Commercial Code), CMR Convention which standardized conditions and determined the responsibilities that transporters have in international land transportation. According to the regulations, the transporters are responsible for the safety of the goods in case of a damage and loss) from the moment they take them until they deliver them. The transporters can only be exempt from this responsibility in the case that general and specific presumptions of innocence that a place in the law (TTK) and the CMR can be proven. Otherwise, the transporter shall be responsible for compensating for the damage or the loss that occurred and the cost for the indemnity shall be determined. Although TTK and CMR Convention have similarities in many regards, in some ways they are distinctively different from one another. This point which has a critical role in the future of international trade has brought about many juridical discussions, especially ones related to responsibilities.
Keywords: Contracts; Delivery; Eşya taşıma; Goods transportation; Highway Route with International Furniture Removal Agrement; Highway transportation; Kara yolu taşımacılığı; Karayolu ile Uluslararası Eşya Taşıma Sözleşmesi; Obligation to delivery; Sözleşmeler; Teslim borcu; Teslimat; Turkish Commercial Code; Turkish commercial law; Türk Ticaret Kanunu; Türk ticaret hukuku

Anonim şirketlerde ilişkili taraf işlemleri - Şi̇mşek, Bahar (İstanbul Üniversitesi, 2022)
İlişkili taraf işlemlerine ilişkin özel düzenlemelerle şirketin varlıklarının ilişkili taraflara aktarılması ve şirketin ve şirketin bütün menfaat sahiplerinin hâkim pay sahipleri ve yöneticiler tarafından sömürülmesinin engellenmesi amaçlanır. Bu amaçla ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu'nda etraflıca bir düzenleme getirilmiş ve önemli bazı işlemler için prosedür öngörülmüştür. Çalışmamız, esaslı düzenleme Sermaye Piyasası Kanunu'nda yer aldığı için bu düzenleme temel alınarak şekillendirilmiştir. Ancak sadece halka açık şirket değil; halka kapalı şirketler yönünden de konu incelenmiş, ilişkili taraf işlemi sayılabilecek Türk Ticaret Kanunu'nda ve diğer kanunlarda yer alan diğer düzenlemelere de yer verilmiştir. Tez dört bölümden oluşmaktadır. İlk bölümde ilişkili taraf işlemi kavramı genel olarak açıklanmış, ilişkili taraf işlemleriyle ilgili düzenlemelere neden ihtiyaç olduğu hususu ortaya koyulmaya çalışılmıştır. Bu kapsamda benzer kavramlarla karşılaştırılmış ve Avrupa Birliği ve çeşitli ülkelerde düzenlemeler incelenmiştir. Nihai olarak Türk hukukunda ilişkili taraf işlemlerinin tarihsel sürecine yer verilmiştir. İkinci bölümde yasal düzenlemelerdeki ilişkili taraf ve ilişkili taraf işlemi kavramı ele alınmıştır. Üçüncü bölümde ise ilişkili taraf işlemleriyle ilgili Sermaye Piyasası Kanunu, Türk Ticaret Kanunu ve bazı özel kanunlarda yer alan düzenlemeler incelenmiş, ilişkili taraf işlemleri için öngörülen prosedürel korumalar açıklanmıştır. Dördüncü bölümde ise hukuka aykırı ilişkili taraf işlemlerinin sonuçları incelenmiş ve ilgililerin sorumluluğuna yer verilmeye çalışılmıştır. Special regulations regarding related party transactions aim to prevent the transfer of the assets of the joint stock company to the related parties and thus prevent the exploitation of all the stakeholders of the company by the controlling shareholders and managers. For this purpose, a comprehensive regulation has been introduced in the Capital Markets Law regarding related party transactions and a procedure has been envisaged for some significant transactions. Since the main regulation is contained in the Capital Markets Law, our thesis has been shaped based on this regulation. However, this thesis has not examined the subject only for public companies; it has also examined it in terms of non-public companies, and other regulations in the Turkish Commercial Code and other laws, which can be considered as related party transactions. The thesis consists of four parts. In the first part, the concept of related party transactions is explained in general and the reason for the need for regulations regarding related party transactions is tried to be revealed. In this context, related party transactions have been compared with similar concepts and the regulations in the European Union and various countries have been examined. Finally, the historical process of related party transactions in Turkish law is examined. In the second chapter, the concept of related party and related party transactions as defined in legal regulations is discussed. In the third section, the regulations contained in the Capital Markets Law, the Turkish Commercial Code and some special laws related to related party transactions are examined and the procedural protections provided for related party transactions are explained. In the fourth chapter, the results of unlawful related party transactions are examined and the liability of the related parties is tried to be included.
Keywords: Anonim şirketler; Camouflage of earning distribution; Joint stock company; Société par actions; Turkish capital market; Turkish commercial law; Türk sermaye piyasası; Türk ticaret hukuku; Örtülü kazanç dağıtımı

Anonim ortaklıkta pay sahibinin bilgi alma ve inceleme hakkı - Sümer, Burak (Hacettepe Üniversitesi, 2022)
Anonim ortaklıkta her pay sahibi genel kurulda, yönetim kurulundan şirketin işleri; denetçilerden ise denetimin yapılma şekli ve sonuçları hakkında bilgi alma talebinde bulunma hakkına sahiptir. Ayrıca her pay sahibinin şirketin ticari defterlerini ve yazışmalarını, sorusunu ilgilendiren kısımları ile sınırlı olarak inceleyebilme hakkı bulunmakla birlikte, bunun için genel kurulun açık izni veya yönetim kurulunun bu hususta kararı gereklidir. Pay sahibinin bilgi alma ve inceleme hakkının reddi, talep edilen bilginin şirket sırlarının açıklanmasına veya korunması gereken diğer şirket menfaatlerinin tehlikeye girmesine neden olabilecek ise söz konusu olabilir. Bilgi alma ve inceleme talebinin cevapsız bırakılması, haksız olarak reddedilmesi, ertelenmesi veya pay sahibinin kanunda düzenlendiği şekilde bilgi alamaması halinde, hakkın açılacak bir dava ile mahkeme aracılığıyla kullanılması da mümkündür. Çalışmamız dört bölümden oluşmaktadır. İlk bölümde bilgi alma ve inceleme hakkının genel nitelikleri ile karşılaştırmalı hukuktaki düzenlenme şekli; ikinci bölümde hakkı etkileyen ilkeler ve hakkın düzenlenme amacı; üçüncü bölümde bilgi alma ve inceleme hakkının kullanılması ve hakkın sınırları; dördüncü ve son bölümde ise hakkın ihlalinin hukuki sonuçları ele alınmıştır. At the general meeting, any shareholder of a joint stock company is entitled to information from the board of directors on the affairs of the company and from the external auditors on the methods and results of their audit. Also the company ledgers and business correspondence, limited to the parts about the question may be inspected only with the express authorisation of the general meeting or by resolution of the board of directors. It may be refused where providing it would jeopardise the company's trade secrets or other interests warranting protection. If the request for information and examination is left unanswered, unfairly rejected, postponed or if the shareholder is unable to obtain information as regulated in the law, it is also possible to exercise the right through a lawsuit to be filed. Our study consists of four parts. In the first part, the general characteristics of the right to information and examination and the way it is regulated in comparative law; in the second part, the principles affecting the right and the purpose of regulation of the right; the exercise of the right to receive and review information and the limits of the right in the third part; In the fourth and last chapter, the legal consequences of the violation of the right are discussed.
Keywords: Anonim ortaklıklar; Bilgi alma ve inceleme hakkı; Company law; Incorporated companies; Pay sahipleri; Right to information and examination; Shareholders; Turkish commercial law; Türk ticaret hukuku; Şirketler hukuku

Halka açık anonim şirketler bakımından şirketler topluluğunda ortak nakit ve hizmet kullanımının hukuki sonuçları - Üzeler Demi̇rağ, Rabia Sanem (İhsan Doğramacı Bilkent Üniversitesi, 2022)
Bu çalışmanın temel amacı şirketler topluluğunda yer alan halka açık şirketlerin topluluk şirketleri ile ortak nakit ve hizmet kullanımına yönelik işlemlerinin sermaye piyasası mevzuatı açısından sınırlarının ve hukuki sonuçlarının tespit edilmesidir. Bu doğrultuda sermayenin oluşturulması ve malvarlığının korunması kuralları kapsamında ortak nakit kullanımı uygulamalarının sınırları, ilişkili taraf işlemlerine ilişkin düzenlemeler ve örtülü kazanç aktarımı yasağı çerçevesinde değerlendirilmiştir. İlaveten, şirketler topluluğunda maliyet tasarrufu sağlayan ve topluluğun ortak stratejiler çerçevesinde yönetilmesi bakımından gerekli olan ortak hizmetler nedeniyle yapılan ödemelerin tutarlarının belirlenmesine ilişkin esaslar örtülü kazanç aktarımı yasağı bağlamında ele alınmıştır. Son olarak, hukuka aykırılığa yol açan ortak nakit ve hizmet kullanımı uygulamalarına yönelik Sermaye Piyasası Kurulu'nun müdahale yetkileri ve şirketler topluluğunda hâkim şirketin bağlı şirketin kaybını denkleştirebilmesi olanağının halka açık şirketlerde uygulama alanı bulmasının hukuken hangi hâllerde gündeme gelebileceği irdelenmiş ve halka açık şirketlerin dâhil oldukları şirketler topluluklarında ortaya çıkan menfaat çatışmalarının dengelenmesine yönelik değerlendirme ve düzenleme önerilerinde bulunulmuştur. The main purpose of this study is to determine the legal limits and consequences of the shared use of cash and services within corporate groups for publicly held companies' in relation to capital markets legislation. In this respect, the legal limits of transactions which enables sharing cash among group companies with respect to rules on formation and protection of capital of publicly held companies is reviewed within the context of related party transactions and cases which may result in disguised profit distribution is evaluated. Additionally, the use of shared services in corporate groups which provides significant savings and is necessary for developing common strategies is examined in order to determine which principles must be adhered to while charging for these services with regard to the ban on disguised profit distribution. Furthermore, Capital Markets Boards' intervention powers regarding the shared use of cash and services which results in violation of the law is evaluated and the parent company's opportunity of balancing the disadvantages of the subsidiary is assessed for publicly held companies. Finally, legislative amendments have been proposed in order to balance the conflicts of interest which arises where a publicly held company is part of a corporate group.
Keywords: Anonim şirketler; Capital Market Board; Capital Market Law; Cash flow; Cash management; Cosourcing; Halka açık ortaklıklar; Joint stock company; Nakit akışı; Nakit yönetimi; Ortak kaynak kullanımı; Public held companies; Sermaye Piyasası Kanunu; Sermaye Piyasası Kurulu; Turkish commercial law; Türk ticaret hukuku

Geçmişe etkili sigorta - Yolal, Oğuz (Selçuk Üniversitesi, 2022)
Sigorta ettiren genellikle geleceğe etkili olarak sigorta korumasından yararlanmak üzere sigorta sözleşmesi yapmaktadır. Ancak sigorta ettiren, sözleşmenin kurulmasına ilişkin öneri ile sözleşmenin kurulması arasında veya sözleşmeye ilişkin önerinin yapıldığı tarihinden önce sigorta korumasından yararlanmak isteyebilir. Sigorta ettirenin sözleşmenin kurulmasından önce sigorta korumasından yararlanabilmesi, geçmişe etkili sigorta ile mümkün olmaktadır. Geçmişe etkili sigorta TTK m. 1458 hükmünde düzenlenmiştir. Geçmişe etkili sigorta sözleşmesinin kurulabilmesi için ikisi olumlu bir tanesi olumsuz şart olarak üç şartın bulunması gereklidir. Olumlu şartlar, sigorta sözleşmesine ilişkin mutabakatın bulunması ve sigorta sözleşmesinin kurulması; olumsuz şart ise, sigortacı, sigorta ettiren ve sözleşmeden haberdar olmak şartıyla sigortalının rizikoya ilişkin bilgi sahibi olmamasıdır. Bu şartların sağlanması hâlinde, geçmişe etkili sigorta sözleşmesi geçerli olacak ve böylelikle sigorta koruması, sigorta sözleşmesinin kurulduğu tarihten önce başlayacaktır. Geçmişe etkili sigorta gerçek ve gerçek olmayan geçmişe etkili sigorta olarak ikiye ayrılmaktadır. Gerçek geçmişe etkili sigorta, sigorta korumasının sözleşmenin kurulmasına ilişkin önerinin yapıldığı tarihten önce başladığı sigortadır. Gerçek ol-mayan geçmişe etkili sigorta ise, sigorta ettirenin sözleşmeye ilişkin öneride bulun-duğu tarih ile sözleşmenin şekli olarak kurulduğu tarih arasında sigorta korumasının sağlandığı sigorta olarak isimlendirilmektedir. Nitekim TTK m. 1458 düzenlemesinin ilk cümlesinde de, sigorta korumasının "sözleşmenin yapılmasından önceki bir tarihten itibaren" sağlanabileceği belirtilerek, gerçek veya gerçek olmayan geçmişe etkili sigortanın yapılmasının mümkün olduğu anlaşılmaktadır. The insured generally makes an insurance contract in order to benefit from insurance protection effectively for the future. However, the policyholder may wish to benefit from insurance protection between the proposal for the conclusion of the contract and the conclusion of the contract or before the date of the proposal regarding the contract. It is possible for the insurant to benefit from insurance protection before the conclusion of the contract, with retroactive insurance. Retroactive insurance TCC m. It was regulated in the 1458 provision. In order for a retroactive insurance contract to be established, three conditions must be present, two of which are positive and one is negative. Positive terms, agreement on the insurance contract and establishment of the insurance contract; The negative condition is that the insurer, the policyholder and the insured are not informed about the risk, provided that they are aware of the contract. If these conditions are met, the retroactive insurance contract will be valid and thus insurance protection will start before the insurance contract is established. Retroactive insurance is divided into two as real and unreal retroactive insurance. Actual retroactive insurance is insurance in which insurance protection begins before the date of the proposal for the establishment of the contract. Unreal, retroactive insurance, on the other hand, is called insurance in which insurance protection is provided between the date the policyholder makes a proposal regarding the contract and the date the contract is formally established. As a matter of fact, TTK art. In the first sentence of regulation 1458, it is understood that it is possible to make real or non-real retroactive insurance, by stating that insurance protection can be provided "from a date before the conclusion of the contract".
Keywords: Geçmişe etkili sigorta; Insurance; Insurance contracts; Insurance law; Insurance sector; Recroactive insurance; Sigorta; Sigorta hukuku; Sigorta sektörü; Sigorta sözleşmeleri; Turkish commercial law; Türk ticaret hukuku

Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması - Babayev, Ilgar (İstanbul Ticaret Üniversitesi, 2021)
Uluslararası ticaretin gelişimi ve artması dünyadaki bütün devletler tarafından hedeflenen bir amaçtır. Ancak devletlerin ulusal hukuk sistemleri arasındaki farklar bu gelişim için belirli engeller oluşturmaktadır. Bu engelleri aşmak için uluslararası ticaret hukukunun yeknesaklaştırılması, yani aynı uluslararası hukuki işleme uygulanacak iki veya daha çok ulusal hukuk sisteminin farklı kurallarının bir kuralla değiştirilmesi çare olarak görülmektedir. Bu amaçla şimdiye kadar bir çok çalışmalar yapılmış ve bir çok yeknesaklaştırma aracı ortaya konulmuştur. Uluslararası ticaret hukukunun bel kemiğini oluşturan uluslararası ticari sözleşmeler alanında hazırlanmış olan yeknesaklaştırma araçları ise bu bakımdan özellikle önem taşımaktadır. Hukukun yeknesaklaştırılması alanında çalışmalar sürdürülmekle birlikte bu konuya şüpheyle bakanlar ve yeknesaklaştırmanın kendi amacına ulaşamayacağını düşünenler de mevcuttur. Bu yeknesaklaştırma sürecinde ortaya çıkan bir takım sorunlarla ilgilidir. Ancak özellikle de uluslararası ticaret hukuku alanında yapılan yeknesaklaştırma çalışmalarında elde edilen başarılar umut vaat etmektedir. Uluslararası ticari sözleşmeler hukuku alanında yapılmış olan ayrı ayrı yeknesaklaştırma çalışmaları ile ilgili araştırmalar mevcut olsa da, konuyu daha kapsamlı bir şekilde ele alan ve meseleye daha geniş bir perspektiften bakan araştırmaların eksik olduğunu görmekteyiz. Özellikle de Türkiye'de bu tür araştırmalarda bir boşluğun mevcut olduğu hissedilmektedir. Uluslararası ticari sözleşmeler hukukunun yeknesaklaştırılması amacıyla ortaya konulmuş çalışmaların ve hazırlanmış olan araçların daha kapsamlı bir şekilde araştırılması, onların sağladığı faydaları göstermek, bu alanda ortaya çıkan sorunları belirlemek ve gerekli çözüm önerileri sunmak açısından önem arz etmektedir. Bütün bunları dikkate alarak biz bu araştırmamızda uluslararası ticaret hukukunun yeknesaklaştırılması kavramını, onun önemini ve sağladığı avantajları, yeknesaklaştırmanın gerçekleştirilmesi yöntemlerini, uluslararası ticaret hukukunun yeknesaklaştırılması alanında çalışmalar yapan ve bu sürece katkıda bulunan uluslararası kurumları, uluslararası ticari sözleşmeler alanında yapılmış olan ve şu an yapılmakta olan çalışmaları, bu konuyla ilgili ortaya çıkan sorunları ve bu sorunların ortadan kaldırılması için sunulan çözüm önerilerini incelemeye çalıştık. [...] The development and growth of international trade is an aim targeted by all states in the world. However, the differences between the national legal systems of states pose certain obstacles to this development. To overcome these obstacles, the unification of the international commercial law is considered a remedy, that is, changing the different rules of two or more national legal systems to be applied to the same international legal process with one rule. For this purpose, so far many studies have been done and many unification instruments have been introduced. The unification instruments prepared in the field of the international commercial contracts, which form the backbone of international commercial law, are particularly important in this regard. Although studies on the unification of the law continues, there are also those who are skeptical about this issue and those who think that it cannot achieve its own goal. It concerns a number of problems that arise in the process of unification. However, the successes achieved in the unification studies especially in the field of international commercial law promise hope. Although there are researches on individual unification studies in the field of international commercial contracts law, we see that there is a lack of research that covers the issue more extensively and looks at the issue from a wider perspecitve. Especially, a vacancy in this kind of research is available in Turkey. It is important to investigate the studies and the instruments that have been prepared for the purpose of the unification of the international commercial contracts law, to show their benefits, to identify the problems that arise in this field and to offer necessary solutions. Considering all these, in this research, we tried to examine the concept of the unification of the international commercial law, its importance and advantages, the methods of realization of unification, the international institutions that work in the field of the unification of the international commercial law and contribute to this process, the problems that arise about this issue and the proposed solutions to eliminate these problems.
Keywords: Hukukun Yeknesaklaştırılması; International Commercial Contracts Law; International Commercial Law; International commercial contracts; Lex Mercatoria; Uluslararası Ticaret Hukuku; Uluslararası Ticari Sözleşmeler; Uluslararası Ticari Sözleşmeler Hukuku; Unification Instruments; Unification of Law; Yeknesaklaştırma Araçları

Yönetim kurulu krizleri ve çözüm yolları - Meti̇n, Umut (Kadir Has Üniversitesi, 2021)
YK farklı sorunlar veya uyuşmazlıklarla yüzyüze gelebilir. Sorunlar veya uyuşmazlıklar kriz halini alarak YK'nın işleyişine olumsuz etki edebilmektedir. Kriz derinleştikçe, YK işlevini yerine getirmekte zorlanabilir. Krizin bir adım ötesinde ise YK kilitlenebilmektedir. Pay sahipleri arasındaki menfaat çatışmaları, YK kriz ve/veya kilitlenmesinin en sık rastlanan temel nedenidir. Kilitlenme durumunda, YK toplantı yapamamakta veya karar alamamaktadır. Oysa ki, YK her daim çalışabilmesi gereken bir organdır. YK'nın kilitlenmesi, şirketin de kilitlenmesi sonucu doğurabilir. Bu durum öyle risklidir ki, şirketin feshi/tasfiyesi yakın bir ihtimal olabilmektedir. Bu aşamada kilidin olabildiğince hızlı açılması şirketten menfaati olan herkes için (pay sahipleri, YK üyeleri, çalışanlar, alacaklılar, kamu vb.) hayati önemdedir. Bu nedenle, şirket esas sözleşmesinde YK kriz ve kilitlenmelerine karşı önlemler planlanmalıdır. Tek kişiden ibaret YK modeli ve YK'ya danışma kurulu desteği kilitleme riskine karşı önerdiğimiz modeldir. Pay sahipleri sözleşmesi, aile şirketleri için aile anayasası gibi hukuki metinler kriz ve/veya kilitlenmeye ilişkin tedbirler içermelidir. Önlemlere, rağmen kilitlenme gerçekleşir ise, öncelikle YK içi ve şirket içi çözümler uygulamaya konulmalıdır. Bu tür yöntemler yeterli olmazsa, AUÇY'nin tatbiki, şirket dışından gelen çözümün ilk aşaması olarak kabul edilmelidir. Arabuluculuk ile YK kriz ve kilitlenmelerine karşı etkin, hızlı ve kalıcı çözümler sağlanabilmektedir. "Med-arb" veya "Arb-med" gibi yöntemlerden de faydalanılabilir. Tahkim de bir çözüm yoludur. Bu yolda "seri tahkim usulü" YK kilitlenmeleri için daha uygundur. Son çare olarak nitelediğimiz, dava yolu ise, bazı durumlarda içinde şirketin fesih ve tasfiye riskini barındırdığı için kilidi açmak ve hatta kilidi kırmak için uygulamaya konulabilir. Mahkemelerde, organ yokluğuna dayalı fesih davası ve özellikle haklı sebeple şirketin feshi davası çözüm sağlayabilecek dava tipleridir. Özellikle, haklı sebeple şirketin feshi davası, kriz ve kilitlenmelere daha uygun olup, stratejik sonuçlara da imkân vermektedir. Bunlar yanında, YK işleyişinde yapay zekâdan faydalanmanın mümkün olup olmadığı, yapay zekâya YK üyesi olarak kişi statüsü verilip verilemeyeceği, bu meselenin YK üyelerinin sorumluluğuna etkisi incelenmiştir. Board of Directors may face various disputes or disagreements. These disputes or disagreements may turn into crises which negatively affect the normal functioning of the board. As the crisis deepens, Board of Directors could have difficulties in fulfilling its function. Moreover, a step further from the crisis, Board of Directors might even be locked up. Conflicts of interest among shareholders are known as the most common cause of the board of directors crisis and/or deadlock. In event of a deadlock, Board of Directors, a body should always be able to function, cannot hold meetings or make decisions anymore. The deadlock of board of directors, may lead the entire company to be locked down whereas the company may encounter the possibility of dissolution and liquidation. At this point, unlocking the crisis as quickly as possible is vital for relevant competent persons of the company. Therefore, measures should be taken in the company's articles of association against Board of Director crisis and/or deadlock. One-person Board of Directors model and support of Advisory Board to Board of Directors is the model we recommend against the risk of locking. Legal texts such as shareholder agreements and family constitutions for family companies should include measures regarding deadlock. If a deadlock has occurred in spite of precautions, first of all, Board of Directors and internal remedies should be implemented. If such methods are not sufficient enough, Alternative Dispute Resolution (ADR) methods should be regarded as the first stage of external intervention. Effective and rapid solutions can be achieved against deadlocks via mediation. "Med-arb" or "Arb-med" could be also utilised. Arbitration is also a way and in this way; "expedited (fast-track) arbitration" procedure is more suitable for corporate deadlocks. Litigation, as the last possibility that we propose, could also be applied to unlock or even break the lock, since it contains the risk of dissolution and liquidation of company in some cases. In courts, termination action based on the absence of organs and especially termination of the company with a valid reason are the types of cases that may provide a solution. Especially termination of the company with a valid reason is more suitable for crisis and deadlocks, and also grants strategic results. In addition to these, it has been questioned in this study whether Board of directors possibly benefit from artificial intelligence in the operations and whether AI can be attributed a person-status as a member of Board of Directors. The effects of this issue on the responsibility of the members of Board of Directors have been analysed.
Keywords: Absence of body; Arabuluculuk; Arbitration; Artificial Intelligence; Board directors; Conseil d'administration; Crisis; Deadlock; Inteligência artificial; Intelligence Artificielle; Kilitlenme; Kriz; Mediation; Members of the board directors; Médiation; Organ yokluğu; Tahkim; Yapay zeka; Yönetim kurulu; Yönetim kurulu üyeleri

OHADA bölgesinde yabancı yatırımlara ilişkin hukuki sorunlar « Türk hukuku ile karşılaştırmalı olarak » - Useni, Ahmed Emedi (İstanbul Ticaret Üniversitesi, 2021)
OHADA bölgesindeki yabancı yatırımların yasal korunması bahassederken yasal mekanizmaların varlığı fikrine atıfta bulunur. Yabancı yatırımlarının korunmasının sağlanması Bu Örgüte üye olmayan ülkelerin vatandaşları. Mukayese arama sürecinde Türk hukuku ile anlayışlı olmalıdır. Bu yatırımlar için optimal yasal güvenlik modeli olmalidir çünkü OHADA yasa nispeten yeni ve yapım aşamasındadır. Talking about the legal protection of foreign investments in the OHADA zone inevitably refers to the idea of the existence of legal mechanisms capable of ensuring the protection of investments of economic operators who are nationals of non-member countries of this Organization. The comparison with Turkish law must to be understanding in the process of seeking the model of optimal legal security for these investments, because the OHADA law remains relatively new and under construction.
Keywords: Company law; Comparative law; Foreign capital investments; Hukuksal korunma; Investissement étranger; Investments; Karşılaştırmalı hukuk; Legal protection; Organization for the Harmonization of African Business Law; Ticaret Kanunu Uyum Örgütü; Turkish law; Türk hukuku; Yabancı sermaye yatırımları; Şirketler hukuku

Medeni usul hukukunda inşai hüküm - Büyük, Elif Irmak (Marmara Üniversitesi, 2020)
ukuk davaları yaygın şekilde mahkemeden istenen hukuk himayeye göre bir sınıflandırılmaya tabi tutulmaktadır. Kişiler arasında geçerli olarak kurulan bir hukuki ilişkiyi bertaraf ederek yeni bir hukuki durum tesis eden davalar inşai davalar, bu davaların kabulü üzerine verilen mahkeme kararları ise inşai hükümler olarak adlandırılır. İnşai hükümler o zamana kadar var olmayan, ancak hükmün kesinleşmesiyle birlikte ortaya çıkan bir yeni bir hukuki durum yaratırlar. Kural olarak inşai hükümler herkese karşı etkilidir ve istenilen etkiyi doğurmak için icraya ya da herhangi bir aracıya ihtiyaç duymazlar. Özel hukuk alanında inşai davalar aile hukuku ve ticaret hukukunda yoğunlaşmakla birlikte, usul hukuk ve takip hukuk alanında inşai dava örnekleri de bulunmaktadır. Keza çekişmeli yargıda olduğu kadar çekişmesiz yargı işlerinde, geçici hukuki koruma tedbirleri görünümünde de inşai sonuç doğuran mahkeme kararlarına rastlanır. Bu tezde inşai hükümle ilgili temel kavramlar ele alındıktan sonra inşai hükmün özellikleri, türleri ve hükmün inşai etkisi başlıkları ayrıntılı bir şekilde ele alınacak; problemli gördüğümüz hususlarla ilgili kişisel önerilerde bulunulacaktır. Civil lawsuits are commonly subject to a classification according to the legal protection required from the court. Lawsuits which establish a new legal situation by eliminating a legal relationship established between individuals, are called constitutive lawsuits, and court verdicts made upon the acceptance of these lawsuits are called constitutive judgments. The constitutive judgments create a new legal situation that did not exist until then, but emerged with the finalization of the judgment. Likewise, as a rule, constitutive judgments are inter omnes effective against everyone and do not require execution or any means to produce the desired effect. In the field of private law, constitutive lawsuits are concentrated mostly in family law and commercial law, but there are also examples of constitutive lawsuits in the field of procedural law and law of execution. Moreover, in the area of non - contentious jurisdiction and temporary legal protections, constitutive court decisions are also exist. After considering the basic concepts related to the constitutive judgments, the features, the types and the titles of the constitutive judgments will be discussed in detail in our dissertation. Later on personal suggestions will be made on issues we consider problematic.
Keywords: Constitutive judgment; Constitutive lawsuits; Law of civil procedura; Medeni usul hukuku; İnşai davalar; İnşai hüküm

Şirketlerin insan hakları sorumluluğuna hak temelli bir yaklaşım: İnsan hakları due diligence'i (Human right due diligence) - Çimrin Ardiç, Çiğdem (İstanbul Bilgi Üniversitesi, 2020)
Çokuluslu şirketlerin etki alanı küresel olmakla birlikte, gerçekleştirdikleri faaliyetlerdeki menfaatleri özeldir ve nihai hedefleri de kârlılıklarını arttırmaktır. 1970'lerden itibaren çokuluslu şirketlerin dünyanın ekonomik kalkınmasına hizmet edebileceğine yönelik toplumsal beklentinin gerçekçi olmadığı ciddi insani ve çevresel maliyetleriyle birlikte anlaşılmıştır. Gerçekten de, neoliberal politikalar, ekonomik küreselleşme ve uluslararası yatırım antlaşmaları rejimiyle daha da güç ve nüfuz kazanan çokuluslu şirketlerin sebep olduğu siyasi, ekonomik, hukuki, çevresel ve sosyal sorunlar günümüzde belirgin bir hale gelmiştir. Toplumsal ve küresel eşitsizliklerin ve adaletsizliklerin daha da derinleşmesi kamuoyunda büyük endişe yaratmaktadır. Yaşanmakta olan bu süreç, insan haklarını koruma ve mağduriyetleri telafi mekanizmalarının yetersizliklerini gözler önüne sermektedir. Çokuluslu şirketlerin faaliyetlerini nasıl gerçekleştirdiğine veya güçlerini ne yönde kullandıklarına ilişkin hesap verilebilirliğin sağlanabilmesi için ortaya çıkan toplumsal beklentinin karşılanabilmesi amacıyla, 2011 yılında Birleşmiş Milletler İnsan Hakları Konseyi tarafından oybirliğiyle kabul edilen Rehber İlkeler çerçevesinde, devletlerin insan haklarını koruma ödevlerinin yanı sıra şirketlerin de insan haklarına saygı gösterme sorumluluğunun olduğu ve bu sorumluluğun gereklerini yerine getirmek için insan hakları etki incelemesi (HRDD) yapmaları gerektiği açık bir şekilde ifade edilmiştir. Şirketlere atfedilen bu insan hakları sorumluluğunun uluslararası hukukta ve uluslararası insan hakları hukukunda temellendirilmesi önem taşımaktadır. Zira, çokuluslu şirketlerin tedarik zincirlerindeki uygulamaları, uluslararası hukukun emredici kurallarının (jus cogens) ihlallerini de içeren birçok insan hakları ihlallerine sebebiyet vermektedir. Ancak, iç hukuk sistemlerinde çokuluslu şirketlerin örgütlenme biçimleri ve tüzel kişilik perdesinden kaynaklanan kısıtlar nedeniyle hesap verilebilirlikleri sağlanamamaktadır. Gerçekten de, iş dünyası ve insan hakları alanının esas tartışması ve sermayenin insan hakları ihlalleri kaynaklı yaşanan adaletsizliklerin esas nedeni, çokuluslu şirketlerin insan hakları sorumluluğunun sağlanabilmesine karşı en başta ticaret hukuku ve sözleşmeler hukuku olmak üzere iç hukukta yer alan yasal engeller, liberalizmin kalıplaşmış bakış açılarının aşılamaması ve çokuluslu sermayenin (yabancı yatırımın) ekonomik kalkınmayı ve toplumsal gönenci beraberinde getireceğine yönelik gerçekdışı beklentidir. Şirketlerin sahip olduğu insan hakları sorumluluğu uluslararası örf ve âdet hukuk normu olarak belirdikten sonra Rehber İlkeler kapsamında beyan edilmiş, HRDD de bu sorumluluğunun gereklerini ifa edilebilmesi için önemli ve gerekli bir risk tespit aracı olarak öngörülmüştür. Devletlerin insan haklarını koruma ödevleri gereği, şirketlerden hesap sorulabilirliğin ve hak mağdurlarının adalete erişimlerinin sağlanabilmesi için iç hukuk engellerini kaldırması ve/veya hesap sorulabilirliği kolaylaştırıcı iç hukuk düzenlemeleri yapması gerekmektedir. Son dönemde özellikle Avrupa Birliğinde ve Avrupa Birliğine üye olan devletlerde yaşanan yasal gelişmeler de bu gerekliliğin bir sonucudur. Even though the domain of multinational companies is global, their interests are private and their ultimate goal is to increase their profitability. Since 1970s, it has been understood that the social expectation that multinational companies can serve for the economic development of the world is not realistic and this understanding was gained with serious human and environmental costs. Indeed, the political, economic, legal, environmental and social problems caused by the mutinational companies, who have assumed more power and influence through widespread neoliberal policies, economic globalization and international investment treaties regime, have become more evident today. The intensification of social and global inequalities as well as injustice among societies raised great concern in the public opinion. This ongoing process reveals the shortcomings and inadequacies of human rights protection and remediation mechanisms. In order to meet the social expectation for ensuring legal accountability of multinational companies regarding their global activities, in 2011 the United Nations Human Rights Council unanimously adopted the 'Guiding Principles on Business and Human Rights', which explicity sets forth corporate responsibility to respect human rights in addition to already existing state duty to protect human rights. Guiding Principles also states that business actors should make human rights due diligence (HRDD) to fulfill the requirements and conditions of their human rights responsibility. It is important to establish legal basis of corporate responsibility to respect human rights within the scope of international law and international human rights law. Otherwise, such responsibility would not be legally enforceable and thus, one can easily argue that this responsibility exists in vacuum juris. However, we have been witnessing various practices and operations of multinational companies within their supply chains, which would constitute human rights violations - in fact, some of these violations are breaches of jus cogens. Nonetheless, it is not possible to ensure the legal accountability of multinational companies in the current national legal systems due to legal barriers arising from how multinational companies' organizations are structured and corporate veil doctrine stipulated in national laws. The main discussion in the field of business and human rights and the main reason for injustices due to human rights violations by corporate actors; legal barriers arising from domestic law – particularly, commercial and contractual law – for establishing human rights responsibility of multinational companies, inability to go beyond streotypical approach of liberalism, and the unrealistic expectation that multinational companies (as well as foreign investment) will bring economic development and social welfare. As a matter of fact, the corporate responsibility to respect human rights has been declared within the scope of the Guiding Principles after this responsibility was emerged as an international customary law norm. HRDD is also envisaged as an important and necessary risk assessment tool for the fulfillment of this responsibility's requirements. As precribed by the duty of states to protect human rights, in order to ensure legal accountability of corporate actors and to enable victims' access to justice, removing domestic legal barriers and enacting necessary regulations that would facilitate accountability are required. Recent legal developments, especially in the European Union and the member states of the European Union, are also a result of this necessity.
Keywords: Business world; Companies; Due diligence; Fundamental rights; Guiding principles; Human rights; Rehber ilkeler; Social rights; Sosyal haklar; Temel haklar; Özen yükümlülüğü; İnsan hakları; İş dünyası; Şirketler

Milletlerarası ticari tahkimde usule ilişkin konularda irade serbestisi - Takavut, İbrahim Doğan (İstanbul Üniversitesi, 2020)
Party autonomy is a well-accepted doctrine codified by national, international and supranational organizations that enables parties to be able to not only shape their contract but also their dispute resolution methods. It is believed that parties know their best interests; therefore, it is reasonable to give parties the freedom to decide whom they contract with and on what terms. This maximizes the autonomous freedom of the parties. Therefore, today it is well accepted that parties could waive their right to go to court and choose arbitration instead. However, through history, party autonomy has been seen as a direct threat to sovereign authority. States were always suspicious that arbitration hearings may not be as fair as court hearings since parties have the right to manipulate the arbitration processes. As a direct result of this, states regulated restrictions on party autonomy in international commercial arbitrations. Unfortunately, there is not an accepted definition of these restrictions and their effects on party autonomy have not been established or regulated internationally. Since party autonomy is the backbone of international commercial arbitration, it is important to crystalize the restrictions on party autonomy in procedural issues which directly affects the wellbeing of the arbitration process. Well accepted international regulations such as the New York Convention on Recognition and Enforcement of Foreign Arbitral Awards or UNCITRAL Model Law on International Commercial Arbitration helped to establish a unified system of restrictions on party autonomy but every state and state's courts interpret these restrictions differently. As procedural issues affect the result of international commercial arbitration, restrictions on party autonomy in procedural issues should be examined carefully. It is not an exaggeration that in international commercial arbitration the real and complicated questions most of the time originate from the issues of the boundaries of party autonomy. The tension between the party autonomy and efficiency of an arbitration process affects every decision which can be made by parties, arbitrators or courts. Therefore, this dissertation will investigate these problems in three parts by outlining; the source of party autonomy, the restrictions of party autonomy and the applications of these restrictions to party autonomy in procedural issues in international commercial arbitration. In the first part, the origin of party autonomy doctrine and how the doctrine developed throughout time will be examined. The law of arbitration, lex arbitri will be examined first. There are two accepted theories to determine lex arbitri. According to the territorialism theory, arbitration gets its power from the law of the place where the arbitration takes place. This theory suggests that the place where the arbitration takes place has control power over the procedure of arbitration. On the other hand, delocalization theory suggests that arbitral tribunals are detached from and not under the control of the law of the seat of arbitration. Although it looks like delocalization theory suits the needs of the international trade practice better because it assumes that arbitration is not in control of any law, it is still important to accept the power of the seat of arbitration since arbitration always needs a law to be controlled and get help. This section will also cover how different countries and international regulations determine lex arbitri and how it is determined in Turkish law according to the Turkish International Arbitration Law, Law no.4686. In the second part, restrictive measures of party autonomy will be examined. It will start with why party autonomy in procedural issues is needed to be restricted. Then the source of these restrictions will be mentioned. Afterwards, the common notions of the restrictions will be examined under the concepts of principles and rules. Under principles, the public policy and the common due process issues such as party equality, right to be heard, independence and impartiality of arbitrators will be examined in great detail. Then, mandatory rules which are based on these principles and their effect on party autonomy will be explained. The section will be closed with the examination of the circumstances where these principles and rules contradict each other. The main purpose of the second part is to look for commonly accepted problems of restrictions of party autonomy in procedural issues and how these common problems may evolve to a uniformed standard of the law, namely lex proceduralia. In the third part, the application of restrictions on party autonomy will be examined. The application of restrictions has different effects on parties, arbitrators and courts. Parties' autonomy is restricted while they are preparing their agreement on procedural issues, arbitrators are restricted during the arbitration processes and courts are restricted while helping the arbitration or controlling the awards. Before the arbitration process is initiated, parties' autonomy to shape their agreement looks like it is almost unlimited. However, parties' autonomy is always restricted by their choices. This situation is called the autonomy paradox. Therefore, the question of what parties can decide before the arbitrators join the processes is of the upmost importance. When the process starts and arbitrators start working, they balance the choice of parties and the restrictions of party autonomy. Since it is accepted that arbitrators are bound by the parties' choice and their power comes from the agreement of parties, it should be questioned whether they need to execute every choice of parties even if the choice is against mandatory provisions of lex arbitri or general accepted due process norms. Last but not least, courts' role on determining the party autonomy will be questioned. The power of courts to intervene in the arbitral process determine the practical limits of the autonomy of parties. During the arbitration process, the court may intervene in the process to help or control the arbitration; but real control power comes from when one of the parties asks courts to set aside or enforce the arbitral awards. While courts examine the arbitral awards, they also indirectly decide the limits of party autonomy. Therefore, this section will examine, which restrictions will affect the fate of the arbitral awards and how the courts should evaluate these restrictions. In conclusion, the dissertation will mainly investigate the topic of freedom of parties to determine the procedural issues in international commercial arbitration. It will aim to interpret and make use of the party autonomy doctrine as coherent as it can in the modern age. By illustrating the definition and limitations of the party autonomy in the procedural issues in international commercial arbitration, the dissertation will try to find a common international ground. This common ground may help to keep arbitration processes efficient while it provides fair hearings.
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitration boards; Commercial Arbitration; Commercial law; Free will; Hakem usulu; International Arbitiation Law; International Chamber of Commerce; Milletlerarası Tahkim Kanunu; Party autonomy; Procedural law; Tahkim; Tahkim kurulları; Ticaret hukuku; Uluslararası Ticaret Odası; Usul hukuku; Özgür istenç; İrade muhtariyeti

Anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve sınırları - Vezi̇roğlu, Cem (İstanbul Üniversitesi, 2020)
Bu doktora tezi, anonim ortaklıklar hukukunda esas sözleşme özgürlüğü ve bunun sınırlarının çeşitli açılardan incelenmesini konu almaktadır. Üç bölümden oluşan tezin ilk bölümü konunun kuramsal çerçevesini çizmeyi hedeflerken, ikinci ve üçüncü bölümler ise mevcut sorunlar karşısında dogmatik hukuk bakımından çözümler geliştirmeyi amaçlamaktadır. Bu kapsamda öncelikle özel hukukta ve ortaklıklar hukukunda sözleşme özgürlüğünün kavramsal, teorik, tarihsel, anayasal, ekonomik ve ahlaki zemini ortaya koyulmuştur. İkinci bölümde sözleşme özgürlüğünün anonim ortaklıklar hukukundaki görünümü ele alınmış ve bunu hayata geçiren en önemli işlem olan esas sözleşme çeşitli açılardan irdelenmiştir. Son bölümde ise esas sözleşme özgürlüğünün genel hükümler ve anonim ortaklıklar hukuku çerçevesindeki sınırları incelenmiştir. Bu bağlamda TK m. 340 hükmünde düzenlenen emredici hükümler ilkesine özel bir önem atfedilmiştir. Çalışmada disiplinler arası yöntemin esas alınması doğrultusunda ortaklık teorilerine ve hukukun ekonomik analizine başvurulmuştur. Anılan yöntemlerin katkısı hem pozitif hukuk hem de hukuk politikası açısından ortaya koyulmuştur. Ayrıca incelemede karşılaştırmalı hukuka ve tarihsel araştırmaya geniş yer ayrılmıştır. This doctoral thesis analyzes contractual freedom in articles of association and its limits in joint stock companies from various aspects. The thesis consists of three parts. While the first part aims to set the theoretical framework of the problem, the second and third parts intend to find solutions vis-à-vis existing problems in terms of positive law. Within this scope conceptual, theoretical, constitutional, economic and ethical aspects of contractual freedom in private law and corporate law are primarily examined. The second part deals with contractual freedom in corporate law and examines articles of association from various perspectives as it is the most important legal act that brings contractual freedom into being. The last part analyzes the limits of contractual freedom in articles of association pursuant to general provisions of civil law and joint stock company law. In this regard, the principle of mandatory norms stipulated in Turkish Commercial Code numbered 6102 Article 340 is attached a particular importance. Theories of the corporation and economic analysis of law are applied in accordance with the interdisciplinary methodological view adopted in this study. Contribution of the mentioned methods are set forth in terms of both positive law and legal policy. Moreover, comparative legal analysis and historical analysis are used extensively.
Keywords: Anonim ortaklıklar; Anonim şirketler; Commercial law; Company law; Contracts; Contractual freedom; Emredici norm; Incorporated companies; Joint stock company; Peremptory norms; Sözleşme özgürlüğü; Sözleşmeler; Ticaret hukuku; Şirketler hukuku

İşletme yöneticilerinin ticari belgelerin tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri üzerine bir araştırma - Yardimcioğlu, Melek (Gaziantep Üniversitesi, 2020)
"Bu tez çalışması ile işletme yöneticilerinin ticari belge tanzim ve hukuki süreçlerine ilişkin bilgi ve algı düzeyleri ortaya konmaya çalışılmıştır. İşletme yöneticileri içinde faaliyet gösterdikleri ülkenin hukuki kurallarına göre iş piyasası ve iş hayatında faaliyet gösterirler. Ve bu kurallar ticari hayat içinde onlar için en önemli bağlayıcı normlardır. Bu çalışma ilgi ticaret hukukunun iş hayatında en önemli faaliyet ve uygulama alanı bulan ticari belge tanzimi ve hukuki süreçlerinin yöneticiler tarafından ne seviyede algılandığının ortaya konması amaçlanmıştır. Tez çalışma dört bölümden oluşturulmuştur. İlk bölümümüz giriş bölümüdür. İkinci bölümde yönetim konuları, ticari belgeye ilişkin hukuki argümanlara yer verilmiştir. Üçüncü bölüm uygulama bölümüdür. Dördüncü bölümde ise sonuç ve yorumlara yer verilmiştir. With this thesis, the level of knowledge and perception of business executives regarding the issuance and legal processes of commercial documents has been tried to be revealed. Business executives operate in the labor market and business life according to the legal rules of the country in which they operate. And these rules are the most important binding norms for them in commercial life. With this study, it is aimed to reveal the level of perception of commercial document arrangement and legal processes, which find the most important field of activity and application in business life, by managers. The study is composed of four parts. Our first part is the introduction. In the second part, administrative issues and legal arguments related to the commercial document are included. The third part is the implementation part. In the fourth section, results and comments are given."
Keywords: Bilgi düzeyi; Business management; Commercial documents; Commercial law; Level of knowledge; Managers; Ticaret hukuku; Ticari belgeler; Yöneticiler; İşletme yönetimi